Les principes en droit de la famille - Romand-Gerbault, Isaure de (Université de Rennes, 2023)
Le principe est une norme issue de la jurisprudence dont l’ascendance se caractérise par une grande généralité et par un régime juridique souple. En effet, à partir de la seconde moitié du XXe siècle, le juge a eu recours à deux types de principes. Le premier groupe de principes guide la jurisprudence afin d’obtenir un droit de la famille cohérent. Ils sont issus de l’esprit de l’ensemble des normes de droit de la famille. Les uns sont très proches de la morale, ce sont la dignité, l’égalité et la solidarité. Les autres structurent la famille ; il s’agit de la monogamie et l’exogamie. Le second grand corps de principes permet de régir des objets spécifiques qui nécessitent un régime juridique trop subtile pour être contenu par écrit. Ces derniers sont ceux visés par un arrêt de la Cour de cassation. Deux d’entre eux sont directement attachés à la famille : les souvenirs de famille et le nom de famille. Les autres ont un impact sur la vie familiale : infans conceptus, l’indisponibilité de l’état des personnes, le don manuel et le non arrérage des aliments. L’étude de ces principes a conduit à constater leur autonomie. Leur nature extratextuelle les place en dehors de la pyramide des normes. Ils font plutôt office de contrepoids puisqu’aujourd’hui la résolution des conflits familiaux ne peut se satisfaire d’une norme textuelle toute-puissante. Pourtant, dans un droit de la famille en constante révolution, les principes voient leur effectivité affectée au fil des décisions. Le risque est de voir alors la force des principes en droit de la famille pleinement relative.
Keywords: Famille (droit); Law; Principes; Principes généraux du droit; Principles; Sources

L'arme numérique : essai sur la dématérialisation des infractions pénales - Chabaud, Laurent (Université de Montpellier, 2023)
Le développement d’Internet, et du numérique en général, a facilité la commission de bon nombre d’infractions et a fait son entrée dans la majorité des branches du droit pénal. Pourtant il reste une branche du droit pénal où le numérique n’a pas fait son entrée : l’atteinte à l’intégrité physique de la personne. Ce rejet, pourtant logique, ne pose-t-il pas question ? Le développement des objets connectés à Internet permet d’envisager que ces atteintes deviennent réalité. Il faut donc intégrer la possibilité de réaliser de telles atteintes au sein du Code pénal. La première partie propose d’étudier cette possibilité par un rapprochement entre les notions d’arme et de numérique pour créer la notion d’arme numérique. Si ces notions paraissent antinomiques, elles sont au contraire relativement proches. Leur intégration au sein du Code pénal permet de montrer qu’elles obéissent au même mécanisme : la sanction de l’usage d’un outil particulier, l’arme ou le numérique, pour réaliser l’infraction. Nous proposons donc un changement de paradigme dans l’analyse de l’arme pour rapprocher ces notions. Cette rethéorisation de l’arme autour de sa fonction, que nous appelons le mode de perpétration, permet une meilleure prise en compte de la dématérialisation des infractions. La seconde partie quant à elle, s’attache à dresser le régime de l’arme mode de perpétration pour intégrer l’arme numérique en permettant de renforcer l’efficience économique de la loi en matière de lutte contre la cybercriminalité. Cela permet notamment une prise en compte globale de la cybercriminalité en favorisant une analyse proactive plutôt que simplement réactive.
Keywords: Actes juridiques électroniques; Arme numérique; Criminal law; Cybercriminality; Cybercriminalité; Dematerialization; Digital weapon; Droit pénal; Dématérialisation; Theory of aggravating circumstances; Théorie des circonstances aggravantes

L'institution du dialogue social dans les entreprises du secteur privé - Mellot, Dorian (Université Lumière Lyon 2, 2023)
Le syntagme « dialogue social » est présent dans le discours du Législateur pour motiver ses réformes des relations collectives et dans le discours législatif lui-même au bénéfice de ces même réformes. Cependant, il n’est défini par aucun de ces discours, malgré trois chapitres du code du travail qui y sont consacrés et un article relatif à la formation des salariés, des employeurs ou de leurs représentants à celui-ci. Il s’agit donc dans cette thèse de déterminer ce qui le singularise d’autres expressions qui pourraient être tenues pour synonymes, comme celle de « relations collectives ». Le cas échéant, nous cherchons à identifier le modèle de relations collectives que le Législateur signifie par l’emploi et l’institution de ce syntagme. Il nous apparaît que ce modèle repose sur la décentralisation de la production normative, entendue comme un repositionnement de l’Etat afin de permettre une adaptation des organisations économiques à leur environnement économique et financier.
Keywords: Accord; Agreement; Collective bargaining; Comité social et économique; Comités sociaux et économiques; Company; Decentralisation; Décentralisation; Employee representation; Entreprise; Etat; Négociation collective; Négociations collectives; Partenaires sociaux; Représentation du personnel; Social and economic committee; State

La distinction entre recours en annulation et exequatur en droit français de l'arbitrage international - Alain, Alex (Université Paris 1, 2023)
S’interroger sur la distinction entre le recours en annulation et exequatur, c'est poser la question du régime juridique applicable à chacun de ces mécanismes de contrôle de la sentence arbitrale. Ces derniers paraissent, par hypothèse, différenciés puisqu’ils relèvent de deux catégories de procédures que le droit français ne confond pas : les voies de recours et l’exequatur. L’application des règles du droit processuel français commande donc en principe de ne pas confondre le recours en annulation, qui est une voie de recours, avec l’exequatur. Or, s’il est bien une notion qui innerve tous les pans du droit français de l’arbitrage international, c’est celle d’« autonomie ». Il en résulte que malgré la référence expresse à des notions bien connues du droit commun - i.e 1’exequatur et la voie de recours pour le recours en annulation -, celles-ci paraissent recevoir une acception spéciale en droit français de l’arbitrage international. Gommant les différences qui séparent traditionnellement les voies de recours de l’exequatur, le droit français de l’arbitrage international semble à bien des égards confondre le recours en annulation et l’exequatur. Émerge ainsi l’idée que les sentences arbitrales font l’objet d’une procédure de contrôle unique. Une confusion certaine entre le recours en annulation et l’exequatur existe en droit français de l'arbitrage international, elle est à l’origine de nombreuses incertitudes. Pour remédier à ce constat, l’étude propose l’application aux sentences arbitrales des règles du droit commun, relatives aux voies de recours et à l’exequatur.
Keywords: Action for annulment; Arbitrage international; Civil Procedure; Contrôle de la sentence arbitrale; Distinction; Droit international privé; Exequatur; International Arbitration Law; Jugements étrangers; Private International law; Procédure civile; Recours en annulation; Voie de recours; Voies d'exécution

Les sanctions unilatérales de l'inexécution du contrat - Pinier-Rafer, Julia (Université Jean Moulin Lyon 3, 2023)
L’exception d’inexécution, la faculté de remplacement unilatérale du débiteur défaillant dans le cadre de l’exécution forcée indirecte, la réduction unilatérale et proportionnelle du prix et la résolution par voie de notification constituent, depuis l’ordonnance du 10 février 2016, les sanctions unilatérales légales de l’inexécution du contrat. Elles autorisent le créancier, en dehors de toute intervention judicaire, à intervenir lui-même sur le sort du contrat dans le cas où son débiteur n’a pas respecté ses engagements. Si à première vue certains de ces mécanismes unilatéraux sont connus et reconnus, notamment dans le cadre des droits spéciaux, ce n’est pas le cas de tous. Leur consécration en droit commun des contrats est une véritable innovation. Dans une logique d’efficacité économique cette intégration est la bienvenue. Toutefois, encore faut-il que cette dernière soit satisfaisante, d’autant plus que l’admission des sanctions unilatérales bouleverse la conception traditionnelle du contrat basée sur l’accord de volontés. Corrélativement, le principe de sa force obligatoire est généralement réfractaire à accorder à la volonté unique le pouvoir de produire des effets de droit. Cette étude propose alors d’apprécier l’intégration de ces nouvelles mesures dans le droit commun des contrats, avec pour intuition de départ que cette dernière n’est pas satisfaisante et qu’elle pourrait remettre en cause l’efficacité et la pérennité de celles-ci. Parce que les sanctions unilatérales s’intègrent désormais dans un nouveau droit de l’inexécution centralisé au sein des articles 1217 et suivants du Code civil, une étude approfondie de toutes les dispositions en lien avec celles-ci doit être menée. Un tel travail est nécessaire et justifié pour déceler les éventuelles difficultés relatives au régime de chaque sanction. De surcroît, la critique de l’intégration des sanctions unilatérales conduit à mettre en exergue une contradiction entre ces dernières et la conception du contrat retenue par la réforme, un silence relatif à leur nature juridique et une absence de prise en compte de la partie faible à un contrat d’adhésion dans le régime de celles-ci. À l’issue, si un réaménagement complet des sanctions unilatérales n’apparait pas opportun, des corrections techniques et théoriques se révèleront utiles pour améliorer l’intégration des sanctions unilatérales dans le droit commun des contrats. L’impératif de protection de la partie faible et la prise en compte de la qualification des sanctions unilatérales en prérogatives contractuelles peuvent être des éléments déterminants pour, à la fois, rendre pérenne l’intégration des nouvelles sanctions unilatérales et améliorer des éléments de leur régime.
Keywords: Contrat d'adhésion; Contrat de gré à gré; Contrats; Exception d’inexécution; Exception d’inexécution préventive; Exécution forcée en nature; Exécution forcée indirecte; Faculté unilatérale de remplacement du débiteur défaillant; Inexécution; Inexécution du contrat; Protection de la partie faible; Réduction unilatérale et proportionnelle du prix; Réforme; Résolution unilatérale; Résolution unilatérale anticipée; Sanctions (droit); Sanctions de l’inexécution; Sanctions unilatérales; Unilatéralisme

Le non-exercice des droits subjectifs - Villalonga, Florian (Université de Limoges, 2023)
Le non-exercice des droits subjectifs est un phénomène courant auquel tout justiciable est un jour confronté. Il s'agit du titulaire d'une option qui ne sait pas quel parti prendre et se prononce trop tard, de celui qui subit une atteinte à l'un de ses droits mais ne sait pas comment le défendre, de celui qui est bénéficiaire potentiel, sans le savoir, d'une prestation sociale qu'il oublie de réclamer. L'époque est loin du petit commerce de village dont le propriétaire ménage certains clients connus de longue date qui, ayant promis de le payer une prochaine fois, n'ont jamais tenu leur parole, et auxquels il ne viendra pas réclamer son dû. L'inaction est aujourd'hui massive puisque le droit est complexe et les prérogatives individuelles multiples. Derrière elle se nichent une multitude de comportements, de la passivité consciente à la résignation, de l'oisiveté à la vulnérabilité. Pour les comprendre, ce travail propose de dévoiler le panel d'attitudes envisageables en les catégorisant selon des ensembles cohérents, tel le rassemblement ordonné des pièces d'un puzzle forme une image. Cette limpidité trouvée, le constat est fait que chaque type de non-exercice mérite une réponse adaptée. Le traitement juridique du non-exercice s'effectue donc en considération du comportement initial, le vulnérable est incité à agir, quiconque subissait une influence extérieure et ne pouvait agir est assisté pour le faire, celui qui profitait de l'inaction pour nuire à autrui est sanctionné. Mais l'éventail de comportements étant large, le panel de sanctions est logiquement complet. L'étude du non-exercice des droits subjectifs est ainsi l'occasion d'aborder l'état d'esprit du justiciable et de revisiter diverses notions, comme la prescription, la renonciation, eu égard à une thématique capitale et pourtant très peu étayée.
Keywords: Droits subjectifs; Force majeure; Passivity; Passivité; Prescription; Renonciation; Waiver

L'association du travail au capital : de l'échec de l'intégration à la conversion - El Kdim, Karim (Université de Limoges, 2023)
Le travail et le capital sont deux notions fondamentales qui pourraient paraître antinomiques. Notre droit place ces deux notions fondamentales au cœur des législations économique et sociale. Dans cette perspective, a été constitué un arsenal juridique visant à associer les salariés aux bénéfices de l'entreprise ainsi qu'au capital social. La participation des salariés aux bénéfices s'applique à toutes les sociétés mais n'est obligatoire que pour les entreprises employant un certain effectif. L'association des salariés au capital social demeure quant à elle "marginale" ; son champ d'application étant d'ailleurs réservé aux sociétés par actions et aux sociétés coopératives telles que les SCOP (sociétés coopératives de production ouvrière et les SAPO (sociétés anonymes à participation ouvrière). Notre thèse vise à conceptualiser deux modèles de conversion de l'activité humaine en part de capital : la conversion du travail salarié et la conversion de l'industrie apportée. Ainsi deviendrait effective l'association du travail au capital.
Keywords: Actionnariat; Apport en industrie; Capital; Droit du travail; Labour law; Participation; Shareholding; Stock-Options; Work

L'autonomisation des moyens de transport - Folliot, Océane (Université de Bordeaux, 2023)
Avec le développement de l'intelligence artificielle, sont apparus les robots intelligents, qui sont capables de simuler l'intelligence humaine dans des fonctions qui reviennent traditionnellement à l'homme. Ce phénomène de remplacement de l'homme par les machines autonomes s'observe notamment en matière de transports, avec l'émergence des véhicules autonomes, qui se distinguent des véhicules sans équipage. Ce processus d'autonomisation amorce une réflexion chez le juriste : qu'est ce que l'autonomie du moyen de transport ? Doit-on circonscrire cette autonomie ? Dans quelle mesure faut-il adapter le droit ?
Keywords: AI; Artificial Intelligence; Inteligência artificial; Intelligence Artificielle; Liability; Responsabilité; Robot; Systèmes de transport intelligent; Transport; Transport -- Droit; Véhicules autonomes; Véhicules connectés

L'application du droit des obligations en droit fiscal : (contribution à l'étude de l'autonomie et du réalisme du droit fiscal) - Bretaudeau, Valérie (Université Paris 1, 2023)
Le postulat est l’existence d’un principe d’application du droit des obligations en droit fiscal. Puis, la réflexion a porté sur la consécration du principe, soit son existence et son expansion. Concernant son existence, l’origine du principe impliquait de revenir brièvement sur les controverses relatives à l’autonomie et au réalisme du droit fiscal et d’affirmer, à la suite de la doctrine, que ni l’une, ni l’autre n’existait. En effet, le droit fiscal est un droit de superposition. Ainsi, sauf exceptions, il est soumis aux autres disciplines juridiques dont le droit des obligations. Il serait aussi d’interprétation stricte. La thèse mettra en évidence que l’éventail des procédés d’interprétation est large et que le droit fiscal, n’est pas seulement interprété de manière stricte. En outre, une interprétation large du droit fiscal n’exclut pas l’application du droit des obligations, notamment. Quant aux manifestations du principe de l’application du droit des obligations en droit fiscal, et grâce à des exemples, elles se matérialisent par les renvois au droit civil aussi bien à ses définitions qu’à ses qualifications. S’agissant de l’expansion du principe en question, l’accent est mis sur ses deux origines, législative et jurisprudentielle. Là encore des exemples choisis illustreront les propos. Ensuite, la thèse s’intéresse aux fondements des exceptions à l’application du droit des obligations en droit fiscal. Il y a les règles spéciales de la fiscalité, d’une part. Il y a lutte contre la fraude et l’évasion fiscale, d’autre part.
Keywords: Droit des obligations; Droit fiscal; Impôt; Obligations (droit)

La régulation de la concurrence en France et en Tunisie à la lumière du droit économique européen - Bhouri, Habiba (Université Jean Moulin Lyon 3, 2023)
En France, la décision d'ouvrir le marché à la concurrence et à l'économie de marché a été prise de manière autonome en tant que décision politique nationale, marquée par la réforme des monopoles publics. En revanche, en Tunisie, le processus de libéralisation a été mis en place sous la pression des principales institutions financières internationales en réponse aux défis économiques auxquels le pays était confronté. La Tunisie a été contrainte d'adopter certaines directives visant à accroître sa compétitivité sur les marchés mondiaux, ce qui a conduit à la création de mécanismes de régulation plus flexibles et transparents. L'analyse du cas tunisien est d'un intérêt particulier, car elle met en évidence l'influence juridique exercée sur certains pays lorsqu'ils se préparent à rejoindre l'Union européenne ou à établir des partenariats avec elle. Cette évolution peut être examinée à travers d’une part, l'analyse du cadre juridique, et d’autre part, le cadre institutionnel et opérationnel de la régulation de la concurrence.
Keywords: Anti-Competitive practices; Comparative law; Competencia; Competition law; Concurrence; Concurrence (droit); Contrôle des concentrations; Droit comparé; Droit français; Droit tunisien; Droit économique européen; European economic law; France; French law; Merger control; Pratique anticoncurrentielle; Regulation; Régulation; Tunisian law; Tunisie; Études comparatives

Ecriture de contrats intelligents : essai de méthodologie en droit et en informatique - Diallo, Abdoulaye (Université Grenoble Alpes, 2023)
Les smart contract sont des programmes informatiques qui ont pour principale caractéristique d’être déployés dans une blockchain. Comme le suggère leur appellation, ils peuvent être utilisés afin d’automatiser l’exécution de véritables contrats. L’objectif de notre recherche est de développer une méthodologie pour créer ces conventions dont des stipulations sont codées informatiquement et exécutées dans une blockchain. A travers notre proposition, nous présenterons leurs contextes d’utilisation les plus pertinents : quels sont les contrats les plus enclins à une exécution par smart contract ? Nous établirons la forme la plus appropriée que doivent prendre ces conventions : doivent-elles être écrites uniquement en code informatique ou pourvues également d’un texte rédigé en langage naturel ? Que doit-être le rôle et le contenu de ce dernier ? Enfin nous exposerons comment procéder techniquement à leur réalisation : sur quelles blockchain les déployer et de quelle manière peut-on coder leurs stipulations dans le langage de programmation Solidity ? Smart contracts are computer programs that are primarily deployed within a blockchain. As their name suggests, they can be used to automate the execution of real contracts. The objective of our research is to develop a methodology for creating these agreements, in which stipulations are coded computationally and executed within a blockchain. Through our proposal, we will present their most relevant use cases: which contracts are most suitable for execution by smart contracts? We will establish the most appropriate form these agreements should take: should they be written solely in computer code or also include text written in natural language? What should be the role and content of the latter? Finally, we will explain how to proceed technically with their implementation: on which blockchains to deploy them and how to code their stipulations using the Solidity programming language.
Keywords: Blockchain; Blockchains; Contrats intelligents; Legaltech; Smart contract

Les évolutions juridiques relatives à l'activité économique portuaire : contribution à l'étude de la réforme portuaire de 2008 - Karfoul, Mais Alrim (Université Toulouse Capitole, 2023)
Malgré les réformes consécutives dans l’optique de moderniser les grands ports de commerce, ces derniers restent organisés selon un processus traditionnel de gestion d’établissement public étatiques. Mais depuis un certain temps, ces établissements se sont vus transformés dans leur activité économique ; celle-ci est réduite à certains périmètres classiques dans le but d’adapter son cadre de production avec l’impératif de relance économique des infrastructures essentielles dans le secteur, mais également pour se mettre en conformité avec le droit européen s’imposant pleinement lorsqu’il y aurait à constater des activités économiques. Bien que les équipements nécessaires à l’exercice de l'activité économique soient transférés au secteur privé lors de la réforme de 2008, à savoir la manutention portuaire, l’établissement public portuaire demeure propriétaire du domaine public, support de ces équipements. Il est également le gestionnaire général responsable du pilotage du port et de son développement durable, ce qui n’est pas sans conséquence dans la gestion et l'organisation afin d'assurer la bonne gestion des ports. Des conflits d’intérêts se révèlent alors dans la gestion des ports, et la recherche d’un régime juridique adapté serait déterminante pour trouver l’équilibre entre ces différentes exigences, et assurer une efficacité économique du modèle des grands ports maritimes.
Keywords: Activité économique; Aspect économique; Concessions portuaires; Contractualisation; Contractulisation; Domanialité publique; Economic activite; Etablissement public; General interest; Intérêt général; Port; Ports; Public domain; Public establishement

Le développement du recours aux modes amiables en matière civile : étude comparée entre la France, les Etats-Unis et le Canada - Watrin, Geoffrey (Université de Strasbourg, 2023)
Darwin disait que « les espèces qui survivent ne sont pas les espèces les plus fortes ou les plus intelligentes, mais celles qui s’adaptent le mieux aux changements ». La justice n’échappe pas à cette règle. Sans cesse confrontée à de nouveaux défis, tels que l’encombrement judiciaire ou la pacification des relations entre les parties, cette dernière va devoir trouver les moyens qui lui permettront de fonctionner en accord avec les besoins de son temps. Les modes amiables de résolution des conflits pourraient bien en faire partie. Implantés de longue date et particulièrement appréciés aux États-Unis et au Canada, ces derniers semblent pour l’heure boudés par les praticiens et les justiciables en France. Le législateur montre néanmoins un intérêt de plus en plus important pour ces méthodes et pour cause : elles ont fait leurs preuves Outre-Atlantique. Dès lors, comment parvenir à les développer au sein de notre système ? C’est la question à laquelle nous essayerons de répondre dans cette thèse.
Keywords: ADR; Canada; Development; Droit comparé; Développement; France; MARC; Mediation; Modes amiables; Médiation; Procédure civile; United States; États-Unis

Le juge judiciaire et la conventionnalisation du droit du travail - Bouquard, Paul (Université Clermont Auvergne, 2023)
La normativité des conventions et accords collectifs au sein du panorama des sources propres au droit du travail n’a cessé d’évoluer au fil des réformes législatives. Cette évolution de la normativité conventionnelle, faisant aujourd’hui de l’accord collectif la norme privilégiée dans la réglementation des conditions de travail et d’emploi, porte un nom : conventionnalisation. Si ce mouvement a pour origine la volonté du législateur, le juge judiciaire en est également un acteur à part entière. Ce dernier n’a eu de cesse de valoriser la conventionnalisation de par la multitude de ses solutions prétoriennes dans toute une série de domaines diverses et variés. A ce titre, l’accompagnement de la valorisation de la conventionnalisation par l’activité jurisprudentielle du juge de l’ordre judiciaire se fait à plusieurs niveaux. Au stade de la négociation - en particulier d’entreprise - tout d’abord, le renforcement de la normativité conventionnelle passant bien évidemment par un renforcement des exigences relatives à la phase de négociation en tant que telle. Au stade de l’application de l’accord collectif ensuite, où le juge judiciaire a notamment adapté le principe d’égalité de traitement au contexte de la conventionnalisation. Mais les rapports entre le rôle du juge et la conventionnalisation ne se limitent pas à l’activité jurisprudentielle. Celui-ci est aussi tributaire d’une activité juridictionnelle, dont le lien avec l’activité jurisprudentielle est d’ailleurs omniprésent. De par cette dernière, le juge judiciaire est venu modifier à la fois son pouvoir de contrôle sur la négociation collective dans son ensemble, et son pouvoir d’interprétation de l’accord collectif. C’est à la suite de tels constats que nous nous proposons d’approfondir ces différents rapports de valorisation : celle de la conventionnalisation par l’activité jurisprudentielle du juge judiciaire, qui par conséquent va engendrer celle de son activité juridictionnelle. The normativity of collective bargaining within the panorama of sources specific to labor law has continued to evolve with the legislative reforms. This evolution of contractual normativity, which today makes the collective agreement the preferred norm in the regulation of working and employment conditions, has a name : conventionalisation. If this movement originates from the legislator's will, the private law judge is also a full-fledged actor. He has constantly promoted conventionalisation through the multitude of its case law rulings in a whole series of diverse and varied fields. In this respect, the development of the value of conventionalisation by the jurisprudential activity is accompanied at several levels. First of all, at the negotiation stage of company-level agreements, the strengthening of the normativity of bargaining obviously involves a strengthening of the requirements relating to the negotiation phase as such. Secondly, at the stage of application of the collective agreements, where the courts have adapted the principle of equal treatment to the context of conventionalisation. But the relationship between the role of the judge and conventionalisation is not limited to case law. The judge is also dependent on jurisdictional activity, the link between which and jurisprudential activity is ubiquitous. Therefore, the private law judge has modified both his power of control over collective bargaining as a whole, and his power to interpret collective agreements. It is in the light of these observations that we propose to examine in greater depth these different relationships of valuation : the conventionalisation by the jurisprudential activity of private law judges, which consequently will generate that of his jurisdictional activity.
Keywords: Collective bargaining; Contractual normativity; Conventionnalisation; Droit du travail; Juge judiciaire; Labour law; Négociation collective; Négociations collectives; Private law judge

Contribution du droit pénal à la régulation des atteintes à l'environnement : réflexions à partir d'une comparaison des droits français et brésilien - Souid, Inès (Université Jean Moulin Lyon 3, 2023)
La nécessité de réguler les atteintes à l’environnement émerge dès les années 70. Le droit a été très tôt mobilisé comme remède à la crise environnementale. Mais en dépit de l'évolution du droit de l'environnement, la transition de la société, indispensable à la maîtrise de la crise, s’avère difficile. Devant cette impasse juridique et le besoin urgent de protéger la société de l'insécurité environnementale, nous avons remis en question la place qu'occupe le droit pénal dans cette quête visant à réguler les atteintes à l’environnement. Tient-il un rôle particulier ? En d'autres termes, s'agit-il d'une réponse, voire, d'une solution à la crise ? La progression des atteintes à l'environnement est liée à l’évolution des activités humaines. Évaluer la contribution du droit pénal à la régulation des atteintes à l’environnement exige donc une approche différente de la matière pénale. Il est nécessaire de confronter le droit pénal à des questions plus directes de régulation. Jusqu'ici, les études ont dévalorisé les tendances régulatrices du droit pénal de l’environnement. En ne reconnaissant pas ces particularités, on ne saurait pourtant tenir suffisamment compte de l'importance de la contribution du droit pénal à la régulation des atteintes à l’environnement. Ces travaux viennent compléter la compréhension du modèle de droit pénal de l'environnement en conceptualisant les transformations que le rapport entre le droit pénal et le droit de l'environnement engendre sur les normes pénales substantielles, sanctionnatrices et procédurales. Celles-ci définissent les critères d’une logique unique de régulation. Les courbes inédites du droit pénal de l'environnement établissent un véritable droit pénal de gestion au soutien de la réalisation d'une multitude d'objectifs de politique environnementale de plus en plus nombreux, audacieux, et fixés sur le long terme, à l'échelle locale comme mondiale. Si l'identité punitive du droit pénal résiste - nécessairement - la logique répressive semble tout à fait reléguée au second plan. Elle ne présente qu'un seul intérêt : alimenter une logique de régulation primaire pour poursuivre la correction des activités sociales générant les risques les plus significatifs pour l’environnement. Les réflexions menées s’appuient sur une comparaison des droits français et brésilien. Le modèle brésilien de droit pénal de l’environnement est parvenu à une certaine maturité. Ses révolutions sont plus évidentes et laissent entrevoir de nouvelles entrées dans l'examen du droit pénal de l'environnement français. L’étude de l'apport du droit pénal à la régulation des atteintes à l’environnement invite le lecteur à se familiariser avec une autre version du droit pénal appelée à se développer. Le droit pénal de l'environnement est axé sur l'avenir de la vie sociale. Il ne cherche pas à conserver un modèle d’organisation des activités sociales mais à le corriger, à le transformer, à le faire évoluer afin de garantir l’accès aux générations présentes et futures à un environnement intègre et sain. C'est un droit pénal dynamique qui cadre avec les défis hypercomplexes de régulation sociale de son époque. Il donne un peu plus d'informations sur les fondements d'un droit pénal postmoderne. Le droit pénal de l'environnement s'impose ainsi en tant que véritable réponse à la crise. Mais il lui reste à trouver les bons outils pour supporter ses profondes transformations. Cette thèse jette aussi les bases d'une meilleure réponse du droit pénal à la crise environnementale. Un nouveau modèle de droit pénal de l’environnement est théorisé afin de satisfaire aux attentes d'efficacité de la régulation des atteintes à l'environnement.
Keywords: Administration; Administrative law; Anticipation; Autorégulation; Brazilian law; Brésil; Comparative law; Compliance; Conformité; Constitutional law; Corporate environmental performance; Criminal Law; Criminal procedure; Disciplinaire; Disciplinary; Dispositions pénales; Disseminated interests; Dommages irréversibles; Droit administratif; Droit brésilien; Droit comparé; Droit constitutionnel; Droit de l'environnement; Droit fondamental de l'environnement; Droit pénal; Droit pénal de l'environnement; Droit répressif; Droit souple; Efficacité; Efficiency; Environmental criminal law; Environmental damage; Environmental governance; Environmental information; Environmental law; Environmental management; Environmental policy; France; Fundamental environmental law; Gestion de l'environnement; Glocal; Good administration; Gouvernance environnementale; Incertitude scientifique; Informations environnementales; Infractions contre l'environnement; Intérêts diffus; Irreversible damage; Legal pragmatism; Performance environnementale des entreprises; Politique environnementale; Pragmatisme juridique; Precaution; Prevention; Procédure pénale; Précaution; Préjudices environnementaux; Prévention; Regulation; Repressive law; Risks; Risques; Régulation; Scientific uncertainly; Self-regulation; Social en environmental transition; Soft law; Spheres of decision; Sphères de décision; Transaction sociale et environnementale; Études comparatives

La régulation du lobbying en droit économique - Mbaka, Axel (Aix-Marseille Université, 2023)
La question de l’encadrement juridique du lobbying a longtemps été oubliée par le droit Français. Pendant un temps, seuls le droit pénal et l’autorégulation formaient les contours du faisable. Inspirée d’exemples étrangers, la loi n°2016-1691 du 9 décembre 2016 relative à la transparence, à la lutte contre la corruption et à la modernisation de la vie économique, dite « loi Sapin 2 », a renversé le paradigme en créant des obligations de transparence pour les lobbyistes et les pouvoirs publics. Pour contrôler le respect de ces obligations, la loi a aussi créé la Haute Autorité pour la Transparence de la Vie Publique (HATVP). Toutefois, à peine née, la régulation du lobbying est confrontée aux défis contemporains du droit économique. À l’heure des autorités de régulation, de la privatisation du pouvoir normatif et de la résurgence des nations, que peut encore la régulation du lobbying ?
Keywords: Contrôle de l'État; Droit économique; Economic law; Interest representatives; Lobbying; Loi Sapin 2; Lutte contre la corruption; Regulation; Représentants d'intérêts; Régulation; Sapin 2 law; Transparence; Vie publique

Le Conseil d'État et la régulation des marchés financiers - Sevagamy, Romuald (Université de Montpellier, 2023)
La contribution à la régulation des marchés financiers par différents acteurs tels que l’Autorité des marchés financiers (AMF), les institutions européennes ou le juge judiciaire, a fait l’objet d’importants travaux. Toutefois, la juridiction administrative n’a pas reçu les mêmes honneurs. Dans le cadre du contentieux de la régulation des marchés financiers, la compétence du Conseil d’État a été davantage décriée que saluée. En effet, d’aucuns ont pu soutenir que les difficultés résultant du dualisme juridictionnel en matière financière, justifieraient la suppression de la compétence de l’ordre administratif. La compétence unique de l’ordre judiciaire pour connaître des décisions individuelles de l’AMF, telles que les sanctions, étant présentée comme un remède à la complexité du contentieux de la régulation financière. Si bien que l’on est amené à se demander si la présence du juge administratif dans cette matière est véritablement indispensable. En d’autres termes, se pose la question de savoir si le Conseil d’État est nécessaire à la régulation des marchés financiers. La présente thèse a pour ambition d’apporter une réponse résolument affirmative. Depuis la création de l’AMF, la compétence en premier et dernier ressort du juge administratif a été étendue de manière importante. Ce dernier étant désormais compétent pour connaître des recours contre les décisions individuelles, prises à l’encontre des professionnels des marchés. La jurisprudence administrative constitue également une source d’enrichissement significative du droit de la régulation financière. En effet, tant les garanties procédurales que les règles de fond, qui encadrent le pouvoir de sanction de l’AMF, ont été consolidées par le juge administratif. Ainsi, le Conseil d’État s’est affirmé en tant qu’acteur incontournable de la régulation des marchés financiers.
Keywords: Administrative litigation; Administrative penalties; Autorité des marchés financiers; Contentieux administratif; Dualisme juridictionnel; Financial markets regulation; Jurisdictional dualism; Office du juge; Office of the judge; Places financières; Régulation des marchés financiers; Sanctions administratives

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Les marques corporelles : contribution au statut du corps humain - Mitaine, Chloé (Université de Lille, 2023)
Is the human body a person or is it just a tool at its service? Is it an individual or is it just an object? In an attempt to solve this enigma, classical legal doctrine distinguishes the status of the body associated with a person from that which is dissociated from one. When the body is home to an individual, it is protected by civil and criminal laws relating to persons. When the body isn’t, or no longer is, home to an individual, it would then fall under the civil and criminal laws relating to goods. Laws relating to both goods and persons would thus work together to ensure a complete protection of the human body. The appearance of bodily marks, innate or wanted, on the legal scene (like tattooing, body painting, scarifications) provides a challenge: does it not upset the classical analysis? Does the human body not become a simple good owned by an individual? Why do bioethical laws not regulate these new cultural practices? Should they be left in a legal vacuum? Should the principle of respect for human dignity be reduced to respect for the will of the individual who must be able to transform his body as he sees fit under the auspices of an ever more liberal legal regime? The word «brand» is not neutral and evokes intellectual property: should the individual’s right to his body be fully attached to ownership rights? Should we permanently dissociate the body from the person? Is the human body a person or is it just a tool at its service? Is it an individual or is it just an object? In an attempt to solve this enigma, classical legal doctrine distinguishes the status of the body associated with a person from that which is dissociated from one. When the body is home to an individual, it is protected by civil and criminal laws relating to persons. When the body isn’t, or no longer is, home to an individual, it would then fall under the civil and criminal laws relating to goods. Laws relating to both goods and persons would thus work together to ensure a complete protection of the human body. The appearance of bodily marks, innate or wanted, on the legal scene (like tattooing, body painting, scarifications) provides a challenge: does it not upset the classical analysis? Does the human body not become a simple good owned by an individual? Why do bioethical laws not regulate these new cultural practices? Should they be left in a legal vacuum? Should the principle of respect for human dignity be reduced to respect for the will of the individual who must be able to transform his body as he sees fit under the auspices of an ever more liberal legal regime? The word «brand» is not neutral and evokes intellectual property: should the individual’s right to his body be fully attached to ownership rights? Should we permanently dissociate the body from the person?
Keywords: Biens (droit); Bioéthique (droit); Body marks; Chose; Consentement (droit); Corps humain; Dignité de la personne (droit); Expression de la volonté (droit); Human body; Marques corporelles; Person; Personne; Personnes (droit); Property; Propriété; Status; Statut; Tatouage; Thing

L'arrêt de travail : symptôme d'un mal-être au travail ou syndrome précontentieux ? : étude du mécanisme sous le prisme du débat : entre souffrance psychique liée au travail et instrumentalisation de l'arrêt maladie - Sloovere, Mathilde De (Université Paris 1, 2023)
Face à l’évolution des relations de travail et aux métamorphoses de leurs conditions d’exercice, le cadre du recours à l’arrêt maladie est en pleine mutation. Bien que plébiscité sur la scène internationale, le mécanisme français de l’arrêt maladie fait l’objet de vives critiques. Entre surprotection des salariés pour les uns et, au contraire, abandon des travailleurs en souffrance psychique pour d’autres, les arguments respectifs sont nombreux et influencent les comportements. L’approche juridique de l’arrêt maladie permet d’étudier les enjeux actuels. La thèse vise d’abord à éclaircir le dispositif de l’arrêt maladie et son cadre juridique. Pour qu’un arrêt maladie soit opportun, encore faut-il que les règles qui l’encadrent soient connues, maitrisées et appliquées par tous. Aujourd’hui, son application limitée ne fait pas l’unanimité. Les raisons ? Une connaissance lacunaire des dispositions en vigueur, leur technicité ou encore un contexte de travail non propice au recours à un arrêt maladie. Or, au-delà de toute considération subjective, le dispositif est complet. L’arrêt maladie est protecteur de la santé du salarié. Mais surtout, de nombreuses règles permettent une prévention efficace des risques puis, a posteriori, l’accompagnement du salarié lors de la reprise du travail. Peut être cité l’essai encadré. Peu connu, il assure une reprise du travail simplifiée et durable. La recherche, ensuite, permet d’établir des critiques objectives du mécanisme français et de proposer des mesures d’amélioration. L’objectif est d’aboutir à une meilleure protection de la santé mentale des salariés et de limiter les dérives dans l’utilisation de l’arrêt maladie. Faced with the evolution of labor relations and the metamorphosis of working conditions, the context of sick leave use is undergoing significant changes. Although acclaimed on the international scene, the French sick leave system is heavly criticized. Arguments on both sides are numerous and influence behaviors, ranging from overprotection of employees for some, to the abandonment of suffering workers for others. The legal approach of sick leave allows us to study the current challenges. The thesis first aims to clarify the sick leave mechanism and its legal framework. For sick leave to be appropriate, it is essential that the rules governing it be known, controlled, and applied by all. Today, its limited application eludes consensus. The reasons? A partial understanding of the current provisions, their technicality, or a work context not conducive to the use of sick leave. However, beyond any subjective consideration, the system is comprehensive. Sick leave is protective of employees’ health. More importantly, numerous rules allow for effective prevention of risks and, subsequently, the support of the employee when returning to work. “L’essai encadré”, the supervised trial period, can be used as an example. Little known, it ensures a simplified and sustainable way of returning to work. The research, then, allows for the establishment of objective criticisms of the French mechanism and proposes measures for improvement. The objective is to achieve better protection of the mental health of employees and to limit abuses in the use of sick leave.
Keywords: Absentéisme; Arrêt de travail; Arrêt maladie; Congé de maladie; Droit de la santé; Droit du travail; Health law; Labor law; Mal-être au travail; Santé au travail; Santé publique (droit); Sick leave

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

L'invisible et l'infraction - Barret, Elise (Université Grenoble Alpes, 2023)
Tout est invisible. Selon les sensibilités de chacun, tout, ou presque, peut en effet être qualifié ainsi. La matière pénale, qui retient notre attention dans cette étude, présente elle aussi de nombreuses occurrences de l’« invisible ». Entendue lato sensu, la matière fait état d’un vaste champ offert à l’invisible. Si tout peut ainsi être invisible, la réflexion, pour être cohérente, doit toutefois se limiter au cœur même du droit pénal : l’infraction. La notion traverse l’intégralité des matières pénales, en tant qu’elle constitue à la fois le début intellectuel du droit pénal lato sensu et l’aboutissement concret de celui-ci. Sans l’infraction, la matière pénale perd sa clé de voûte et n’a plus de raison d’être. La présente étude s’intéresse donc à l’invisible en tant qu’il impacte l’infraction. L'invisible est par définition ce qui n'est pas manifeste, qui échappe à la connaissance. Or, ce que l'on ne peut percevoir est parfois source d'inquiétudes. Rapporté à l’infraction, l’invisible renvoie au point de vue de l’autorité judiciaire puisque c’est à ses yeux que l'infraction doit exister pour que la machine pénale puisse se mettre en route. L’invisibilité envisagée est de sorte objective car elle n’apparaît pas aux yeux de l’institution actrice principale du procès pénal. Le terme d'invisible n'est pas courant en droit pénal, notamment parce qu'il semble étranger aux principes qui l'innervent. Or, à bien y regarder l’invisible se révèle constituer bien souvent un obstacle à la répression. Laquelle se retrouve empêchée par une incapacité technique, scientifique, ou circonstancielle. Si le terme peut de prime abord rappeler certaines notions déjà connues du droit pénal, le recours à la notion d’« invisible », présente toutefois l’avantage de couvrir un champ d’étude plus vaste, de prendre de la hauteur, d’envisager l’infraction sous un regard plus global afin de n’omettre aucune des difficultés que l’absence de visibilité peut causer à la répression. Surprenant de prime abord, le lien entre invisible et infraction est à bien y réfléchir plus évident qu’il n’y paraît. L’infraction, sous tous ses aspects, en tant qu’acte, donc étudiée de façon macrocosmique, comme en tant qu’incrimination, alors étudiée de manière microcosmique, peut faire l’objet de l’irruption paralysante du phénomène invisible. L’étude macrocosmique, soit celle des infractions en tant qu’acte dénote de l’existence d’infractions invisibles aux yeux des autorités judiciaires. L’infraction peut également faire l’objet de l’invisibilité dans son contenu. Etudiée d’un point de vue microcosmique, l’incrimination laisse entrevoir l’aspect intellectuel de l’infraction comme le siège évident de cette invisibilité au sein de l’infraction. Quant à l’aspect matériel de l’infraction, qu’on penserait à l’abri des difficultés liées à l’invisible, puisqu’il correspond à l’extériorisation de la pensée criminelle, il s’avère également impacté par celui-ci : évolution des technologies, dématérialisation, atteinte à l’intégrité psychique des victimes ou encore recours à des moyens psychologiques sont autant d’occasion pour l’invisible de venir entraver la répression. L’invisible gêne ainsi le travail répressif de deux manières : en empêchant la constatation des infractions, puisqu’il rend leur découverte délicate, et en entravant l’examen de la constitution de l’infraction, par les difficultés notionnelles et probatoires qu’il génère. Ainsi, cet obstacle insoupçonné à l’application de la loi pénale est un enjeu de taille auquel le droit pénal doit faire face fréquemment. L’invisible, ce non-dit de la matière pénale, vient alors éclairer nombre de pans du droit pénal en s’imposant comme une clé de lecture à certains régimes dérogatoires ou appréciations extensives, comme autant de moyens d’assurer l’efficacité du droit pénal lorsqu’il se retrouve confronté à ce qui lui demeure insaisissable. Everything is invisible. Depending on one's sensibilities, almost anything can be described as ''invisible''. Criminal law, which is the focus of this study, also features numerous instances of the ''invisible''. Understood in the broadest sense of the term, criminal law is a vast field open to the invisible. But if everything can be invisible, then to be coherent, the reflection must be limited to the very heart of criminal law: the offence. The notion runs through all criminal matters, insofar as it constitutes both the intellectual beginning of criminal law and its concrete outcome. Without the offence, criminal law loses its keystone and no longer has reason for being. This study therefore focuses on the invisible insofar as it impacts on the offence. The invisible is, by definition, that which is not manifest, that which escapes knowledge. Yet what we cannot perceive is sometimes a source of concern. In relation to the offence, the invisible refers to the point of view of the judicial authority, since it is in its eyes that the offence must exist for the penal machinery to be set in motion. The invisibility considered is thus objective. The term ''invisible'' is not commonly used in criminal law, not least because it seems foreign to the principles that underpin it. Yet, on closer inspection, the invisible often proves to be an obstacle to repression. Repression is thus obstructed by a technical, scientific or circumstantial incapacity. While the term may at first glance be reminiscent of certain notions already familiar in criminal law, the use of the notion ''invisible'' has the advantage of covering a wider field of study, taking a more global view of the offence, so as not to omit any of the difficulties that the absence of visibility can cause for repression. Surprising at first glance, the link between invisibility and crime is more obvious than it seems. The offence, in all its aspects, both as an act (studied macrocosmically) and as an incrimination (studied microcosmically), can be subject to the paralyzing irruption of the invisible phenomenon. The macrocosmic study of offences as acts points to the existence of offences that are invisible to the judicial authorities. Offences can also be invisible in terms of their content. Studied from a microcosmic point of view, incrimination reveals the intellectual aspect of the offence as the obvious seat of this invisibility within the offence. As for the material aspect of the offence, which we would expect to be sheltered from the difficulties associated with the invisible, since it corresponds to the externalization of criminal thought, it also proves to be impacted by the invisible: developments in technology, dematerialization, harm on the psychic integrity of victims or the use of psychological means by the perpetrator are all opportunities for the invisible to hinder repression. The invisible thus hampers law enforcement in two ways: by preventing the detection of offences, since it makes them difficult to discover, and by hindering the examination of the constitution of the offence, through the notional and evidential difficulties it generates. Thus, this unsuspected obstacle to the application of criminal law is a major challenge that criminal law must frequently face. The invisible, this unspoken aspect of criminal law, sheds light on several areas of criminal law, imposing itself as a key to the interpretation of certain derogatory regimes or extensive judge’s interpretations, as a means of ensuring the effectiveness of criminal law when confronted with what remains elusive.
Keywords: Criminal law; Droit pénal; Infraction; Infractions; Invisibility; Invisibilité; Offence

D'un cadre national à l'internationalisation du social des gens de mer : l'application du droit international du travail maritime en Afrique francophone de l'Ouest - Dia, Ibrahima Fedior (Nantes Université, 2023)
En Afrique francophone de l’Ouest, le droit social maritime positif est né dans une sphère nationale. Mais, la liberté internationale d’immatriculation des navires, l’internationalisation du transport maritime, l’engagement des gens de mer et l’intensification des rapports internationaux, ainsi que la prise de conscience de l’importance du facteur humain dans la prévention des risques maritimes étaient à l’origine d’un début de construction d’un droit international du travail maritime dans les années 1970. Ainsi, l’OMI et l’OIT ont développé un certain nombre d’instruments destinés à définir des règles en matière de sécurité maritime et de travail maritime. Toutefois, la réglementation de la profession de marin dans la sphère internationale a connu son plein essor avec l’adoption de la MLC et puis de la C188. La réglementation internationale est devenue la source essentielle de ce marché international du travail. Mais, la législation maritime ouest africaine ne prend pas en compte toutes les dimensions des conventions internationales, malgré une ratification massive de la MLC et une ratification limitée de la C188 en Afrique de l’Ouest. Or, la volonté exprimée de se mettre en conformité avec le droit international afin d’assurer aux gens de mer des conditions de travail décentes et sures doit être accompagnée d’actes concrets allant dans le sens d’une mise en conformité effective. Ceci passe par l’adoption de normes nationales conformes au droit international. Mais aussi, par des efforts d’encadrements et de contrôles, quitte à songer à une collaboration inter-régionale sur la plan normatif et institutionnel
Keywords: Afrique de l'Ouest; Afrique francophone; Conventions internationales; Droit international privé; Droit maritime; International Conventions; Marin; Relations extérieures; Seafarers; West Africa

Le particularisme de la répression pénale de la fraude fiscale - Cocly, Camille (Université de Saint-Etienne, 2023)
Le particularisme de la répression pénale de la fraude fiscale ressort de l’agrégation d’une pléthore de particularismes générés par la mise en œuvre d’un dispositif singulier de déclenchement des poursuites pénales. Le pouvoir discrétionnaire de l’administration fiscale de mettre en œuvre le dispositif de déclenchement des poursuites pénales pour fraude fiscale, plus connu sous l’appellation de verrou de Bercy, aura des répercussions sur toutes les étapes de la procédure pénale à l’instar d’un effet papillon. L’administration fiscale est en mesure de mettre en œuvre trois types de procédures administratives en cas de fraude fiscale : une procédure de recherche, une procédure de sanction et une procédure de recouvrement. Par conséquent, le recours à la répression pénale n’intervient qu’à titre subsidiaire afin de garantir le succès des procédures fiscales. Dans le cadre de la répression pénale de la fraude fiscale, dès lors que seule l’administration fiscale est en mesure de déclencher des poursuites pénales, la mise en œuvre du droit de punir est décidée par cette autorité administrative qui n’est pas indépendante car subordonnée au pouvoir exécutif en la personne du ministre du Budget. En conséquence, la répression pénale se retrouve détournée de son objectif primordial de rétribution afin de servir les impératifs budgétaires de l’administration fiscale dictés par le pouvoir exécutif. Outre un tel détournement, cette répression pénale sera exercée de façon inégalitaire puisqu’elle ne sera amenée à punir que les justiciables qui n’auront pas conclu une transaction avec l’administration. Le verrou de Bercy, en tant que pouvoir de faire obstacle à la répression pénale, s’il permet à l’administration de recouvrer l’impôt par transaction, il lui permet également de protéger les proches du pouvoir exécutif de poursuites pénales pour fraude fiscale. Le particularisme de la répression pénale de la fraude fiscale se nourrit de la réaction du législateur et de l’autorité judiciaire face à l’immoralisme qui s’évince du pouvoir de l’administration de permettre la mise en mouvement de l’action publique. En ce qui concerne le législateur, il va prendre un ensemble de mesures pour moraliser la vie politique, dont l’objectif est d’assurer la transparence sur les patrimoines des membres du pouvoir exécutif et des responsables politiques, de sanctionner plus sévèrement la fraude fiscale en renforçant la répression pénale de cette infraction. S’agissant de l’autorité judiciaire, si l’on peut remarquer une certaine détermination des autorités de poursuites à mettre en mouvement l’action publique lorsqu’elles sont saisies par l’administration fiscale, il convient de remarquer pareillement une certaine opiniâtreté du juge pénal à prononcer des condamnations pour fraude fiscale. D’autre part, les autorités de poursuites sont en mesure de s’affranchir des exigences procédurales du verrou de Bercy afin de poursuivre la fraude fiscale sous les qualifications de droit commun d’escroquerie et de blanchiment. Cependant, le constat de la faiblesse des peines d’emprisonnement prononcées ainsi que les possibilités d’aménagement de leur exécution soulèvent le curieux paradoxe d’une justice déterminée à condamner la fraude fiscale sans pour autant faire subir au fraudeur la violence légitime qu’il mérite. On peut se poser la question de savoir si une telle démarche moraliste de l’autorité judiciaire ne contribue pas à garantir le paiement de la dette fiscale. Cette réflexion est corroborée par l’avènement de la justice pénale négociée pour fraude fiscale, cadre dans lequel l’autorité judiciaire, à l’instar de l’administration fiscale, instrumentalise la répression pénale afin de recouvrer l’impôt.
Keywords: Bercy; Criminal-fiscal; Dispositions pénales; Droit; Droit fiscal; Fraud; Fraude; Fraude fiscale; Impôts; Instrumentalisation; Instrumentalization; Law; Lawsuits; Lock; Poursuites; Poursuites judiciaires; Pénal-fiscal; Taxes; Verrou

La fin de la fiscalité locale - Nazon, Romaric (Université de Montpellier, 2023)
Les impôts locaux avec pouvoir fiscal pour les collectivités territoriales sont progressivement démantelés par des allègements fiscaux de l'État qui aboutissent à la suppression de ces impôts. Le financement de la décentralisation dépend dès lors de plus en plus du partage de recettes fiscales nationales. L'impossible autonomie fiscale locale pousse à repenser les relations fiscales complexes entre l'État et les collectivités. La recréation d'un pouvoir fiscal local passerait par la concertation et la codécision entre l'État et les collectivités locales mais aussi, notamment, avec la crise de la démocratie représentative, entre des élus locaux et des citoyens. Cependant, la verticalité caractérise aujourd'hui les relations entre ces acteurs.
Keywords: Collectivités locales; Collectivités territoriales; Decentralization; Décentralisation; Décentralisation administrative; Finances publiques locales; Fiscalité locale; Impôt local; Local public finance; Local tax system; Territorial collectivities

L'après-franchise (?)... Le contrat de partenariat : nouveau modèle de contrat de distribution - Descazaux, Marcel-Philippe (Université de Montpellier, 2023)
L'après franchise (?)... le contrat de partenariat... nouveau modèle de contrat de distributionLes réseaux de franchise et le contrat qui les sous-tend sont aujourd'hui incontournables. Toutefois, le monde et le commerce sont en constante évolution. À tel point, que d'aucuns parlent d'une « crise » de la franchise. De nouveaux enjeux juridiques ont-ils vus le jour ? La maturité des réseaux actuels de franchise, le développement des concepts de commerce équitable, d'économie solidaire et le mode de fonctionnement des nouvelles générations tendent-ils vers un nouveau modèle contractuel plus horizontal ? A la marge des contrats de distribution en réseau « traditionnels », le contrat dit « de partenariat » occuperait aujourd'hui une place en progression constante, en prétendant répondre aux problématiques ci-dessus. Les observateurs relèvent, dans le même temps, que ce système de distribution en réseau semble peiner à s'affirmer et à être reconnu, notamment dans son cadre juridique. Le temps semble venu de vérifier si le contrat de partenariat n'est qu'une variante des autres modèles de contrats de distribution, notamment celui d'une franchise devenue éthique, ou bien s'il est un système spécifique et autonome de distribution. Constatant l'autonomie, cette thèse ambitionne de modéliser et de qualifier juridiquement le contrat de partenariat, en proposant des solutions novatrices aux freins avérés, afin de participer à son avènement.
Keywords: Chartes; Circuits de distribution; Collective interest; Contrat de partenariat; Distribution networks; Franchise; Franchising; Intérêt collectif; Know-How; Partenariat public-privé; Partnership agreement; Partnership-Knowledge; Réseaux de distribution; Savoir-Faire; Savoir-Partenarial

Le droit à la preuve en droit du travail - Lhomond, Cindy (Université Lumière Lyon 2, 2023)
Consacré en 2012 par la première chambre civile, puis en 2016 par la chambre sociale, un « droit à la preuve » voit le jour dans la jurisprudence de la Cour de cassation. Le droit à la preuve tend à préserver la recevabilité en justice d’un élément de preuve illicite produit spontanément ou demandé au juge. Le droit à la preuve, en tant que droit subjectif processuel, doit être concilié avec d’autres droits par l’intermédiaire du contrôle de proportionnalité. Le droit à la preuve est tributaire de la mise en œuvre du raisonnement de proportionnalité. Ces façons de concevoir et de mobiliser le droit à la preuve ont alors des conséquences en droit de la preuve, particulièrement en droit du travail. Les particularités structurelles du droit du travail, en tant que branche du droit, attribuent au droit à la preuve une coloration particulière. La thèse se propose ainsi d’analyser le droit à la preuve dans tous ses aspects, des liens qu’il entretient avec d’autres notions jusqu’aux limites de sa portée. Par ailleurs, l’étude s’inscrit dans une démarche plus générale, permettant de contribuer à l’analyse des évolutions du droit de la preuve en droit du travail .
Keywords: Ability to prove; Aptitude à la preuve; Burden of proof; Business secrecy; Charge de la preuve; Conflict of rights; Conflits de droits; Contrôle de proportionnalité; Droit de la preuve; Droit du travail; Droit à la preuve; Employee's personal life; Evidence; Fair trial; Fairness of evidence; Investigative measures; Labour law; Law of evidence; Loyauté de la preuve; Mesures d’instruction; Preuve; Preuve (droit); Procès équitable; Proportionality control; Right of produce evidence; Secrecy of correspondence; Secret des affaires; Secret des correspondances; Vie personnelle du salarié

La responsabilisation : essai sur la transformation de la protection sociale - Bourdenx, Aurore (Université de Bordeaux, 2023)
La protection sociale est traversée par des mutations qui, plus que conjoncturelles, semblent répondre à un véritable mouvement de fond. Ce mouvement s'inscrit dans le droit avec l'apparition de formes de régulation nouvelles, réinterrogeant les possibles conciliations entre intérêt individuel et intérêt général, et l'adaptation des régimes juridiques des prestations : bonnes pratiques, convention d'objectifs et de gestion, tarification à l'activité, parcours de santé, projets personnalisés, contrats d’engagement etc. Ces mutations se traduisent notamment par une tendance à la responsabilisation des acteurs qui jouent un rôle dans l’attribution ou l’utilisation des prestations sociales. Elles nourrissent un débat sur le coût de la protection sociale et sur les moyens de le réduire, des interrogations sur la philosophie de notre système de protection sociale et sur sa pérennité, de même qu'un questionnement sur l’existence et le fondement d’un droit aux prestations sociales. L'ensemble de ces évolutions impose de repenser les catégories doctrinales permettant l'analyse du droit de la protection sociale. La responsabilisation, souvent convoquée dans le discours sur le droit de la protection sociale, semble pouvoir constituer une grille de lecture pertinente pour décrire ces évolutions. L’étude entreprend de rechercher les liens entre la notion de « responsabilisation » et d'autres concepts juridiques visant à saisir les rapports de la norme à l'action tels ceux d’incitation, de norme promotionnelle et d'objectif. Plus largement, le sujet invite à saisir l'irruption de formes de rationalité économique dans le droit de la protection sociale. A ce titre, il impose aussi de réfléchir à la façon dont les droits à la protection sociale, mettant en œuvre des droits fondamentaux, peuvent prospérer sous contrainte de responsabilisation.
Keywords: Accountability; Aide sociale; Empowerment; Fonction du droit; France; Gouvernance; Governance; Responsabilité; Sécurité sociale

Les nullités en procédure pénale - Trifkovic, Stefan (Aix-Marseille Université, 2023)
Le régime juridique et la théorie des nullités en procédure pénale souffrent d’insuffisances. Il en résulte des difficultés de qualification et de prononcé des nullités qu’il est indispensable de résoudre. La méthode d’évaluation de la protection des intérêts en concours permet de qualifier toute nullité de manière optimale et opératoire. Le grief ne constitue qu’un critère complémentaire et facultatif dans le cadre de cette opération. Lorsqu’une disposition procédurale protège de manière exclusive ou prévalente l’intérêt général ou un intérêt privé, la qualification de la nullité empruntera le nom de l’intérêt ainsi protégé. Lorsque la disposition protège de manière équivalente les deux intérêts, la qualification adéquate est la nullité d’intérêt général par primauté. Cette méthode révèle aussi que la nullité d’intérêt privé peut parfois être retenue par subsidiarité, alors que la nullité d’intérêt général s’impose a priori. La stabilisation de la qualification par la méthode proposée permet de réhabiliter les nullités d’intérêt général et de catégoriser les nullités d’intérêt privé. Le prononcé des nullités s’articule quant à lui autour de la nécessité. Celle-ci procède du grief qui est prédominant pour la contestation en nullité et qui constitue la condition nécessaire du prononcé de toute nullité d’acte irrégulier, quelle que soit sa nature. La nullité subséquente repose en revanche sur une logique objective. La nécessité de son prononcé procède du lien procédural qui unit l’acte support et l’acte subséquent considéré. Seule l’appréciation rigoureuse de la consistance de ce lien à travers la notion de support déterminant rendrait satisfaisante la nullité subséquente
Keywords: Actes juridiques (annulation); Intérêt général; Intérêts privés; Nullité; Nullité (droit); Nécessité; Procédure pénale; Qualification; Sanction

La contribution de l'Union européenne à l'instauration d'un État de droit en République démocratique du Congo - Luabeya, Pacifique Hippolyte (Université de Lille, 2023)
L'UE est un acteur essentiel dans le processus de la construction et de la pérennisation de l’État de droit en République Démocratique du Congo (RDC). Son action extérieure dirigée vers cet État tiers prend plusieurs formes et se déploie sur des secteurs diversifiés. Le caractère protéiforme de l’action extérieure de l’Union se justifie notamment par les différentes réalités que traduit l’État de droit, un concept fourre-tout. Tantôt l’État de droit renvoie à l’idée de paix, tantôt à l’idée de justice (justice étatique et justice transitionnelle), tantôt à l’idée de démocratie (élection) et des droits de l’homme. L’UE mobilise pour chaque action menée au Congo-Kinshasa un instrument juridique adopté dans le cadre d’une stratégie juridique extérieure qui vacille entre la normativité souple et la normativité imposée. Ceci confirme que l’affirmation de l’Union, en tant qu’acteur international, passe aussi par le droit, et, plus précisément, par les projections de son droit sur la scène internationale et par sa soumission au droit international public. A partir de l’exemple des relations UE-RDC, il est possible d’envisager des perspectives intéressantes de mise en place d’une boîte à outils des actions de l’UE exportables vers d’autres États tiers, membres de l’OEACP (ex-ACP). The EU is a key player in the process of building and sustaining the rule of law in the Democratic Republic of Congo (DRC). Its external action directed towards this third State takes several forms, and has been deployed in diversified sectors. The protean nature of the Union's external action is justified in particular by the different realities reflected in the rule of law, a catch-all concept. Sometimes the rule of law refers to the idea of peace, sometimes to the idea of justice (state justice and transitional justice), sometimes to the idea of democracy (election) and human rights protection. The EU uses for every action carried out in Congo-Kinshasa a legal instrument adopted within the framework of an external legal strategy which wavers between flexible normativity and imposed normativity. This confirms that the affirmation of the Union, as an international actor, also depends on the law, and, more precisely, on the projections of its law on the international arena and its conformity to public international law. From the EU-DRC relationship model, it is possible to envisage interesting prospects for setting up a toolbox of EU actions that can be exported to other third countries, members of the OACPS (formerly ACP).
Keywords: Accord ACP-UE de Cotonou; Congo (République démocratique); Droit; Droit international; Droits de l'Homme; Démocratie; Justice transitionnelle; MONUC; MONUSCO; Maintien de la paix; Politique étrangère et de sécurité commune; Primauté du droit; Relations extérieures; Rule of law; Sanctions (droit international); Sanctions ciblées; State of peace; Targeted sanctions; Transitional justice; Union européenne; État de droit; État de paix

Reserva e alienação em garantia no direito da OHADA - Sampa, Samora Ilídio Delgado (Universidade de Lisboa, 2023)
O presente estudo aborda o tema da alienação fiduciária em garantia no âmbito da OHADA e do Direito positivo da Guiné-Bissau. A alienação fiduciária tem vindo a assumir uma importância decisiva no comércio jurídico internacional e no mercado de alta finança. A alienação fiduciária em garantia é um instituto com raízes no Direito Romano “fiducia cum creditore”. A evolução histórica da fidúcia revela que o instituto tem tendência para reaparecer nos momentos em que o Direito positivo se mostra inadequado para acompanhar novas necessidades sociais e económicas, nomeadamente a procura de garantias com a facilidade de constituição e execução. Actualmente, os negócios fiduciários têm raízes sólidas nos Direitos Civis de base romanística e continuam a influenciar o Direito Europeu e todos os Direitos que nele se inspiram, nomeadamente a OHADA, que instituiu, em 2010, a figura da alienação em garantia, em especial, cessão de crédito em garantia e alienação fiduciária de dinheiro em garantia. Um dos desafios das garantias fiduciárias instituídas pela OHADA é a falta da sua articulação saudável com os institutos fundamentais do Direito Civil, porque o novel Acto Uniforme não contém um regime fiduciário em geral e existem outros aspectos que suscitam dúvidas e carecem de aperfeiçoamentos. Todavia, o regime da alienação em garantia instituído pela OHADA revela, de um modo geral, ser favorável ao credor, facto manifesto ao nível dos mecanismos da execução da garantia, pois permite ao credor recorrer aos meios tradicionais da execução da garantia - via judicial – assim como a execução por via convencional ou através do pacto marciano - obrigando sempre ao credor à restituir a diferença na execução da garantia. Cette étude aborde le thème de l’aliénation fiduciaire en garantie dans le cadre de l'OHADA et du droit positif dans la Guinée - Bissau. L’aliénation fiduciaire a joué un rôle décisif dans le commerce juridique international et sur le marché de la haute finance. L’aliénation fiduciaire en garantie c`est un institut aux racines du Droit Romain «fiducia cum creditore». L’évolution historique de la fiducie montre que l’institut a tendance à réapparaître à des moments où le Droit positif est insuffisant pour faire face aux nouveaux besoins sociaux et économiques, à savoir la recherche de garanties avec la facilité de constitution et de réalisation. Actuellement, les contractes fiduciaires ont des racines solides dans les droits civils fondés sur le Droit Romain et continuent d’influencer le Droit européen et tous les droits sur lesquels elle s’appuie, à savoir l’OHADA, qui a établi en 2010 la fiducie – sûreté, en particulier la cession de créances en garanties, la réserve de propriété et la cession fiduciaire de la somme monétaire en garanties. Un des défis des garanties fiduciaires instituées par l’OHADA est l’absence de son articulation saine avec les instituts fondamentaux de Droit Civil, car le nouvel acte uniforme ne contient pas de régime général de la fiducie et il y a d’autres aspects qui soulèvent des doutes et manque des enquêtes et de l’approfondissement. Cependant, le régime de la fiducie – sûretés établi par OHADA est d’une façon générale, favorable au créancier, ce qui est confirmé au niveau des mécanismes d’exécution de la garantie, car ils permettent au créancier d’utiliser les moyens traditionnels d’exécution de la garantie - judiciairement - ainsi que l’exécution par convention ou par le biais du pacte martien - obligeant toujours le créancier à rétablir la différence dans l’exécution de la garantie.
Keywords: Alienação; Aliénation; Fiduciaire; Fiduciária; Garantia das obrigações; Garantie d’obligations; OHADA

La fraude à la loi en droit fiscal - Bach, Laurène (Université de Bordeaux, 2023)
Face aux crises et aux scandales financiers des dernières années, les préoccupations budgétaires des États ont évolué. En marge de la lutte contre la double imposition, il est apparu nécessaire de lutter contre les stratégies fiscales frauduleuses pour préserver la base imposable des États. D’abord reconnue par la jurisprudence européenne et française, la lutte contre la fraude à la loi s’est intensifiée avec l’ambitieux projet BEPS de l’OCDE. Les diverses initiatives se sont concrétisées par l’adoption de la directive « ATAD », la signature d’un instrument multilatéral reprenant les actions du projet BEPS ou encore l’instauration d’une nouvelle procédure d’abus de droit en droit interne. Il en a résulté une multiplication des moyens de lutte contre la fraude à la loi.Alors que la démarche poursuivie par les États était celle de la convergence au service de la lutte contre la fraude à la loi, l’intégration de nouveaux fondements en droit interne et les divergences rédactionnelles présentes au sein de ces fondements ont entraîné une fragmentation apparente de la notion de fraude à la loi, ainsi que des interrogations sur l’articulation des différents fondements désormais applicables.Toutefois, en comparant et en analysant le sens de chacun des termes employés dans les différents fondements, une définition unifiée de la fraude à la loi peut être retenue autour de deux critères : une volonté déterminante d’obtenir un avantage fiscal et le détournement de l’intention des auteurs des textes. Par ailleurs, une première grille d’articulation peut être développée à partir de critères d’articulation issus des éléments distinctifs des fondements de lutte contre la fraude à la loi. Cette dernière devra ensuite être confirmée par les différentes instances ainsi que la jurisprudence tant interne, qu’européenne.
Keywords: Abus de droit; Anti-abuse clause; Articulation; Clause anti-abus; Droit fiscal; Fraude; Fraude à la loi; Montage; Substance; Tax avoidance; Tax law evasion; Tax planning

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Contribution à l'amélioration du cadre juridique du processus de passation des marchés publics au Cameroun - Dicka, John Eric (Université Paris-Saclay, 2023)
Un des maux endémiques de certains pays africains est la faiblesse du dispositif législatif et réglementaire de l'achat public, face aux nombreux et variés défis de développement et de satisfaction de l'intérêt général. Partout dans le monde, la gestion de la commande publique est sujette à des dérives (corruption, détournements de deniers publics, sous-consommation des crédits publics, favoritisme, collusion, etc.), tant les enjeux sont majeurs pour l'État, les entreprises, et l'économie. Mais le rôle de l'achat public réduit à l'assainissement de la dépense publique progresse et épouse de plus en plus la sphère de la gouvernance et d'autres missions d'intérêt général ; Si dans ce secteur sensible, certains États réussissent mieux que d'autres à calibrer et concilier ces objectifs, cela tient en grande partie à leur appareil légal et réglementaire et à la capacité des administrations comme des juridictions à l'appliquer. Ainsi ce sujet, quoique centré sur le droit camerounais, traite d'une problématique bien plus large qui concerne plusieurs États et dont les analyses comparatives faites dans ce travail avec d'autres systèmes proches, justifient un lien commun et profond.À partir du contexte d'application et des faiblesses Recensées du cadre normatif camerounais au niveau de la phase de conclusion de l'achat public, il s'agit d'étayer un constat : le droit camerounais des marchés publics ne semble pas permettre que les marchés publics soient conclus en garantissant à l'administration une certaine efficacité d'action dans l'atteinte de ses objectifs variés.Si ce constat aura pour effet d'identifier ces principaux enjeux, il doit se servir d'une analyse sérieuse de la politique et de l'idéologie des marchés au Cameroun que révèle avec force le processus de passation, afin de déboucher sur des moyens conséquents devant assurer aux textes leur capacité à concilier les fonctions initiales des marchés publics avec celles qui semblent de plus en plus émerger ces derniers temps ; le tout, en conférant aux textes des garanties d'effectivité dans ce sens.L'exemple (ou le contre-exemple ?) du Cameroun doit permettre de mettre en lumière des phénomènes très répandus à travers le monde, à savoir l'ineffectivité d'un dispositif légal et réglementaire et bien plus l'inadéquation normative par rapport aux objectifs d'intérêt général inhérents à l'action publique. L'étude ne tend donc pas seulement au constat statique d'une situation insatisfaisante et dommageable pour le pays, bien plus il vise une analyse valable par-delà les frontières du Cameroun : un droit positif aux multiples finalités - à mettre en lumière -, dont l'impact est insuffisant sur la pratique, et une proposition d'outils juridiques et de management public pour y remédier.
Keywords: Afrique centrale; Approvisionnement public; Cadre juridique; Cameroon; Cameroun; Contribution; Intégration économique; Legal framework; Marchés publics; Marchés publics (droit); Passation; Process; Processus; Public contracts; Public procurement

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

O processo de constitucionalização dos estados africanos de expressão portuguesa: caminho para um pluralismo jurídico de procedimento - Roda, Arménio Alberto Rodrigues da (Universidade Federal da Bahia, 2023)
Os Estado africanos gozam de uma peculiaridade de possuírem caraterísticas culturalmente heterogêneas, o que acaba tendo um reflexo direto na composição das ordens normativas, as quais compreendem a mesma estrutura híbrida. Com o processo colonial, foram introduzidas na África famílias jurídicas do common Law e civil Law, que foram mantidas no período pós independência, resultando, desse modo, num conflito intersistêmico entre o direito estatal positivista e os direitos africanos – e, em alguns Estados, direito islâmico (Sharia). Diante dessa relação truculenta, a presente pesquisa propõe, em primeiro lugar, o reconhecimento do pluralismo jurídico procedimental e processual, de forma a amenizar esse conflito entre ambas as ordens, no qual o direito positivo arroga-se hegemônico e monista, limitando as manifestações dos direitos consuetudinários. Frisa-se de antemão que essa pesquisa se cinge especialmente aos países africanos de expressão portuguesa, dos quais a Constituição jurídica reconhece formalmente o pluralismo jurídico, todavia na perspectiva meramente substantiva, ou seja, sem métodos claros para efetivação do pluralismo jurídico, seja no âmbito institucional ou na dimensão processual, capaz de integrar os tribunais comunitários e as autoridades tradicionais num ambiente funcionalmente dialógico e plural. Ademais, a pesquisa buscou analisar a forma de funcionamento dos tribunais comunitários que exprimem a manifestação concreta do pluralismo jurídico, tendo sido analisados países como Moçambique, Cabo Verde, Guiné-Bissau e, de forma módica, Angola. Foram descritas as vantagens dos tribunais comunitários para o acesso à justiça e as suas limitações inerentes a certos direitos e certas garantias fundamentais que correm risco de serem violados, como o devido processo, negação da igualdade formal das mulheres e direitos das crianças. Para tal, foi proposta a possibilidade de fiscalização desses tribunais e participação de juízes profissionais em casos de grande magnitude. Sem embargos, cabe mencionar que foi trazida à discussão o paradigma pós positivista como um mecanismo de superação do positivismo puro, admitindo uma correção do direito pela moral, no sentido proposto por Robert Alexy (2009) e com nuances argumentativas compatíveis com a realidade africana, apresentado no terceiro capítulo em que se discuti a questão da crise do positivismo no continente africano. Frisa-se também que foi agregado a esse trabalho uma argumentação voltada à possibilidade de constitucionalização de Ubuntu como um princípio constitucional, parte dos direitos africanos, constituindo um mecanismo de incorporação e codificação plural dos valores africanos nos leques das normas estatais. Além do que já foi dito, foi analisada a questão ligada à efetividade dos direitos fundamentais, sobretudo os direitos das mulheres, tendo enaltecido a viabilidade de um constitucionalismo feminista, que pugna pela justiça de gênero na África, especialmente nas questões concernentes aos direitos reprodutivos e ao acesso às mesmas oportunidades. Por fim, descreveu-se o modelo das cortes constitucionais e o seu papel para a garantia e promoção dos direitos fundamentais. African states have the peculiarity of having culturally heterogeneous characteristics, which ends up having a direct impact on the composition of their legais systems, which comprise the same hybrid structure. With the colonial process, common law and civil law legal families were introduced in Africa, which were maintained in the post-independence period, thus resulting in an intersystemic conflict between positivist state law and African rights - and, in some states, Islamic law (Sharia). Faced with this truculent relationship, this research proposes, firstly, recognising procedural and procedural legal pluralism, in order to ease this conflict between the two orders, in which positive law claims to be hegemonic and monistic, limiting the manifestations of customary rights. It should be noted beforehand that this research is particularly focused on Portuguese-speaking African countries, whose legal constitution formally recognises legal pluralism, but from a purely substantive perspective, i.e. without clear methods for making legal pluralism effective, either in the institutional sphere or in the procedural dimension, capable of integrating community courts and traditional authorities in a functionally dialogical and plural environment. In addition, the research sought to analyse the way in which community courts that express the concrete manifestation of legal pluralism operate, having analysed countries such as Mozambique, Cape Verde, Guinea-Bissau and, in a modest way, Angola. The advantages of community courts for access to justice were described, as well as their inherent limitations with regard to certain fundamental rights and guarantees that are at risk of being violated, such as due process, denial of formal equality for women and children's rights. To this end, the possibility of supervising these courts and involving professional judges in cases of great magnitude was proposed. It is worth mentioning that the post-positivist paradigm was brought into the discussion as a mechanism for overcoming pure positivism, admitting a correction of the law by morality, in the sense proposed by Robert Alexy (2009) and with argumentative nuances compatible with the African reality, presented in the third chapter in which the issue of the crisis of positivism on the African continent is discussed. It should also be noted that this work includes an argument for the possibility of constitutionalising Ubuntu as a constitutional principle, part of African rights, constituting a mechanism for the incorporation and plural codification of African values into state norms. In addition to what has already been said, the issue of the effectiveness of fundamental rights, especially women's rights, was analysed, highlighting the viability of a feminist constitutionalism that strives for gender justice in Africa, especially on issues concerning reproductive rights and access to the same opportunities. Finally, the model of constitutional courts and their role in guaranteeing and promoting fundamental rights were described.
Keywords: Community courts; Constitucionalismo - África; Direitos humanos; Human rights; Justiça tradicional; O processo histórico do constitucionalismo africano; Pluralismo jurídico; Pluralismo jurídico procedimental; Procedural legal pluralism; Traditional justice; Tribunais comunitários

Droit à l'eau et partenariats internationaux : réflexions aux confluences des droits de l'homme et du droit international économique - Meireles, Gustavo Fernandes (Université Paris-Saclay, 2023)
L'eau représente un besoin vital pour l'homme. Sous l'effet du changement climatique et en raison de sa mauvaise utilisation, sa disponibilité pour l'utilisation humaine est gravement menacée. En outre, mobiliser les moyens techniques pour en assurer l'accès est coûteux. En conséquence, l'accès à l'eau constitue un enjeu largement investi par les programmes de développement mis en avant par les institutions internationales, à l'instar des Objectifs du Millénaire définis en 2000 et des Objectifs de développement durable de 2015. Les partenariats y sont proposés comme des moyens adaptés pour pallier les déficits d'infrastructures, notamment dans des États en développement. Solution particulièrement encouragée par la Banque mondiale et d'autres institutions financières internationales, la participation privée par le biais de partenariats internationaux est prônée comme une solution de nature à associer les entités publiques généralement chargées des services de l'eau et de l'assainissement avec les entreprises du secteur ayant un savoir-faire reconnu en vue de développer l'accès à l'eau potable. Alors que les partenariats internationaux ont joué un rôle de premier plan dans l'agenda de développement pour favoriser l'accès à l'eau, sont-ils des instruments adaptés pour réaliser le droit à l'eau ? Le droit à l'eau n'a été reconnu que de manière progressive dans le système onusien de protection des droits de l'homme. L'étude met en perspective l'originalité des partenariats internationaux dans le secteur de l'eau et souligne la difficulté à les inscrire dans le cadre normatif qui s'impose pour la réalisation du droit à l'eau. Les partenariats internationaux constituent des ensembles complexes d'instruments juridiques mis en place pour l'accès à l'eau. Malgré des avancées récentes en faveur de la consolidation de la responsabilité des entreprises en matière de de droits de l'homme, la pratique témoigne de ce qu'ils sont insuffisants pour mettre en œuvre pleinement le droit à l'eau.
Keywords: Accès à l'eau; Droit à l'eau; Droit à l'eau (droit international); Droits de l'homme; Développement; Développement durable; Partenariats internationaux; Personnes morales (responsabilité); Responsabilité des entreprises

Le contrat administratif à l'épreuve du droit des entreprises en difficulté - Lacarrère, Florent (Université de Pau et des Pays de l'Adour, 2023)
Le droit administratif et le droit des entreprises en difficulté sont caractérisés par leur exorbitance par rapport au droit commun -civil ou commercial-, en particulier en matière contractuelle. Ainsi le droit des contrats administratifs admet, par définition, que l'Administration contractante puisse user de pouvoirs dérogatoires du droit commun, dans un objectif d'intérêt général ou pour préserver la continuité du service public. De même, le droit des entreprises en difficulté permet aux organes de la procédure collective de mettre en oeuvre des mesures contraignantes pour l'entreprise contractante en difficulté, y-compris contre la volonté de l'Administration. La nécessité de préserver l'activité économique d'une entreprise et les emplois qu'elle véhicule, comme l'objectif moins prioritaire de rétablir les droits des créanciers, peuvent conduire à une remise en cause des droits de tout cocontractant du débiteur, y-compris ceux de l'Administration elle-même. L'ouverture de la procédure collective à l'égard du cocontractant de l'Administration se traduit par la confrontation de logiques et principes antagonistes ; elle ouvre un champ d'incertitudes théoriques et pratiques considérables. L'objectif de la présente thèse est donc d'étudier ce conflit de double exorbitance, qui se manifeste spécifiquement lorsque, dans le cadre d'un contrat administratif, le cocontractant de l'Administration est placé en procédure de sauvegarde, de redressement ou de liquidation judiciaire. La rencontre du droit des entreprises en difficulté avec le droit des contrats administratif entraîne la marginalisation partielle des solutions de droit administratif avec notamment une forme de primauté des règles imposées par les organes de la procédure collective sur les facultés de l'Administration contractante. Il convient d'accepter les entorses aux solutions traditionnelles en droit administratif, inhérentes aux impératifs de préservation des emplois, de redressement économique et de paiement des créanciers de l'entreprise en difficulté, tout en dénonçant le manque de clarté, la complexité, voire même le déséquilibre qui se manifestent parfois dans le cadre de cette conciliation.
Keywords: Contrats administratifs; Droit public économique; Entreprises en difficulté; Entreprises en difficulté (droit); Insolvency proceedings; Marchés publics; Procédures collectives; Public contracts; Public procurement; Redressement et liquidation judiciaire

Les modes alternatifs de traitement des conflits familiaux : étude comparative des droits français et ivoirien - Ouattara, Tiégolo Fougniguéta (Université de Bordeaux, 2023)
La famille se fonde sur des liens qui ne sont pas nécessairement rompus par l'existence d'un conflit. De ce fait, la résolution des conflits familiaux nécessite l'usage de méthodes favorisant la restauration des relations familiale ou un vivre ensemble harmonieux entre les membres de la famille. Dans cette perspective, en droit français et ivoirien, les systèmes traditionnels de résolution des conflits familiaux étaient partagés entre la méthode amiable et la méthode judiciaire. En droit français, ce partage s'observe durant la période de l'Ancien régime et la période révolutionnaire. En droit ivoirien, cela s'observe durant la période coloniale. Cependant, dans ces deux ordres juridiques, dans le cadre légal, la méthode amiable a été reléguée au second plan au profit de la méthode judiciaire. Toutefois, ces dernières années, face au besoin de réduire la charge de travail du juge, d'apporter des solutions aux conflits dans des délais raisonnables et d'adapter la résolution des conflits à la conception sociale de la justice, se développent les modes alternatifs. Ceux-ci regroupent un ensemble de mécanismes ayant pour objet la résolution amiable des conflits. Le développement de ces modes varie d'un pays à l'autre. En France, ils font l'objet d'un développement accru. En Côte d'Ivoire leur développement est timide. Néanmoins, des méthodes similaires aux modes alternatifs sont utilisées par le justiciable ivoirien pour la résolution des conflits familiaux, mais dans un cadre informel. Eu égard à l'attachement du justiciable ivoirien à la justice informelle, aussi qualifiée de justice traditionnelle, se manifeste un besoin de sa reconnaissance légale. La justice traditionnelle ivoirienne étant par principe amiable tout comme les modes alternatifs, le développement de ces modes dans la législation familiale ivoirienne pourrait se faire dans le cadre d'une conciliation des règles les régissant avec celles régissant la justice traditionnelle ivoirienne. Mais cette conciliation devrait être faite en tenant compte des limites des modes alternatifs observées grâce à l'expérience française de ces mécanismes et des réalités sociales ivoiriennes. The family is founded on ties that are not necessarily broken by the existence of conflicts. Therefore, resolving family conflicts requires the use of methods that promote the restoration of family relationships or a harmonious living together among family members. In this regard, under French and Ivorian law, traditional systems for resolving family conflicts were divided between the amicable method and the judicial method. In French law, this division can be observed in the periods of the Old Regime and the Revolution. In Ivorian law, this can be observed during the colonial period. However, in both legal systems, the amicable method failed from a legal point of view in favor of the judicial method. This failure was due to the litigant and the legislator. However, in recent years, faced with the need to reduce the judge's workload, provide solutions to conflicts in reasonable timeframes, and adapt conflicts resolution to the social conception of justice, alternative methods of resolution are developed. These comprise a set of mechanisms aimed at amicably resolving conflicts. The development of these methods varies from one country to another. In France, they are subject to increased development. In Côte d'Ivoire, their development is modest. Nevertheless, similar methods to alternative modes are used by Ivorian litigants for the resolution of family conflicts, but in an informal setting. In view of the Ivorian litigants' attachment to informal justice due to the fact that it represents Ivorian traditional justice, there is a need for its legal recognition. Since Ivorian traditional justice is amicable by nature, just like alternative modes, the development of these methods in Ivorian family legislation could take place within the framework of a reconciliation of the rules governing them with those governing Ivorian traditional justice. However, this reconciliation should take into account the limitations of alternative modes observed through the French experience of these mechanisms and ivorian social realities.
Keywords: Alternative modes; Comparative law; Conflicts; Conflits; Côte d'Ivoire; Différends; Disputes; Droit; Droit comparé; Famille; Famille (droit); Family law; France; Justice traditionnelle; Litigation; Litiges; Modes alternatifs; Médiation familiale; Règlement de conflits; Traditional justice

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

La justice sociale dans le contrat international de travail : étude du conflit de lois en droit international privé tunisien et français - Tlili, Nahla (Université Paris 1, 2023)
L’inscription de la question de la justice sociale dans le cadre de la résolution du conflit des lois dans le contrat international de travail suscite des interrogations multiples quant à l’efficacité méthodologique et substantielle des mécanismes de droit international privé.En raison de ses insuffisances intrinsèques et extrinsèques, la réglementation conflictuelle n’incarne que relativement les principes fondamentaux d’une justice d’égalité et d’une justice de liberté. Leur développement dépend d’une révision des règles de conflit par une articulation du principe de proximité et du principe de l’autonomie de la volonté dans un sens de faveur. Toutefois, la démarche d’adaptation de la méthode conflictuelle pourrait avoir un sens plus dynamique et plus effectif en intégrant l’idéal de justice sociale dans sa dimension universelle recognitive et participative. Une exploitation des différents mécanismes de correction classiques et ceux renouvelés en droit international privé du travail est, à cet effet, indispensable. Elle traduit le besoin de garantir un minimum social universel intangible au seuil duquel seront freinés le dumping social et le forum shopping et au-delà duquel est impulsée la diversité législative. Tirant ses fondements des normes sociales de jus cogens, ce minimum social universel forme un ordre public social transnational dont la mise en œuvre favorise une diversification des formes de coordination des systèmes en droit international -privé. Il autorise, par-ailleurs, un ordonnancement du pluralisme normatif et une communication entre droit dur et droit souple dont les normes sociales de RSE constituent la principale expression. En véhiculant et concrétisant les principes d’ordre public social transnational, ces normes participent originalement, dans le contrat international du travail, à la transformation des solutions. Elles s’inscrivent, en conséquence, parfaitement dans ce contexte d’une justice sociale évolutive.
Keywords: Autonomie de la volonté; CSR; Communication between hard and soft law; Conflict of laws; Conflit de lois; Droit international privé; France; Interaction droit dur et droit souple; Justice d'égalité; Justice d'équité universelle et participative; Justice de liberté; Justice of fairness; Justice of freedom; Justice sociale; Ordre public social transnational; Principe de proximité; Principle of proximity; Principle of will; RSE; Responsabilité sociale des entreprises; Responsabilité sociétale; Transnational social public order; Tunisie

La subrogation en droit privé et public des obligations - Collet, Maëllys (Université Savoie Mont Blanc, 2023)
Notion complexe, la subrogation en droit privé et public des obligations se manifeste sous deux formes distinctes. La première dite réelle, permet le report d'un droit sur un bien nouveau, lorsqu'il ne peut plus porter sur le bien d'origine. La seconde dite personnelle aboutit au transfert de la créance au profit du solvens, lorsqu'il ne doit pas supporter, en tout ou partie, la charge définitive de la dette. Cette dualité conduit alors à dissimuler l'unité conceptuelle et fonctionnelle de la notion de subrogation. En tant qu'instrument de conservation d'un droit, la subrogation assure une fonction régulatrice. La survie du droit est assurée par son transfert d'un bien à un autre, d'une masse de bien à une autre, ou d'une personne à une autre. La subrogation permet alors de prévenir ou de corriger un déséquilibre patrimonial qui contredit l'équilibre préétabli par le législateur ou les parties. Ainsi entendue, la subrogation peut être appréhendée comme une notion générale, disposant d'un contenu juridique propre. La proximité entre son application en droit privé et en droit public est telle, que sa transversalité peut être consacrée. Des singularités restent consubstantielles aux différentes variétés de subrogations, puisque leurs régimes juridiques sont adaptés à leurs terrains d'intervention. Le manque d'harmonisation lié à l'instauration de régimes spéciaux, ou à l'existence de solutions distinctes entre les deux ordres juridiques, n'est pas toujours justifié, et fragilise l'unité de la notion. La subrogation reste un mécanisme hétérogène dont il ne faut pas négliger les spécificités.
Keywords: Circulation des créances; Circulation of claims; Créances; Droit privé; Droit public; Obligations (droit); Paiement; Payment; Private law; Public law; Recours subrogatoire; Subrogation; Subrogatory action

Arbitrabilidade objetiva em contratos administrativos - Cardoso, Paula Butti (Universidade de São Paulo, 2023)
A Lei n° 9.307, de 1996, a Lei de Arbitragem, com a redação que lhe foi dada pela Lei n° 13.129, de 2015, passou a prever expressamente que a Administração Pública direta e indireta poderá utilizar-se da arbitragem para dirimir conflitos relativos a direitos patrimoniais disponíveis. Ultrapassadas as discussões em torno da arbitrabilidade subjetiva, a arbitrabilidade objetiva das disputas envolvendo a administração pública ganha papel de destaque. Divergências a respeito do que seriam os direitos patrimoniais disponíveis da administração pública faz com que a questão seja frequentemente levada ao poder judiciário, em atentado a valores informadores da arbitragem, como a segurança jurídica e a celeridade. Daí a necessidade de se buscar solução para a questão, o que pode ser feito a partir do direito administrativo contemporâneo, que valoriza cada vez mais a atuação consensuada em detrimento da atuação unilateral e impositiva da administração pública. Law No. 9,307, of 1996, the Brazilian Arbitration Law, amended by Law No. 13,129, of 2015, expressly provides that the direct and indirect public administration may use arbitration to resolve conflicts relating to renounceable patrimonial rights. Discussions relating to arbitrability regarding the parties in arbitration have given place to discussions regarding subject-matter arbitrability relating to disputes involving public administration. Different understandings about the renounceable patrimonial rights of the public administration frequently take the discussion to be ruled by judiciary courts, jeopardizing values that inform arbitration, such as legal certainty and celerity. The current scenario demands that a solution to the issue is provided. That can be done based on modern administrative Brazilian law, which increasingly values consensual action rather than unilateral action by public administration.
Keywords: Administrative contract; Administrative law; Arbitrabilidade objetiva; Arbitrability; Arbitrage; Arbitragem; Arbitration; Consensualidade; Consensuality; Contrat administratif; Contrato administrativo; Direito administrativo; Droit administratif

Le droit de la preuve face aux techniques numériques - Depaepe, Thomas (Université Paris-Saclay, 2023)
Le droit de la preuve comprend l'ensemble des règles qui encadrent la preuve en justice, c'est-à-dire l'opération visant à faire reconnaître par un juge la véracité d'une allégation contestée. Si l'histoire du droit montre que l'existence de ce corpus est intemporelle, elle révèle aussi que son contenu a toujours été soumis à l'influence de divers facteurs et, en particulier, à celle du progrès technique. Aussi, quantité de modifications ont été apportées aux règles de preuve à partir des années 1970 en réaction à l'essor des techniques numériques dans la société. C'est à l'analyse de cette évolution que s'emploie la présente étude, en se bornant toutefois à celle qu'a connue la règlementation applicable au contentieux privé.Dans une première partie consacrée aux dispositions qui régissent généralement la preuve d'un acte juridique, il est démontré que les interventions législatives successivement entreprises depuis l'an 2000 pour assimiler le document numérique à une preuve littérale n'ont pas été une œuvre d'adaptation mais bien de subversion. Habituellement qualifié de « système de preuve légale », cet ensemble de textes situés pour l'essentiel dans le Code civil tendait encore à la fin des années 1990 à diriger la décision du juge appelé à se prononcer sur l'existence ou le contenu d'un acte juridique. Tel n'est plus le cas du système institué par le législateur sous la pression du fait numérique, dans le cadre duquel le magistrat a insidieusement été laissé libre d'admettre et d'apprécier tous les éléments de preuve produits par les plaideurs, c'est-à-dire de juger conformément à son intime conviction ou à l'idée qu'il se fait de l'équité. Partant, la protection de la sécurité juridique des parties et la prévention de l'engorgement des tribunaux ne peuvent plus être invoquées pour justifier le système organisé par le Code civil comme elles l'étaient antérieurement. L'utilité de maintenir ce système apparaît dès lors douteuse.Dans une seconde partie dédiée aux dispositions qui régissent ordinairement la preuve d'un fait juridique et que l'on a coutume d'appeler « système de preuve morale », il est démontré que la généralisation des procédés numériques a eu deux répercussions significatives. La première a consisté en un renforcement de l'exigence de licéité de la preuve inscrite dans le Code de procédure civile, dont l'édification de la législation « Informatiques et Libertés » à partir de 1978 constitue l'une des manifestations les plus emblématiques. La seconde répercussion, qu'un examen rapproché de la jurisprudence permet de mettre en lumière, a consisté en une relativisation de la faculté du juge à apprécier les pièces qui lui sont soumises en observant le devoir de motivation que lui impose le Code de procédure civile.En synthèse, l'étude révèle donc que le fait numérique a engendré une transformation profonde du droit de la preuve. Elle contribue ce faisant à nourrir la réflexion sur les relations qu'entretient l'ordre juridique avec le fait technique et, donc, sur les rapports du Droit au fait.
Keywords: Confiance numérique; Preuve (droit); Preuve électronique; Technique

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

La protection des savoirs traditionnels dans le secteur alimentaire - Vo, Nguyen Hoang Phuc (Université Lumière Lyon 2, 2023)
Les savoirs traditionnels dans le secteur alimentaire se comprennent comme le fruit d’une activité intellectuelle, d’expériences, de moyens spirituels ou d’idées, sous forme d’expressions verbales ou écrites, dans ou à partir d’un contexte traditionnel. Ils se présentent au cœur de presque toutes les activités, depuis la culture, l’élevage, la préparation et la préservation, jusqu’à la consommation des denrées alimentaires pour la destination de l’ingestion humaine, ainsi que leurs artefacts, c’est-à-dire les plats cuisinés et les produits alimentaires. Tandis qu’ils méritent d’être sauvegardés, à l’heure actuelle, ils ne font pas encore l’objet d’une protection appropriée et efficace.La thèse intitulée « La protection des savoirs traditionnels dans le secteur alimentaire » porte en premier lieu, sur la recherche d’un ou de plusieurs outils existants susceptibles d’être évoqués pour protéger les savoirs alimentaires, y compris la protection fondée sur la nature de l’objet de propriété et celle sur la nature culturelle des savoirs traditionnels dans le secteur alimentaire. Parmi les outils existants, on peut se tourner vers la propriété intellectuelle, les signes de l’origine et de la qualité, mais aussi d’autres droits plus particuliers, notamment issus des conventions internationales relatives aux droits culturels (première partie). En second lieu, partant de l’état des lieux relatif aux outils existants et du constat de leur insuffisance ou leur inaptitude à protéger de manière suffisante les savoirs alimentaires traditionnels, nous formulerons des propositions permettant d’améliorer la protection des savoirs alimentaires.
Keywords: AOP; Appellations d'origine; Droit culturel; IGP; Indication géographique; Indications géographiques protégées; Intellectual property; Patrimoine culturel immatériel; Produits du terroir; Propriedade intelectual; Propriété intellectuelle; STG; Savoirs alimentaires; Savoirs traditionnels

L'immobilier, une source de revenus captifs soumise à une fiscalité punitive, confirmant l'inconsistance du droit de propriété - Guenfici, Alexandre (Université de Perpignan, 2023)
Le point de gravité fixant mutuellement Nation et Citoyen est le sol. Sur ce sol est institué un droit, celui de la propriété foncière privée, un lien juridique primordial unissant Citoyen et Nation. Au cours de l'histoire ce point de fixation qu'est la propriété foncière devient également économique, l'État fondant une grande partie de ses recettes fiscales sur le propriétaire et son patrimoine immobilier. Dans une société moderne où la propriété est intriquée avec son rendement économique, cette propriété se mue en un placement économique subissant désormais une fiscalité punitive, voire confiscatoire. La fiscalité immobilière montre cette appropriation par l'État d'une grande partie des fruits de la propriété privée ; transformant cet objet en un simple droit d'occupation, voire un droit de garde, chargé d'obligations sans plus de droits réels. D’un droit réel à un droit personnel la fiscalité immobilière, par le jeu de l'impôt sur les revenus et de celui sur le patrimoine, transforme ce droit en une obligation fiscale. Dans cette relation nécessairement léonine entre propriétaire immobilier et État, ce dernier propose des régimes de faveur encourageant à investir dans l'immobilier. Ces incitations emprisonnent dans une relation de longue durée l'investisseur, puis l'investissement réalisé, l'État modifie en cours de relations les clauses de ces régimes à son plus grand profit. Or, le contribuable s'engageant dans cette relation n'est pas informé que ces règles peuvent changer d'une manière unilatérale, sans préavis et rétroactivement. Ce modus operandi est particulièrement illustré par la location meublée, la location para-hôtelière, l'impôt sur la fortune immobilière et la transmission de ces biens et activités via le pacte Dutreil. Ce dispositif Dutreil, donné comme un pacte, ne garantit aucune sécurité lors de son exécution ; d'autant que rédigé par une seule partie, le contribuable, l'autre, l'État, n'intervient qu'a posteriori pour éventuellement le remettre en cause
Keywords: Fiscal; Fiscalité; Fiscalité immobilière; Immobilière; Location; Propriété immobilière et impôt; Real estate; Rental; Transmission

Les clauses relatives à l'aménagement des sanctions de l'inexécution du contrat - Scemama, Dan (Université Paris-Saclay, 2023)
La présente étude s'attellera à examiner les clauses relatives à l'aménagement des sanctions de l'inexécution du contrat (la résolution, l'exécution forcée etc.). En effet, le pouvoir pour les contractants d'aménager ces sanctions contractuelles fait l'objet de nombreuses interrogations et difficultés. Ces dernières perdurent et sont ravivées depuis l'entrée en vigueur de l'ordonnance du 10 février 2016. Cette ordonnance est venue apporter des changements au sein du Code civil concernant les règles juridiques applicables aux sanctions contractuelles en cas d'inexécution, lesquels prolongent et étendent les travaux menés par la doctrine et la jurisprudence. L'enjeu de cette étude est alors de déterminer la marge de manœuvre dont disposent les parties en cas de stipulation de telles clauses et en particulier de déterminer leur validité et efficacité.
Keywords: Aménagement; Breach; Clause de sortie; Clauses; Clauses contractuelles; Clauses de non-responsabilité; Contract; Contrat; Contrats; Inexécution; Non-Performance; Résolution de contrat; Sanction

La transformation numérique de la profession d'avocat - Gorlier, Vincent (Université Paris 1, 2023)
La révolution numérique façonne sans discontinuité tous les secteurs de la vie économique et sociale y compris le marché du droit. En effet, Internet qui s'impose comme le premier média des technologies de l’information et de la communication remet en cause les moyens traditionnels de l'accès au droit. L'analyse des bouleversements du droit sur Internet permet de constater l'apparition de nouveaux comportements de plus en plus fragmentés, ce qui nécessite pour les juristes de maîtriser les nouvelles technologies autour de l'intelligence artificielle et des algorithmes prédictifs. Les professionnels du droit et particulièrement la profession d'avocat devront également analyser en profondeurs les mutations et les besoins du justiciable afin de rechercher des solutions adaptées face à la concurrence des nouveaux acteurs que l'on nomme legaltech et qui proposent des services juridiques innovants et disruptifs. Cette étude permet ainsi d’affiner les connaissances d'un marché devenu en quelques années de plus en plus interactifs qui invite les avocats à la fois à un décryptage technologique des enjeux d'Internet et à un cadrage des opportunités pour transformer les règles de l'innovation tout en respectant leur déontologie.
Keywords: ACCES AU DROIT; ACCESS TO LAW; Avocats; Digital; Internet; Lawyers; Legaltech; Numérique; Professions judiciaires et juridiques; Transformation

Les moyens de défense de l’employeur dans le contentieux des accidents du travail et maladies professionnelles - Gosselin, Léa (Nantes Université, 2023)
La législation applicable aux accidents du travail a été construite sur le fondement d’un compromis entre les intérêts des employeurs et des salariés. Le principe d’une responsabilité patronale automatique, en contrepartie d’une réparation forfaitaire, a ainsi été instauré par la loi du 9 avril 1898. Or, le contentieux des accidents du travail et des maladies professionnelles fait l’objet d’une vive actualité légale et jurisprudentielle. Cette actualité s’inscrit dans le contexte d’une préoccupation accrue pour les questions de santé au travail et d’une remise en cause du caractère forfaitaire de la réparation accordée aux victimes. La présente recherche consiste alors à s’intéresser à la situation juridique de l’employeur face aux différentes évolutions du droit des risques professionnels. Une restriction de ses moyens de défense peut, en effet, être observée. Ce constat innerve l’ensemble du contentieux. Cette orientation du droit positif conduit, par conséquent, à interroger les voies susceptibles de permettre un renouvellement de la défense patronale. Face à l’enfermement des moyens de défense de l’employeur, la recherche d’un nouvel équilibre guidé par la prévention semble s’amorcer. L’influence du droit du procès équitable sur la législation des accidents du travail et maladies professionnelles est également perceptible. Si des réponses semblent dès lors s’initier à l’aune de ces fondements, leur portée demeure cependant limitée. Certains obstacles opposés à la défense de l’employeur ne peuvent ainsi être dépassés en l’état actuel du contentieux des accidents du travail et maladies professionnelles.
Keywords: Accidents du travail; Droit du travail; Employeurs (responsabilité); Labour law; Maladies professionnelles; Occupational health; Professional diseases; Santé au travail; Work accidents

Blockchain et activité notariale : vers une remise en cause de l'authenticité ? - Loizon, Margaux (Université de Montpellier, 2023)
L'objectif au sein de cette thèse sera d'étudier l'impact de la Blockchain sur l'activité notariale et de manière plus générale sur le principe d'authenticité. En effet, il est important de se demander si la blockchain, une technologie anti-étatique prônant la désintermédiation ne va pas menacer le rôle du notaire en tant que tiers de confiance. Au delà, il sera également question de se demander si la blockchain ne remet pas en cause le principe d'authenticité et même la place du droit dans notre société actuelle.
Keywords: Actes authentiques; Authenticité; Blockchain; Notariat

L'unification des pratiques de médiation et de conciliation dans les pays membres de l'OHADA - Dah, Sègla Septime (Université de Toulon, 2023)
L’unification des pratiques de médiation et de conciliation s’inscrit dans une démarche centrée sur l’activité du médiateur ou du conciliateur et présente un intérêt double. D’une part, elle forge l’action du médiateur ou du conciliateur en répertoriant les critères afin d’instituer un référentiel qualité. Ce dernier servira à évaluer ses bonnes pratiques du médiateur ou du conciliateur. L’unification desdites pratiques n’entend pas instituer une bonne pratique de la médiation ou de la conciliation. Elle prône pour une identification desdites pratiques afin de constituer un socle commun à l’action et aux prestations de tous les médiateurs des pays membres de l’OHADA. D’autre part, elle est garante du droit à un médiateur compétent et de l’accès à un processus de résolution des conflits de qualité pour une médiation efficace. Le droit à un médiateur compétent et l’accès à un processus de résolution des conflits de qualité sont les deux composantes essentielles du recours effectif à la justice amiable en droit OHADA. Ce recours découle d’un droit de la médiation et de la conciliation qui est en codification dans les pays membres de l’OHADA. Ladite codification est un préalable à cette démarche d’unification. Ainsi, la construction du droit de la médiation et la conciliation doit être accompagnée d’une réelle politique d’unification des pratiques de médiation et de conciliation afin d’inscrire le recours à l’amiable dans l’habitude des justiciables.
Keywords: Amicable settlement; Appeals; Conciliation; Droit de l’amiable; Effectif; Effective; Efficace; Efficient; Evaluation; Justice; Justiciables; Litigants; MARD; Mediation; Médiation; Médiation internationale; Organisation pour l'harmonisation en Afrique du droit des affaires; Quality standards; Recours; Référentiel qualité; Unification; Évaluation

La transformation du Système de résolution des conflits entre État hôte et investisseur étranger : la conciliation des intérêts d’acteurs d’un système adaptatif complexe - Deligny Malchair, Marion (Université de Lorraine, 2023)
Les conflits entre État hôtes et investisseurs étrangers occupent, depuis une dizaine d’année le devant de la scène géopolitique. Le questionnement se porte aujourd’hui de façon globale sur l’articulation des méthodes de règlement de conflits particulièrement complexes en raison de leurs implications institutionnelles, juridiques et économiques. Cette thèse se consacre à appréhender le cadre de règlement des conflits d’investissements selon le modèle du système afin de déterminer les conditions nécessaires à la transformation profonde du Système de résolution des différends entre États-hôtes et investisseurs.L’analyse du Système de résolution des différends entre États-hôtes et investisseurs suppose d’abord d’en restituer le contexte historique et d’examiner les bases institutionnelles posées par le système CIRDI, celui-ci étant le fruit d’une idée, la substitution du droit à la force pour la résolution des différends d’investissement : « le paradigme juridictionnel ». Or, si des bases institutionnelles avaient été posées, celles relationnelles ne l’étaient pas. Il s’en suit un usage des mécanismes du Système de résolution des différends entre États-hôtes et investisseurs dans une logique défensive et adversariale. Cependant, la complexification croissante du monde et incidemment du système des investissements, conduit les acteurs de l’investissement à passer d’une logique adversariale à une logique de collaboration et de co-construction pour résoudre les inévitables problématiques auxquelles ils font face : « le paradigme consensuel ».Nous nous interrogeons alors sur les conditions nécessaires à la mise en œuvre de ce nouveau paradigme comme fondement du Système afin d’en provoquer la transformation profonde. L’application de concepts issus du champ d’étude de la complexité et des systèmes adaptatifs complexes permet de conclure que le consensualisme est tout à la fois le résultat et le moyen à mettre en œuvre pour faciliter cette transformation. Seule une démarche holistique, incluant l’ensemble des acteurs dans leur diversité, peut permettre de faire émerger des solutions innovantes à la hauteur des enjeux. Notre proposition est d’utiliser les outils et méthodes du Design Thinking appliqués au droit – le Legal Design- dont la démarche place les parties prenantes, et donc les éléments de culture et de contexte, au cœur du processus de conception de solutions, et susceptible de provoquer un changement dans la dynamique relationnelle des acteurs vers une logique de collaboration. Cette conclusion s’applique aux deux échelles retenues : celle de la transformation globale du Système de résolution des différends entre États-hôtes et investisseurs, et celle des projets d’investissement, dont une gouvernance participative doit être encouragée afin d’en permettre le succès et de permettre de réaliser une des vocations premières du système des investissements qu’est le développement des États d’accueil au bénéfice de leurs communautés. Conflicts between host states and foreign investors have been at the forefront of the geopolitical scene for the past ten years. Now the question is being raised on a global scale concerning the articulation of particularly complex conflict resolution methods because of their institutional, legal and economic implications. This thesis focuses on understanding the framework for resolving investment disputes based on the system model in order to determine which conditions are necessary for the profound transformation of the Dispute Resolution System between host states and investors.Before any analysis of the Dispute Resolution System between host states and investors can be undertaken, it is necessary to provide an insight into the historical context and to examine the institutional foundations of the ICSID system. These are the result of an idea, substituting international law to the use of force for the resolution of investment disputes: “the jurisdictional paradigm”. If institutional foundations were laid, relational ones were not. This resulted in the use of the Dispute Resolution System mechanisms between host states and investors in a defensive and adversarial logic. However, the increasing complexity of the world and, incidentally, of the investment system, has led investment players to move from an adversarial logic to one of collaboration and co-construction in order to resolve the inevitable problems they face: “the consensual paradigm”.We then question the conditions required for the implementation of this new paradigm as the foundation of the System in order to bring about its profound transformation. Applying concepts from the fields of study into complexity and complex adaptive systems leads to the conclusion that consensus constitutes both the outcome and the means to facilitate this transformation. Only a holistic approach, including all the actors involved and their diverse contexts, can make it possible to develop innovative solutions that meet these challenges. Our proposal is to apply Design Thinking tools and methods in a legal context – Legal Design. This approach places stakeholders, and therefore the elements of culture and context, at the heart of the process of designing solutions, and is therefore well suited to bringing about a change in the relational dynamics of the actors towards a logic of collaboration. This conclusion applies to both scales: that of the overall transformation of the Dispute Resolution System between host states and investors and that of investment projects, whose participative governance structure must be recognized as a crucial success factor and a means to support one of the primary purposes of the investment system, which is the development of host states for the benefit of their communities.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Complex Adaptive System; Dispute System Design; Droit international; Foreign investment; Investissements étrangers; Investment Conflits Resolution; Investment Mediation; Legal Design; MARD; Mediación; Mediation; Mediação; Médiation; Médiation d'investissement; Règlement de conflits; Résolution des conflits d'investissement; Système adaptatif complexe

Les contrats d'activité segmentée - Michel, Stéphane (Université Polytechnique Hauts-de-France, 2023)
L’étude porte sur les contrats qui prennent en compte le caractère discontinue de l’activité économique et professionnelle tout en permettant de maintenir, du moins potentiellement, la relation dans une optique de long terme. En d’autres termes, il ne s’agit d’étudier ni le CDI, ni le CDD ou le CTT, mais les catégories intermédiaires créées au fil du temps par le législateur souvent bien aidé par les partenaires sociaux ou la pratique. Il nous a paru que les contrats les plus représentatifs de ce nouveau genre sont le contrat de travail intermittent, le CDI intérimaire, le contrat de chantier, le portage salarial et le CDDU des intermittents du spectacle. Nous proposons de les qualifier de contrats (de travail) d’activité segmentée et notre propos est de voir s’il existe entre eux des lignes directrices, des lignes de force qui donnerait une cohérence à cette pléiade de contrats. Pour ce faire nous avons considéré que les contrats d’activité segmentée soulèvent deux questions principales : l’une d’identité, l’autre de temporalité. La première est simple à énoncer. Dans le cadre de certains contrats d’activité segmentée (le portage salarial, les intermittents du spectacle, le CDII), qui est qui et qui fait quoi ? Les réponses sont, en revanche, très mal aisées à apporter. En effet, tout d’abord la notion même d’employeur est ici difficile à cerner. Les fonctions de ce dernier sont fragmentées pour ne pas dire atomisées sous le coup des contrats étudiés. Les salariés endossent de nombreuses prérogatives dévolues normalement à l’employeur. Et ce dernier se contente souvent d’un travail que l’on pourrait qualifier d’administrateur-payeur. Les rôles joués par les uns et les autres sont flous. Et ce flou juridique est peut-être encore plus important lorsque l’on étudie lesdits contrats sous l’angle de la mise à disposition. Par ce biais, se pose irrémédiablement la question du coemploi (ou plus précisément de l’emploi conjoint), notion complexe qui pourrait permettre au salarié, notamment, de se voir reconnaitre deux employeurs. Néanmoins les contrats d’activité segmentée se cantonnent, sur le papier, à un unique employeur, sauf qu’il est possible de discuter du point de savoir si c’est l’entreprise signataire du contrat de travail ou l’entreprise utilisatrice qui doit être reconnue comme employeur. Plus encore, la situation de certains des travailleurs étudiés (salarié porté, intermittents du spectacle) pourrait relever de la catégorie des micro-entrepreneurs. La seconde question étudiée, celle de la temporalité, est apparue immédiatement, presque instinctivement. En effet, tous les contrats d’activité segmentée (les 5 retenus) contiennent obligatoirement des périodes travaillées et des périodes non travaillées. Ces dernières sont appelées intermissions (ou périodes interstitielles) et sont appréhendées de différentes manières par notre droit. Ainsi, le salarié est tantôt rémunéré par son employeur, tantôt pris en charge par un régime d’assurance chômage, tantôt exclu des deux mécanismes, sans que l’on puisse pour autant immédiatement dire lequel sera le mieux loti. Certes, le statut de l’intermittent du spectacle peut faire office d’étalon, mais le coût du système peut également faire peur. Les différentes formes de cessations des contrats d’activité segmentée (ruptures, non renouvellements) ont enfin été abordées dans notre étude. Ici encore, les modalités envisagées par le législateur sont diverses et variées. Elles sont calquées sur le CDI, sur le CDD ou sont propres, c’est-à-dire exorbitantes du droit commun. Et à chaque fois, il nous semble que le caractère hybride des contrats d’activité segmentée ressort fortement à cette aune. A tel point d’ailleurs que certains des contrats étudiés relèvent d’une forme de gageure tant ils tentent, en quelque sorte, de concilier l’inconciliable.
Keywords: Activité segmentée; CDI de chantier; CDI intérimaire; Contrat de travail; Contrat de travail intermittent; Contrats de travail à durée déterminée; Droit du travail; Intermittent du spectacle; Labour law; Portage salarial; Relations individuelles du travail; Travail temporaire

Les leviers juridiques à l’inclusion professionnelle des personnes en situation de handicap dans les entreprises - Berthomé-Lelaure, Stéphanie (Université de Rennes, 2023)
Avec un taux d’emploi de seulement 44% des personnes reconnues handicapées contre 73% pour le reste de la population en 2021, la France peut difficilement contester l’inefficacité de son cadre juridique par rapport à l’inclusion professionnelle des personnes en situation de handicap.Or, le travail est un élément essentiel à la consécration de la dignité et de la cohésion sociale. Il faut donc comprendre les raisons de l’inefficacité des politiques publiques et trouver des leviers juridiques.Jusqu’à présent, ancrée dans une dynamique de justice sociale dépendante de l’intervention de l’État, l’inclusion professionnelle n’a porté qu’une attention limitée à l’entreprise la contraignant ou l’incitant financièrement. Le sujet doit être présenté différemment. La personne en situation de handicap, engagée dans un parcours professionnel, ne doit pas avoir un statut spécifique stigmatisant. Elle est avant tout un travailleur dont l’entreprise a besoin pour développer son activité. Il faut dépasser le climat de méfiance envers l’entreprise qui a émergé avec les organisations du travail du début du XXème siècle peu soucieuses du bien-être des salariés. L’entreprise a évolué et joue un rôle social avec la mise en œuvre de la responsabilité sociale des entreprises. Mais l’entreprise ne peut y arriver seule. Pour parvenir à une inclusion professionnelle effective, elle a besoin du soutien du secteur sanitaire et médico-social qui doit être accompagné dans cette évolution.
Keywords: Company; Disability; Entreprise; Entreprises; France; Handicap; Handicapés; Health and social care; Inclusion; Intégration sociale; Santé; Secteur sanitaire et médico-Social; Société; Travail

La rénovation des cadres juridiques de gouvernance foncière dans les pays en développement : étude de cas croisée du Niger, d'Haïti et de l'Afrique du Sud - Pennec, Jérôme (Université de Bretagne Occidentale, 2023)
Le travail de recherche examine les processus d’élaboration et de mise en œuvre de nouveaux cadres juridiques de gouvernance foncière dans les pays en développement. Par le biais de trois pays d’étude de contextes juridiques, historiques et culturels très différents, à savoir le Niger, Haïti et l’Afrique du Sud, l’analyse met en évidence que les réformes foncières dans les pays en développement sont confrontées à certaines problématiques juridiques et difficultés de mise en œuvre communes. Elle démontre les limites des modèles classiques et techniques de gouvernance foncière, ainsi que les failles du cadre international et l’influence de l’aide internationale en la matière. Elle souligne également l’importance de prendre en considération les multiples pratiques sociales en lien avec l’accès et l’usage des terres, qui dépassent largement la seule notion classique de propriété. Sur la base de ce constat, la thèse établit que la prise en compte des pluralités juridiques est un élément clé pour envisager la rénovation des cadres juridiques du foncier, mais que cette étape à elle seule n’est pas suffisante pour créer un système efficient de gouvernance foncière. Il apparaît ainsi nécessaire de penser l’organisation de ces pluralités au sein d’un véritable système pluraliste ordonné. L’analyse évoque les éléments concrets de mise en application de ce concept à des échelles nationales. This paper examines the design and implementation processes of new legal frameworks for land tenure in developing countries. In the light of three case studies with different legal, historical and cultural contexts – namely Niger, Haïti and South Africa – the study shows that they all face the same legal and implementation challenges while carrying out such reforms. The study highlights the limitations of classical and technical land tenure governance models as well as the weaknesses of the international framework and the influence of international assistance on this subject. Moreover, it demonstrates the need to consider the different social practices of land access and use, which go beyond the sole notion of land property. Building on this assessment, the study shows that the examination of legal pluralim is fundamental to consider the reform of land tenure’s legal frameworks, even though this step is not sufficient to create an efficient system for land tenure governance. It seems thus necessary to think the organization of these pluralities within a truly pluralist and ordered system. The study puts forward concrete, hands-on elements for implementing this concept at national levels.
Keywords: Afrique du Sud; Developing countries; Gouvernance foncière; Haïti; Land reform; Legal pluralism; Niger; Pays en développement; Pluralisme juridique; Réforme agraire; South Africa

La soft law, un moyen de régulation économique : approche de droit comparé France - Tunisie - Chebbi, Oussema (Université Grenoble Alpes, 2023)
L’objectif de cette entreprise est d'évaluer l'usage du droit souple comme moyen de régulation économique en France et en Tunisie. Sur le plan méthodologique, la présente recherche part du droit positif mais demeure ouverte sur d’autres disciplines voisines. Dans cette perspective il importe d’indiquer que la méthode retenue n’exclut pas le recours à des outils d’analyse relevant de la théorie du droit, des sciences administratives, de la sociologie, ou encore de l’analyse économique du droit qui pourraient expliquer certains choix des pouvoirs publics. Sur le fond, l'évaluation du droit souple renvoie à étudier dans un premier temps la consécration de ce procédé juridique en matière de régulation économique, puis dans un second temps, le contrôle exercé par les juges nationaux français et tunisien en la matière.Au fur et à mesure du développement de la présente étude, plusieurs problématiques sous-jacentes furent traitées à l'instar de la normativité des actes de droit souple, le régime contentieux de ces derniers, l'évolution du modèle de co-régulation économique et le développement économique (notamment pour le cas tunisien).
Keywords: Droit Souple; Droit public; Droit souple; France; Public law; Regulation; Régulation; Régulation, Théorie de la; Soft law; Tunisie; Études comparatives

Les clauses du contrat de travail et la dignité du salarié : étude comparée des droits du travail français et béninois - Gbénou, Clémence Victoria (Université Jean Moulin Lyon 3, 2023)
La question de la dignité de la personne, plus singulièrement celle du salarié, est permanente et actuelle. Elle fait l’objet de vifs débats. Les uns lui dénient son aptitude à intégrer la sphère du Droit en raison de sa capacité à englober des situations diverses et variées, lui valant le qualificatif ‘fourre-tout’. Les autres au contraire, lui reconnaissent toute sa place dans la sphère juridique, étant au fondement des droits de l’homme dont elle fédère les imbrications. Malgré l’ancienneté des débats, la question ne s’épuise pas. Au contraire, elle se redécouvre, voire se renouvelle. Comme pour, à nouveau, les relancer sur la place juridique, la chambre sociale de la Cour de cassation française relie la notion à celle de bonne foi contractuelle, dans un arrêt récent du 8 février 2023, n°21-14.451, en précisant qu’ « (… ) il résulte de l'article L. 1222-1 du code du travail que l'atteinte à la dignité de son salarié constitue pour l'employeur un manquement grave à son obligation d'exécuter de bonne foi le contrat de travail (…) ».Elle rappelle ainsi que la dignité, celle du salarié, n’est pas extérieure au rapport contractuel de travail. Bien au contraire, elle en constitue l’un des objectifs majeurs auquel doivent converger les divers principes régissant ces rapports. Pour ce faire, la dignité intéresse en amont la formation du contrat et sa conclusion, en aval son exécution et sa fin. L’étendue des obligations contractées se matérialise à travers le contenu des clauses du contrat de travail, lesquelles transcrivent la volonté des parties. Mais dans un rapport contractuel inégalitaire comme celui du travail subordonné, la dignité du salarié trouve-t-elle véritablement à libérer ses tentacules ? C’est dans ce cadre que se situe le présent travail qui vise à rechercher l’articulation entre l’exigence de la dignité du salarié et les clauses du contrat de travail. Mieux, comment s’effectue la conciliation entre la liberté de choix des clauses du contrat de travail et l’exigence de sauvegarde de la dignité dans les droits du travail français et béninois ?Il ressort des deux grandes parties de ce travail, des similitudes formelles dans les divers mécanismes de conciliation en place au sein des deux Etats. Néanmoins, des différences notables subsistent, en ce que ces divers mécanismes, parfois différemment mobilisés, produisent inévitablement des effets soit inverses, soit convergents.
Keywords: Bénin; Clauses de mobilité; Clauses discriminatoires; Clauses du contrat de travail; Clauses du renouvellement indéfini de CDD; Clauses limitatives du droit au repos; Contrat de travail; Devoir d'information; Dignité; Dignité de la personne (droit); Discrimination; Droit d'alerte; Droit du travail; Employeur et employé (droit); France; Intégrité morale; Intégrité physique; Intérêt de l'entreprise; Labour law; Liberté; Personnel (droits); Responsabilité; Santé et sécurité; Subordination; Vie; Volonté du salarié; Égalité; Études comparatives

La transparence des grandes entreprises en matière environnementale et sociale - Saragaglia, Jessie (Université Grenoble Alpes, 2023)
Le devoir de transparence environnementale et sociale des grandes entreprises, dispositif phare de la Responsabilité Sociale d’Entreprise (RSE), se caractérise par la dualité de sa fonction. Ce devoir consiste pour l’entreprise à apporter une information à ses parties prenantes quant aux impacts environnementaux et sociaux de son activité. Au regard des risques de pratiques de greenwashing ou socialwashing de la part des entreprises, la qualité de l’information apportée est déterminante. Un enchevêtrement de mécanismes de droit dur et de droit souple est ainsi mis en œuvre au service de la pertinence et de la fiabilité des informations. En outre de sa fonction informative, le devoir de transparence environnementale et sociale revêt une fonction régulatrice. L’instauration d’un tel devoir par les pouvoirs publics a pour objectif de guider les entreprises vers une prise en compte effective des impacts décrits dans les documents d’information. En d’autres termes, le devoir de transparence invite l’entreprise à concrétiser son discours en actes tangibles. A cet effet, des mécanismes juridiques et extra-juridiques sont mobilisés, reposant sur les rétributions du marché (sanction réputationnelle notamment) et sur les mutations de la place de l’entreprise dans la société. En définitive, tout l’enjeu du droit de la RSE réside dans sa capacité à élaborer une norme juridique (l’obligation d’information en matière environnementale et sociale) qui soit de nature à susciter le respect par les entreprises d’une norme sociale non sanctionnée juridiquement (la prise en compte effective des enjeux environnementaux et sociaux).
Keywords: Autorités de marché; CSR; Competencia; Concurrence; Corporate Social Responsibility; Corporate sustainibility reporting directive; Devoir de transparence environnementale et sociale; Duty of transparency; Déclaration de performance extra-Financière; Environmental and social issues; Extra-Financial disclosure; Information environnementale et sociale; Investissements de capitaux; Non-Financial reporting; RSE; Reporting extra-Financier; Responsabilité sociale de l'entreprise; Responsabilité sociétale des entreprises multinationales

مدى تأثر الشركة بانسحاب الشريك (دراسة مقارنة) - شريفي, ويزة (جامعة مولود معمري, 2023)
تهدف دراسة موضوع انسحاب الشريك في القانون الجزائري والقانون المقارن إلى تحديد التنظيم القانوني لعملية انسحاب الشريك من الشركة، والوقوف على أسباب ومبررات عملية الانسحاب، وأهم الوسائل المتاحة لتحقيقه، خاصة وأنّ آثار الانسحاب تنصرف أساسا إلى الشريك المنسحب، كما تمتدإلى الشركة والشركاء والغير الذي تعامل مع الشركة. وقد أثبتت الدراسة المقارنة في القانونين الجزائري والفرنسي، مدى تأثر القانون الجزائري بالقانون الفرنسي، بسبب غياب تنظيم قانوني خاص في التشريع الجزائري لمسالة انسحاب الشريك من الشركة. ونتيجة لهذا الفراغ القانوني، استوجب الرجوع إلى القواعد العامة في القانون المدني، الذي ينظم عقد الشركة بصفة عامة، مع الأخذ بعين الاعتبار خصوصية الشركات التجارية والأحكام الخاصة المنظمة لها. إنّ انسحاب الشريك، قد يكون إراديًا في حالة قيامه بالتخلّي عن حقوقه الاجتماعية في الشركة، وقد يكون الانسحاب لا إراديا، عندما يكون عن طريق حكم قضائي، بحيث يتم في هذه الحالة إنهاء مهام الشريك من دون إرادته. وكقاعدة عامة، فإن انسحاب الشريك يِؤدي حتما إلى انقضاء الشركة، لاسيما إذا تعلق الأمر بشركات الأشخاص، إلا إذا كانت القوانين الأساسية للشركة والشركاء الباقون، قد قرروا خلاف ذلك، بمعنى استمرار الشركة. L’étude du retrait de l’associé en droit algérien et droit comparé a pour but de déterminer la réglementation juridique du mécanisme du retrait de l’associé de la société, afin de mettre l’accent sur les motifs du retrait, les moyens et techniques juridiques pour y parvenir, mais surtout ses effets, car le retrait touche principalement les droits de l’associé, les partenaires associés, et enfin les tiers. L’étude comparative du droit algérien et français, réaffirme l’influence du droit algérien par le droit français en raison de l’absence d’une règlementation spécifique relative au droit de retrait de l’associé. En raison de ce vide juridique, il est nécessaire de se référer aux règles générales du droit civil qui régissent le contrat de société, tout en tenant compte des spécificités des différents types de sociétés commerciales et des textes qui les régissent. Il est à préciser, que le retrait de l’associé peut être volontaire suite à sa renonciation à ses droits sociaux, mais il peut être involontaire dans le cas du retrait judicaire, quand il s’agit de mettre fin de manière unilatérale aux fonctions de l’associé. En règle générale, le retrait de l’associé entraine obligatoirement la dissolution de la société, notamment dans le cas des sociétés de personnes, sauf si les statuts de la société ou les associés ont convenus autrement, c’est à dire de la continuité de la société.
Keywords: Associés; Droit algérien; Droit comparé; Liquidation; Retrait d'associé; Scission; Société; التصفية; الشركاء; الشركة; القانون الجزائري; القانون المقارن; القسمة; انسحاب الشريك

La compétence universelle en matière civile - Alaa El Sayed El Ghadban, Tarek (Université Paris 1, 2023)
L’absence de législateur universel oblige chaque ordre juridique à déterminer les conditions dans lesquelles ses juridictions exerceront une compétence internationale. Parallèlement, la mondialisation réduit progressivement les situations complètement cantonnées au sein d’un seul ordre juridique. En effet, les progrès technologiques augmentent le risques qu’un comportement, dont les causes ou les effets traversent les frontières étatiques, échappe à tout contrôle judiciaire, à cause de l’hétérogénéité des ordres juridiques étatiques. La majorité ces ordres juridiques étatique connaissent deux régimes permettant à leurs juridictions de connaître d’un litige, malgré leur incompétence de principes en vertu de leurs règles ordinaires de compétence internationale. Le premier, issu du droit pénal international, permet aux États de poursuivre les auteurs de certains comportements qui menacent les intérêts de la société internationale en son ensemble. Il s’agit de la compétence universelle en matière pénale, qui peut entraîner des conséquences civiles tel que le droit des victimes à réparation du préjudice subi. Le deuxième régime, issu du droit international privé, permet à un juge civil normalement incompétent, en vertu des règles ordinaires de compétence internationale des tribunaux de son ordre juridique, de connaître d’une affaire si le demandeur se trouve dans l’impossibilité de faire raisonnablement valoir ses droits à l’étranger. Or, les objectifs et les modes de fonctionnement similaires de ces deux régimes permettent d’envisager un régime unifié de compétence universelle en matière civile mieux adapté aux besoins d’un monde globalisant.
Keywords: Accès à la justice; Compétence universelle; Droit pénal international; Droits de l'homme; Droits fondamentaux; Déni de justice; Mondialisation

The Law of the Sea and Nigeria's Marine Policy: A Critical Evaluation - Tagowa, Wonotanzokan Nzeda (Ahmadu Bello University, 2023)
Keywords: Droit maritime; Marine policy; Nigeria; Sea

La exclusión del socio administrador en la limitada por infracción de la prohibición de competencia - Benitez Garcia, Rufino (Universidad de Sevilla, 2023)
En esta Tesis Doctoral se analiza la causa legal de exclusión del socio que, al propio tiempo, es administrador de una sociedad limitada, consistente en la vulneración de la prohibición de competencia. El instrumento de la exclusión del socio tiene una importancia práctica como mecanismo de tutela de la mayoría del capital social en una entidad capitalista contra aquellos socios que puedan menoscabar la paz social o, de alguna forma, comprometer el desarrollo de la actividad común programada. En concreto, el motivo legal de salida involuntaria sobre el que nos centramos es el atinente a la infracción de la interdicción de competencia que recae sobre dicho sujeto que además de socio es gestor del ente social. A este respecto, la Ley de Sociedades de Capital (LSC), en su artículo 350, regula esta causa legal de expulsión de un modo muy parco. No obstante, en los últimos tiempos no debe menospreciarse el interés casacional que presenta en la actualidad esta herramienta de la que puede servirse la sociedad en cuestión para provocar la salida de aquellos socios que hayan perdido su affectio respecto de la primera. Es el artículo 229.1.f) LSC el que conmina al administrador a abstenerse de llevar a cabo actividades por cuenta propia o ajena que entrañen una competencia efectiva, sea actual o potencial, con la sociedad o que, de cualquier otro modo, le sitúen en un conflicto permanente o estructural con los intereses de dicha entidad. De esta manera, en esta investigación se estudia de un modo profuso la prohibición de concurrencia recayente sobre el administrador, ya que es necesario comprender hasta dónde puede llegar dicho gestor que, al propio tiempo, es socio, en su discurrir competitivo. En definitiva, esta infracción fundamenta el recurso por parte de la sociedad a la baja involuntaria del socio en cuestión. En este sentido, la actividad competitiva no se erige en origen único de los conflictos estables de interés en que puede verse envuelto el administrador social. En cualquier caso, la quiebra del deber de lealtad a que da lugar la violación de la prohibición de competencia no acarrea que dicha conducta deba calificarse como acto de competencia desleal. Nuestro trabajo limita su alcance a la decisión social de salida forzosa del socio administrador competidor, sin ignorar que, en determinados supuestos, el acuerdo de exclusión precisa de una resolución judicial firme (cuando se ostente, al menos, el 25% del capital social).

أحكام التنازل عن الحصص وانتقالها في الشركة ذات المسؤولية المحدودة - بشيخ, ام الخير (Ibn Khaldun University of Tiaret, 2023)
المبدأ العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، إذ لا يجوز التنازل عن الحصص إلى الغير إلا بموافقة أغلبية الشركاء الحائزين لثلاثة أرباع رأس المال. وهو ما نصت علية المادة571 من القانون التجاري. والاستثناء حرية التنازل عن الحصص إلى الأصول والفروع والأزواج مالم ينص القانون الأساسي على تقييد التنازل. كما يخضع فيها التنازل عن الحصص للاسترداد وهو حق مقرر لمصلحة الشركاء والشركة لشراء الحصص المرغوب في التنازل عنها في حالة رفض الموافقة على المتنازل إليه. وإذا كان الأصل العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، فإن الحصص في هذه الشركة تنتقل بكل حرية إلى ورثة الشريك، بشرط أن لا يترتب على ذلك زيادة عدد الشركاء عن الحد الأقصى المقرر قانونا والذي هو 50 شريكا. ومع ذلك يمكن للشركاء تقييد انتقال الحصص إلى الورثة بشرط أن يتم إدراج هذا الشرط في القانون الأساسي للشركة. The general principle in a limited liability company is to restrict the assignment/ abdication of shares, as it is not permissible to assign shares to third parties except with the share-holders majority’s approval who possess three-quarters of the capital. This is what is stipulated in Article 571 of the Commercial Law. The exception is the freedom to assign/transfer shares to ascendants, descendants, and spouses, unless the Basic Law stipulates a restriction of abdication. In addition, the assignment of shares is subject to recovery, which is a right established in the interest of the partners and the company to purchase the desired shares to be assigned in the event of refusal to approve the assignee. Therefore if the general principle in the limited liability company is to restrict the abdication from shares, then the shares in this company are transferred freely to the partner’s heirs, provided that this does not result in an increase in the number of partners beyond the legally prescribed maximum, which are 50 partners. However, the partners can restrict the transfer of shares to the heirs, provided that this condition is included in the articles of association of the company.
Keywords: Associés; Cession d'actions; Droit de rachat; Offre d'actions; Société à responsabilité limitée

Fishing for Rights ! The Protection of the Individual in Fisheries - Longo, Andrea (Università degli studi di Milano, 2023)
La pêche est une activité humaine ayant un impact considérable sur l'environnement. Une mauvaise gouvernance, des mécanismes d'application faibles ou inexistants et des subventions excessives et non réglementées ont entraîné la surexploitation des stocks de poissons dans le monde entier, en produisant des conséquences potentiellement désastreuses sur l'écosystème marin et la sécurité alimentaire. Cependant, les pratiques de pêche non durables sont également liées à des abus à bord des navires de pêche : les organisations internationales et non gouvernementales attirent progressivement l'attention sur les pratiques répandues de violations des droits de l'homme et de crimes en mer, en appelant à repenser le régime international pour la conservation et la gestion des pêches en vue de concilier la sécurité économique et environnementale avec la dimension sociale de la pêche durable.Dans ce contexte, la présente thèse de doctorat aborde les problèmes conceptuels et pratiques qui se rattachent à la protection des individus impliqués dans ou autrement affectés par l'activité de pêche, en se concentrant particulièrement sur les victimes à bord des navires de pêche. La thèse s'appuie sur les études relatives à l'interaction des régimes en vue de favoriser le dialogue entre le droit international des droits de l'homme et le droit de la mer, deux régimes relevant du système plus large du droit international public. Après avoir exploré la portée de la question de recherche et fourni le contexte théorique et factuel, le premier chapitre se penche sur le régime du droit des droits de l'homme et examine la notion de juridiction telle qu'elle s'applique aux violations des droits de l'homme en mer, en étudiant en particulier l'utilisation potentielle de la norme sur la juridiction de l'État du pavillon comme critère pour attirer une violation des droits de l'homme à bord de navires de pêche relevant de la juridiction de l'État du pavillon. Le chapitre explore également le contenu et la portée des obligations en matière de droits de l'homme, en se concentrant notamment sur un ensemble de six droits prétendument violés à bord des navires de pêche, à savoir le droit à la vie, l'interdiction de la torture et des traitements inhumains et dégradants, l'interdiction de l'esclavage et des formes modernes d'esclavage, l'interdiction de la privation arbitraire de liberté, le droit à un travail décent et le droit à la santé. Ensuite, le deuxième chapitre se concentre sur le droit de la mer, en retraçant spécifiquement le développement historique qui a conduit à la consolidation du régime actuel de la pêche et en explorant la portée de la notion de pêche illégale, non déclarée et non réglementée et du phénomène de la criminalité dans le domaine de la pêche. Enfin, le dernier chapitre traite de la notion de juridiction telle qu'elle est utilisée dans le droit de la mer, en étudiant spécifiquement son contenu en ce qui concerne tous les acteurs étatiques de ce régime, à savoir l'État côtier, l'État du pavillon, l'État du port et l'État du marché. En particulier, ce chapitre examine de plus près les obligations de chaque État en ce qui concerne la protection de la personne à bord des navires de pêche, en accordant une attention particulière aux pouvoirs d'exécution de l'État côtier et à l'exercice par l'État du pavillon du contrôle des ses navires. Enfin, et surtout, il apporte un éclairage sur la contribution potentielle que les États du port et les États du marché pourraient apporter à la protection des personnes à bord des navires de pêche.
Keywords: Droit de la mer; Droits de l'homme; Fisheries regime; Fisheries resources; Fishing vessels; Human Rights; Law of the Sea; Navires de pêche; Pêches; Ressources halieutiques; Régime de pêche

La protection des actionnaires minoritaires des sociétés anonymes dans l'espace juridique OHADA - Oueina, Florent (Université de Perpignan Via Domitia, 2023)
Susceptible d'être lésés dans leurs droits représentés par les actions dont ils disposent, les minoritaires dans une société anonyme, ont besoin d'être protégés « non parce qu'ils sont minoritaires, mais parce que leurs intérêts apparaissent comme dignes de protection ». Il n'est pas rare dans le cadre du fonctionnement de la société anonyme d'assister à la prise de décisions contraires, non seulement à l'intérêt des minoritaires, mais également à l'intérêt social, par les actionnaires majoritaires dans l'unique dessein de satisfaire les membres de la majorité au détriment des autres actionnaires. Cette tendance à l'écrasement des minoritaires entraîne des conflits, sinon des oppositions entre actionnaires conduisant à la constitution de blocs antagonistes dont l'attitude peut provoquer une crise au sein de la société. L'étude réside dans l'analyse des garanties et dans la recherche constante d'une protection efficace qu'offrent le législateur et l'autorité du marché financier aux investisseurs minoritaires dans l'espace OHADA. Cette étude étendue en droit français existe aussi en droit OHADA. Likely to be infringed in their rights represented by the actions at their disposal, minority shareholders in a public limited company need to be protected "not because they are in the minority, but because their interests appear to be worthy of protection". It is not uncommon in the context of the operation of the limited company to witness the taking of decisions contrary, not only to the interests of the minority shareholders, but also to the corporate interest, by the majority shareholders in the sole purpose of satisfying the members of the majority to the detriment of the other shareholders. This tendency to crush minorities leads to conflicts, if not oppositions between shareholders leading to the formation of antagonistic blocs whose attitude can provoke a crisis within society. The study lies in the analysis of guarantees and in the constant search for effective protection offered by the legislator and the financial market authority to minority investors in the OHADA area. This extended study in French law also exists in OHADA law.
Keywords: Actionnaire minoritaire; Company profits; Droit OHADA; Droit français; Droit à l'information; Intérêt social; Marché financier OHADA; Minority shareholder; OHADA Law and French Law; OHADA stock market; Public limited companies; Rights of information; S.A.; Société Anonyme

La succession patrimoniale au Gabon entre coutume et droit moderne - Dhembet, Guy Farel (Université de Limoges, 2023)
La succession patrimoniale au Gabon respecte une certaine juridicité, un ensemble de normes coutumières et légales dès son rattachement judiciaire au territoire de Saint-Louis (Sénégal) en 1854. L’autonomisation de la coutume par rapport aux lois impériales dans le décret du 10 novembre 1903, acte la configuration polyjurale de la justice gabonaise et le pluralisme juridique qu’elle occasionne. La conciliation de la coutume et la loi en droit patrimonial de la famille est concrétisée dans la loi n°19/89 du 30 décembre 1989 portant création de la seconde partie du code civil gabonais, mais des pierres d’achoppement induisent la suppression de certaines coutumes dans la loi n°002/2015 du 25 juin 2015.En nous intéressant aux conflits successoraux dans le famille gabonaise, nous mettons en exergue les tiers discours, garants et pratiques que mobilisent leurs arbitrages. La question de la légitimité de la norme applicable entre la coutume et la loi est déterminante pour la justesse du jugement. Elle réinterroge l’importance pour l’arbitre d’être instruit aux lois et coutumes pour l’exercice d’un Droit flexible, ouvert sur l’ensemble de la juridicité. Le multijuridisme et l’autonomie du justiciable par rapport aux traditions juridiques constitutives de la pluralité juridique en droit patrimonial de la famille gabonaise l’impose d’ailleurs, en ce sens qu’il s’agit comme en 1903 de juger le justiciable conformément à la tradition juridique à laquelle il s’identifie et non à celle qu’on l’impose. À la diversité des problématiques successorales contemporaines, des solutions multiples et légitimes sonnent comme une évidence pour le triomphe de la justice et la pérennisation des liens familiaux dans une matière aussi sensible que contentieuse qu’est le droit patrimoniale de la famille.
Keywords: Coutume; Droit des successions; Gabon; Patrimoine; Succession (droit)

Le contrat à titre gratuit - Pansu, Floriane (Université Paris 1, 2023)
Depuis le milieu du XXe siècle, la doctrine retient une conception abstraite de la gratuité, en la définissant cette dernière comme la simple absence de contrepartie. Le développement de la « gratuité » intéressée au XXIe siècle, notamment sur internet, justifie un retour à la conception bienfaisante de la gratuité. La « gratuité » intéressée ne doit pas être soumise au régime du contrat à titre gratuit, qui contient notamment de nombreuses dispositions de faveur pour le concédant. La défense de la conception bienfaisante de la gratuité est consolidée par la précision des éléments objectifs permettant de présumer l’intention bienfaisante subjective : l’existence d’une relation d’affection unissant les parties ou l’affectation de l’avantage procuré à l’œuvre philanthropique. Par ailleurs, la doctrine conteste la qualification contractuelle de l’accord relatif à l’assistance bénévole. Ce doute rayonne sur toute la catégorie des contrats à titre gratuit. L’accord gratuit pourrait ainsi ne jamais constituer un engagement sérieux. Toutefois, l’existence d’éléments objectifs adjoints à l’accord, et notamment d’une forme, permettent d’attester du sérieux de l’engagement des parties et de garantir les fondements de la force obligatoire de celui-ci. L’inexécution doit en être sanctionnée. Et cet accord conditionne et détermine les effets juridiques afférents à la prestation exécutée. Since the middle of the 20th century, authors have adopted an abstract approach of gratuitous contracts, defining the gratuitous aspect as the sole absence of compensation. In the 21st century, the internet has emphasized that businesses can be run through the provision of “free” goods and services. These contracts are self-interested and should not be subject to the rules applicable to gratuitous contracts, which contain numerous provisions favourable to the grantor. A benevolent approach of gratuitous contracts should be preferred, where gratuitous contracts are defined through benevolence and not only the absence of compensation. This approach involves a subjective element, the benevolent intention. Objective elements allow this subjective intention to be presumed: affective relationship between parties and philanthropy. Furthermore, authors write that the agreement on voluntary assistance is no binding contract. This doubt extends to the whole category of gratuitous contracts. However, the existence of objective elements, form, in particular, attests the seriousness of the parties’ commitment and grounds its binding force. Non-performance of the gratuitous contract must be remedied. And the agreement causes and determines the legal effects of the performance.
Keywords: Benevolence; Bienfaisance; Binding force; Contract; Contractual obligations; Contrat; Contrats; Contrats à titre gratuit; Force obligatoire; Gratuitous contract; Gratuité; Interest; Intérêt; Motifs; Motives; Nature contractuelle des obligations; Oeuvres de bienfaisance (droit); Philanthropie; Philanthropy

La lutte contre la corruption et les droits de l'Homme : Approche comparative des cas guinéen, français et camerounais - Traoré, Alsény (Université Côte d'Azur, 2023)
Phénomène ancien, la corruption est une pratique dénoncée de tout temps notamment sur le plan religieux et moral. En droit, la lutte contre le phénomène est restée longtemps une préoccupation nationale, avant de connaitre une internationalisation qui ne cesse de s'étendre. Placée au cœur du débat public, cette lutte prend en compte la pluralité des formes et des conséquences de la corruption surtout sur les droits de l'Homme. La corruption, source d'abus et d'injustice, affecte simultanément toutes les générations de droits de l'Homme. L'État se retrouve face à une double obligation : respecter ses engagements en matière de droits de l'Homme et prévenir et lutter contre la corruption. Les réponses anticorruption, nombreuses et variées, restent cependant insuffisantes.La présente thèse s'interroge sur l'effectivité de ces droits dans un contexte marqué par la corruption publique, la manipulation et l'inefficacité des mécanismes anticorruption. Au regard des exigences qu'ils imposent, les enjeux soulevés par leur double interaction avec la corruption sont examinés.L'admission des principes d'indivisibilité et d'interdépendance des droits de l'Homme, en plus de remettre en cause la dichotomie des obligations étatiques, place ces droits à un égal niveau de protection juridique. D'où le choix de garder les trois générations de droits de l'Homme dans l'analyse de l'incidence liberticide de la corruption publique et de l'insuffisance des mécanismes anticorruption. Pour faire ressortir les particularismes européens et africains en la matière, des États pouvant les représenter (France, Guinée et Cameroun) ont été comparés.Cette thèse démontre l'existence d'une pluralité de facteurs d'ancrage et de victimes de la corruption publique, la pertinence de la consécration des principes d'indivisibilité et d'interdépendance des droits de l'Homme au regard des incidences liberticides de la corruption. Il se trouve que la violation d'un droit du fait de la corruption engendre généralement celle d'autres droits de l'Homme. Cela est un marqueur important de l'urgence à renforcer l'efficacité des mécanismes anticorruption dans le respect de ces droits. La corruption publique pose ainsi un double défi aux États : la nécessité de lutter contre un phénomène liberticide et celle de garantir le respect des droits dans cette lutte.La recherche démontre que la corruption publique et les insuffisances de la lutte anticorruption influencent négativement les droits de l'Homme. En fait, ces droits se retrouvent sous l'étau de diverses formes de corruption et des mécanismes anticorruption. Si leurs manifestations, leurs facteurs d'ancrage, et leurs victimes sont identiques dans les États étudiés, leur portée varie en fonction de la nature des droits et, parfois, des contextes. Les droits civils et politiques sont directement atteints par ces phénomènes, alors que les droits-créance et droits-solidarité n'en subissent principalement que des effets indirects. Et, la carence de l'État de droit les aggrave.La question de l'équilibre entre droits de l'Homme et lutte anticorruption est soulevée dans cette thèse. Plaidant en faveur des premiers, l'étude conclut que ces droits ne devraient pas être sacrifiés sur l'autel de la recherche d'une lutte anticorruption efficace. En mettant la protection des droits de l'Homme au cœur de la lutte anticorruption, cette thèse montre les évolutions juridiques et institutionnelles en cours ou à venir. La judiciarisation de la lutte anticorruption internationale pourrait être l'une de ces évolutions marquantes. La proposition d'une définition du crime international de corruption, et d'un régime de responsabilité internationale des acteurs étatiques et privés font partie des contributions sur les évolutions espérées.
Keywords: Anti-Corruption Law; Case study; Comparative law; Corruption; Domestic Law. International Law; Droit anti-Corruption; Droit comparé; Droit international; Droit interne; Droits de l'Homme; Droits de l'Homme (droit international); Etude de cas; Human rights; Lutte contre la corruption

Reconstruction of CCMA Commissioners' Perceptions of Dispute Resolution in South Africa: a multi-perspective approach - Bendeman, H. M. A. (Potchefstroomse Univèrsiteit vir Christelike Hoër Onderwys, 2023)
A reconstruction of CCMA commissioners' perceptions of dispute resolution in South Africa: A multi-perspective approach This study focuses on the problems in the dispute resolution system in South Africa. The aim of this study is to explore the perceptions of commissioners of the Commission for Conciliation, Mediation and Arbitration (CCMA) regarding the capacity of parties to effectively deal with labour .conflict and disputes within the legal framework provided by the Labour Relations Act (LRA) (66/95). This includes an investigation into the reasons for the high referral rate of unfair dismissal cases to the CCMA and the influence of the case-overload on the effective functioning of the disputé resolution system. The · functionalist and conflict theoretical perspectives are used to study the structural aspects of the dispute resolution system and to explore structural strain. The interactionist perspective is used in the methodology of this study to reconstruct the perceptions of a group of CCMA commissioners. This study is predominantly of a qualitative nature and was conducted in an exploratory manner through in-depth interviews and e-mail questionnaires. Dunlop's open systems approach allowed for the conceptualisation of the major dispute resolution components of the labour relations system. T!Je analysis of the transformation of conflict formed the basis for understanding the background, the problem statement, the aims and assumptions of this study. lt was found that the guidelines in Schedule eight of the LRA (66/95) have become the norm for dealing with conflict within an enterprise, creating complex and technical processes for dealing with disputes. However, most of the employers and individual employees do not have the knowledge and skills to operate effectively in the system. This has led to a new type of adversarialism in the individual employment relationship, which is based on rights, rules and power. The very technical nature of the internai conflict resolution mechanisms, the incapacity of the parties and the adversarial nature of the labour relationship have resulted in the high referral rate and consequent problems that the CCMA is experiencing.
Keywords: Afrique du Sud; Arbitrage; Arbitragem; Arbitration; Conciliation; Conflict resolution; Conflits de travail; Dispute settlement; Industrial sociology; Labour dispute; Labour relations; MARD; Mediación; Mediation; Mediação; Médiation; Relations de travail; Règlement des différends; Résolution de conflit; Sociologie industrielle; South Africa

Le consentement sur le web : une analyse transdisciplinaire - Toth, Michaël (Université Côte d'Azur, 2023)
Le développement numérique des trois dernières décennies a transformé nos vies. Il a permis aux gens de partager des informations dans le monde entier, mais a également mis en lumière des risques sans précédent pour la vie privée. La généralisation de la publicité personnalisée comme moyen de financement des sites web est rapidement devenu un point de tension dans le domaine du droit à la vie privée. Les évolutions législatives dans l'Union européenne depuis 2008 ont posé certains fondements essentiels, en particulier l'importance centrale du consentement de l'utilisateur, conduisant au développement de plateformes de gestion du consentement (CMP). Dans cette thèse, nous avons commencé par mettre en lumière la complexité des interfaces offertes par les CMPs, et les problématiques soulevées par certains types de designs spécifiques, généralement regroupés sous le nom de "dark patterns". Pour ce faire, nous avons mobilisé une méthode dédiée, la critique d'interaction, pour réfléchir spécifiquement à trois types de design : le cookie wall, le consent wall, et le service réduit. Pour chacun d'entre eux, nous avons analysé les différentes phases de la gestion du consentement, et souligné l'intérêt d'un dialogue transdisciplinaire entre sciences techniques et sciences sociales. D'un point de vue juridique, nous avons également analysé le rôle des CMP au regard du règlement européen sur la protection des données. En comparant les traitements de données effectués par des CMPs populaires, nous avons identifié plusieurs situations dans lesquelles ces entreprises définissent les finalités et les moyens des traitements de données, ce qui en fait de facto des responsables de traitement au sens de la loi européenne. Cela a d'importantes implications en termes de responsabilité pour ces entreprises. Enfin, nous avons analysé systématiquement la manière dont les CMP pouvaient influencer, contraindre ou manipuler les éditeurs de sites web par le biais de choix malhonnêtes en matière d'interface et de conception. En suivant le parcours d'un éditeur souhaitant installer le service de CMPs populaires, nous avons réalisé une analyse approfondie du processus requis, des options et des fenêtres contextuelles de consentement fournies. Nous avons mis en lumière les impacts, positifs et négatifs, de ces services, ainsi que leur influence potentielle sur les éditeurs de sites web.
Keywords: Consent; Consentement; Consentement (droit); Dark patterns; Données personnelles; Droit à la vie privée; EPrivacy; GDPR; Identité numérique; Interfaces utilisateur (informatique); Manipulation; Manipulation (psychologie); Personal data; Protection de l'information (informatique) -- Droit; RGPD; Traces numériques; Tracking; Traçage

Las cláusulas sobre seguro en los contratos de utilización del buque: responsabilidad y subrogación del asegurador - Gilabert Gascón, Albano (Universitat Jaume I, 2023)
La presente tesis doctoral pretende avanzar en el conocimiento sobre las cláusulas sobre seguro insertas en los contratos de utilización del buque, así como las consecuencias que su inclusión está llamada a tener sobre las relaciones entre las partes de tales contratos, particularmente, en materia de responsabilidad; sobre las que se produzcan entre dichas partes y el o los aseguradores, tanto del casco y la maquinaria como de la responsabilidad civil frente a terceros; y sobre el derecho del asegurador que haya satisfecho una indemnización a subrogarse en las acciones que pudieran asistir a su asegurado frente a las demás partes involucradas en el entramado contractual y frente a terceros ajenos a él. The aim of this thesis is to gain a deeper understanding of the insurance clauses included in contracts for the use of the vessel, as well as the consequences that their inclusion is bound to have on the relationships between the parties to these contracts, particularly in terms of liability; on those between these parties and the insurer(s), both of the vessel and of third party liability; and on the right of the insurer that has paid an indemnity to be subrogated in actions that could assist its insured towards other parties involved in the contractual framework and towards external third parties.
Keywords: Assureur (responsabilité); Ciencies Jurídiques; Clauses d'assurance; Co-insurance; Co-seguro; Droit des assurances; Droit maritime; Insurance; Liability; Navire; Responsabilidad; Seguros; Shipping; Subrogación; Subrogation; Transportes marítimos

L'insécurité juridique de la norme conventionnelle en droit du travail : l'exemple du forfait-jours - Delamotte, Sullyvan (Université Bourgogne Franche-Comté, 2023)
La norme conventionnelle en droit du travail a la particularité de mettre au cœur de sa création les partenaires sociaux dont leur rôle s'accroit au fil des évolutions législatives. Néanmoins, il peut exister un manque de précision de la part du législateur, lequel se trouve alors comblé par la jurisprudence. Même si ce travail prétorien est salutaire, il intervient malheureusement après l'application de la norme invalidée, créant des situations complexes et parfois couteuses tant pour les salariés que pour les employeurs. L'exemple des conventions de forfait annuel en jours est particulièrement évocateur. Ce dispositif créé en 2000 pour pallier la réduction du temps de travail a connu de nombreux précédents jurisprudentiels du fait d'un manque de précision de la phrase « garantie du respect des durées maximales de travail ainsi que des repos, journaliers et hebdomadaires ». Loin d'être le seul exemple, l'étude de la sécurité juridique de la norme conventionnelle, de ses évolutions et influences, notamment par l’application des théories sur le pluralisme juridique, permet une meilleure compréhension des mécanismes à l'œuvre ainsi qu’un renforcement de la sécurité de la norme conventionnelle.
Keywords: Aménagement du temps de travail; Conventional norms; Day-Rate agreements; Droit du travail; Forfait-Jours; Insécurité juridique; Labour law; Legal insecurity; Legal pluralism; Norme conventionnelle; Négociations collectives; Pluralisme juridique; Règle de droit; Sécurité juridique

Les embargos et l'exécution des contrats internationaux - Sylla, M'Bouré Kaba (Université de Bourgogne Franche-Comté, 2023)
Les mesures d’embargo lorsqu’elles sont décidées unilatéralement par un État ou prises dans un cadre multilatéral par le Conseil de sécurité des Nations Unies sur le fondement du chapitre VII de la Charte des Nations Unies ont pour but d’interrompre tout ou partie des relations avec l’État que l’on entend sanctionner. En tant que normes impératives, les mesures d’embargo s’imposent à tout opérateur du commerce international ainsi qu’aux juges et aux arbitres internationaux qui sont dans l’obligation de les appliquer dès lors qu’ils sont saisis d’un litige relatif à un contrat international ayant pour objet une matière à embargo. S’agissant des opérateurs du commerce international, ceux-ci se voient ainsi interdire de poursuivre l’exécution des contrats qui rentrent dans le champ d’application des lois d’embargo. De ce fait, au regard du droit civil, ces mesures peuvent constituer soit un cas de force majeure, soit une cause d’imprévision libérant le débiteur de ses obligations contractuelles si elles réunissent les conditions de la force majeure ou d’imprévision requises par le système juridique compétent au titre la lex contractus ou par la clause de la force majeure ou de hardship. S’agissant du sort des contrats en cours d’exécution, ces mesures de nature temporaire entraînent d’abord la suspension du contrat. Le contrat n’est résolu ou résilié que lorsque l’embargo affecte durablement l’exécution du contrat. Les mesures d’embargo constituent ainsi une source de perturbations de l’économie des relations contractuelles. Dès lors, les opérateurs économiques pour se prémunir contre les risques de l’embargo insèrent des clauses de sanction. Toutefois, les périmètres très mouvants des embargos font que des stratégies de conformité efficaces doivent être mises en place.

Les conflits sociopolitiques en République Démocratique du Congo : une analyse dans la perspective de Paul Ricoeur - Nzila Yaav, Godefroid (Bourgogne Franche-Comté, 2023)
Les conflits sociopolitiques et les crises à répétitions qui ensanglantent la République Démocratique du Congo depuis des décennies, minent la vie de sa population et son avenir. Pays géostratégique pour l’Afrique et, sans doute, l’un des plus riches du monde en ressources naturelles mais avec une population maintenue dans la pauvreté. En effet, la mal gouvernance fragilise les institutions, engendre les conflits, suscite de la révolte et les violences. En outre, la crise congolaise vient de la perte des valeurs traditionnelles, éthiques et anthropologiques. C’est ce qui justifie le manque d’honnêteté, de sens de dignité et d’honneur, de cohésion interne et externe entre le dire et le faire, le manque de justice et de dialogue sincère ainsi que la corruption qui se trouve au sommet des anti-valeurs qui gangrènent ce pays. Pour ce faire, nous militons pour la bonne gouvernance comme un moyen efficace dans la prévention et la gestion des conflits sociaux.Dans ce sens, il nous faut des dirigeants qui s’auto-tiennent intérieurement, c’est-à-dire, des hommes éprouvés qui ont une moralité et des principes de vie qui témoignent de la responsabilité politique dont ils ont la charge pour la destinée d’une nation et d’un peuple. Au demeurant, il sied de noter que la démocratie est multiforme. Cela étant, quelle démocratie pour l’Afrique ? Il apparaît sagement que si l’Afrique continue d’imiter le système politique d’ailleurs, la catastrophe sera encore plus grande. Dans la dynamique de cette pensée, l’expérience de la vie sapientiale africaine, nous amène à faire appel à la sagesse pratique dans la gestion de la res publica pour un vivre-ensemble pacifique. C’est pourquoi, une bonne gouvernance fondée sur la sapience que nous appelons : la « sophiacratie » est une urgence pour la prévention et gestion des conflits en République Démocratique du Congo. Socio-political conflicts and repeated crises that have bloodied the Democratic Republic of Congo for decades undermine the lives of its people and its future. A geostrategic country for Africa, and undoubtedly one of the richest in the world in natural resources but with a population kept in poverty. Indeed, poor governance weakens institutions, generates conflicts, provokes revolt and violence. The Congolese crisis comes from the loss of traditional, ethical and anthropological values. This justifies the lack of honesty, a sense of dignity and honor, internal and external cohesion between saying and doing it, the lack of justice and sincere dialogue and the corruption that is at the top of the anti-values that plague this country. To do this, we advocate for good governance as an effective means of preventing and managing social conflicts.In this sense, we need leaders who hold themselves internally, that is, tried men who have a morality and principles of life that testify to the political responsibility they have for the destiny of a nation and a people.Moreover, it should be noted that democracy is multifaceted. That being said, what democracy for Africa? It wisely appears that if Africa continues to imitate the political system, the disaster will be even greater.In the dynamics of this thought, the experience of African sapiential life leads us to appeal to practical wisdom in the management of the res publica for peaceful coexistence. That is why good governance based on the sapience we call : "sophiacracy" is an emergency for conflict prevention and management in the Democratic Republic of Congo.
Keywords: Conflicts; Conflits; Conflits sociaux; Congo (République démocratique); Crises politiques; Democratic Republic of Congo; Identité (philosophie); Paul Ricoeur; République Démocratique du Congo; Sociopolitics; Sociopolitiques

Le licenciement pour motif économique : la quête de flexibilité et de sécurité juridique : étude comparée entre le droit français et le droit guinéen - Diallo, Ibrahima (Université de Toulon, 2023)
Le licenciement pour motif économique, non inhérent à la personne du salarié, n’a pas toujours été reconnu comme un mode autonome de rupture du contrat de travail. Aujourd’hui, sa légitimité en tant que régime autonome n’est plus remise en cause en France et en Guinée. Pourtant, le régime juridique du licenciement pour motif économique est souvent à l’origine de débats nourris dans la quête d’équilibre entre la liberté de gestion et la protection de l’emploi. Les réformes rythmées qui se sont succédé témoignent une certaine ambition pour un régime qui soit flexible et juridiquement sécurisé. Ainsi, la liberté d’entreprendre et le droit à l’emploi se chevauchent dans la mise en oeuvre de cette ambition. La première est souvent invoquée pour restreindre les mesures de protection des salariés ou, du moins, pour maîtriser le risque économique par l’employeur. L’attractivité économique et la question du contentieux judiciaire deviennent des critères déterminants sous l’angle de l’employeur. Néanmoins, la multiplication des crises illustre la nécessité d’adopter un régime qui garantit aussi la protection de l’emploi et l’effectivité des droits. Sans occulter les spécificités propres au droit français et au droit guinéen, la présente recherche défend un régime de licenciement pour motif économique qui tient compte de l’exigence de permettre à l’employeur d’agir, par des mécanismes appropriés, notamment dès les prémisses des difficultés économiques, mais aussi qui apporte un certain nombre de garanties aux salariés.
Keywords: Difficultés économiques; Droit comparé; Droit français; Droit guinéen / OHADA; Economic difficulties; Economic dismissal; Flexibility; Flexibilité; France; French law; Guinea Law / OHADA; Guinée; Legal security; Licenciement économique; Reclassement; Reclassification; Restructuration; Restructuring; Sécurité juridique

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

La terre : d'une propriété exclusive à un bien commun - Kouassi, Silhyac Jean-Vianney Léandres (Université Bourgogne Franche-Comté, 2023)
Le droit de propriété suivant la conception civiliste est celui qui confère une maitrise exclusive de l'ensemble des utilités d'un bien en vue de la satisfaction d'un intérêt privé: celui du propriétaire. Objet d'une appropriation exclusive la terre (le fonds de terre) est sous l'emprise du pouvoir souverain du propriétaire. Celui-ci s'attribuerait en vertu de la libre disposition qui lui est reconnue (l'abusus), un droit aux mésusages définit comme la faculté d'assigner une destination et/ou une affectation au bien, peu important que l'usage et/ou la finalité discrétionnairement déterminées soient contraires aux utilités objectives de la chose.Toutefois, sans s'inscrire dans la perspective d'une remise en cause radicale de la conception civiliste de la propriété, il importe de relativiser ce droit dont la teneur et l'intensité des prérogatives ne peuvent être invariables à l'égard de tous les biens. Il est en effet des biens dont le caractère commun de leurs utilités invite à repenser leur statut juridique et leur régime d'appropriation. Penser la catégorie des biens communs permettrait d'y intégrer des biens dont une ou plusieurs utilités sont bénéfiques à un collectif et participent à la préservation de l'intérêt général.Les utilités ou services écologiques assurés par la terre participent indubitablement à un intérêt général, un intérêt transcendant celui du propriétaire, un intérêt existentiel pour l'Humanité. Par conséquent, c'est en considération de la finalité ou fonction salvatrice qu'il est possible d'assigner à l'usage de la terre que l'idée d'une intégration de celle-ci dans la catégorie des biens communs est émise. Un statut nouveau (en ce sens qu'il coexiste avec la qualification d'immeuble par nature déterminée par le droit civil) pour un bien spécial implique une réforme ou a minima une évolution de son régime d'appropriation. Loin de toute hostilité à l'appropriation exclusive, la qualification de la terre en tant qu'un bien commun implique de concevoir son régime d'appropriation dans le sens d'un exclusivisme relativisé et non absolu, dans celui d'une propriété finalisée en faisant notamment allusion aux fonctions sociale et environnementale que ce droit peut accomplir.
Keywords: Bien commun; Environmental protection; General interest; Intérêt général; L'intérêt général; La propriété privée; La protection de l'environnement; Les biens communs; Les droits de l'humanité; Les utilités des sols; Private property; Propriété; Soil uses; The commons; Utilisation du sol; Utilisation du sol -- Droit

Essai sur la transmission de l'action en justice - Ung, Sreida Corinne (Université Paris-Saclay, 2023)
Chacun est libre de disposer de son patrimoine comme il l'entend, dans le respect de l'ordre public. Il est donc libre de transférer tout ou partie de son patrimoine. Il est traditionnellement admis que l'action en justice suit le droit subjectif substantiel auquel elle est liée, tel un satellite. L'intérêt de la transmission d'une action en justice indépendamment du droit subjectif substantiel peut être difficile à appréhender, comme il est difficile de concevoir l'utilité d'un satellite qui ne graviterait autour d'aucune planète. La difficulté liée à la compréhension d'une transmission de l'action en justice indépendamment du droit subjectif auquel elle est rattachée est également liée au fait que l'action en justice n'est pas admise comme un élément distinct du patrimoine. Bien que difficile à appréhender, une telle transmission n'est pas dénuée d'intérêt tant pour le transmettant que pour le bénéficiaire de la transmission. Pour le transmettant, l'intérêt de cette transmission réside de toute évidence dans la prise en charge par une autre personne des dépenses liés au procès, plus particulièrement s'il ne peut bénéficier de l'aide juridictionnelle ou s'il ne bénéficie pas d'assurance juridique. A l'image des sociétés de financement de procès, le bénéficiaire de la transmission recevrait une sorte de rémunération pouvant consister en un pourcentage sur le résultat obtenu en contrepartie de sa prise en charge des coûts du procès. Le transmettant s'évitera donc les frais d'un procès, tout en profitant des effets du jugement sur son droit subjectif substantiel.L'examen du droit positif force à reconnaître l'existence de figures de transmission de l'action en justice, avec ou sans le droit subjectif substantiel auquel elle est rattachée, avec ou sans le consentement de son titulaire.La présente étude se propose d'apporter un regard critique sur ces figures de transmission et de mettre en lumière les contraintes particulières attachées à la transmission d'une action en justice indépendamment du droit subjectif substantiel auquel elle est liée. Everyone is free to dispose of their assets as they wish, in compliance with public order. Then they are free to give all or part of their assets. It is traditionally and widely accepted that a legal action follows the substantial subjective right to which it is linked, as a satellite. It may be complex to apprehend the interest of a transfer of legal action without the substantial subjective right to which it is linked, as it may be difficult to understand the use of a satellite with no planet to orbit around. Legal actions are not considered an asset, which makes the understanding of its transfer without the substantial subjective right to which it is linked, more difficult to apprehend. Even though it is complex to understand, this transfer may be of interest. The one who gives their legal action will not have to bear the costs of a trial. This is of interest to them especially if they are not entitled to legal aid or if they don't have legal expenses insurance. As third-party funding in Common law countries, the one who receives the legal action may charge its remuneration on a percentage taken on the result of the trial. Then the giver will avoid the costs of going to court.A review of current substantive law forces us to recognize the existence of cases of transfer of legal actions, with or without the substantive subjective right to which it is linked, with or without the consent of its holder.This present study aims to present a critical view of these cases of transfer of legal actions and to highlight specific constraints of the transfer of legal action without the substantial subjective right to which it is linked.
Keywords: Action en justice; Actions et défenses; Assurance; Civil procedure; Clause de direction du procès; Clause de transfert; Contract; Contrat; Contrats; Legal action; Procédure civile; Supervision of the proceedings clause; Transfer; Transfer clause; Transfert (droit); Transmission

La confidentialité dans les rapports contractuels - Diallo, Amadou (Aix-Marseille Université, 2023)
Incontestablement, notre siècle est celui de l'information mais aussi celui de la transparence. La plus grande fortune se trouve dans l'immatériel et non plus dans les biens immobiliers, comme c'était le cas au moment de la rédaction du code civil de 1804. Le monde se dématérialise, mais il devient aussi de plus en plus transparent. Ces deux aspects se manifestent davantage dans les rapports contractuels qui constituent un terrain privilégié d'échange d'informations confidentielles. Malgré son importance, l'information, en tant que telle, n'est pas encore couverte par notre droit civil de la propriété qui a une connotation matérielle. En outre, elle n'est encore pas complètement couverte par le droit de la propriété intellectuelle qui a ses critères de protection très exigeants. L'instrument principal de couverture de l'information reste la technique de secret qui, par effet du législateur, a connu un développement particulier ces dernières années. En droit positif, la confidentialité dans les rapports contractuels est garantie par divers instruments légaux de secret. Cependant, cette diversité des régimes légaux n'est pas synonyme d'efficacité de la protection. Les instruments conventionnels de confidentialité sont encore nécessaires et les plus efficaces
Keywords: Business secrecy; Clause de confidentialité; Confiance; Confidential information; Confidentiality clause; Contrats; Duty of loyalty; Dématérialisation (informatique); Information confidentielle; Obligation de loyauté; Secret des affaires; Secret professionnel; Transparence; Transparence (droit); Transparency; Trust

L'application du droit transnastional sportif en droit positif camerounais - Kemo Alene Engamba, Philomène (Université de Limoges, 2023)
Cette thèse a vocation à révéler les différentes techniques qui concourent à rendre compte de l'applicabilité des normes transnationales sportives par les différents acteurs du sport camerounais. Ces normes transnationales sportives issues pour la plupart, d'organisations non gouvernementales sportives parviennent à organiser de nos jours de manière autosuffisante, le système sportif mondial. Ce droit transnational dont le respect est une condition indéniable pour que les fédérations sportives nationales soient reconnues par les Fédérations sportives internationales et partant, que les athlètes des pays puissent participer aux compétitions internationales ou même que ces pays puissent accueillir ce genre de compétitions, s'applique à des personnes physiques et morales et même sur des territoires qui relèvent normalement de la compétence d'Etats souverains. Le sport est donc de toute évidence marqué par une forme de pluralisme juridique structuré autour d'une interaction aussi bien complémentaire que potentiellement conflictuelle entre un ordre juridique sportif et un ordre juridique étatique. L'application par essence d'actes conformes et par nécessité d'actes compatibles, ne permet pas simplement de comprendre la manière dont un ordre juridique étatique appréhende les normes émanant d'institutions qui lui sont externes, mais bien plus, à démontrer comment cette application vient aujourd'hui ébranler le dogme positiviste qui fait de l'Etat la seule source de droit. La recherche n'aura pas ainsi simplement permis de mettre en évidence le diktat des FSI dans les pays en développement comme le Cameroun mais surtout, d'affirmer la prise en compte de l'existence de rapports de force entre les ordres juridiques. Finalement, l'application du droit transnational sportif dans l'ordre juridique étatique ne saurait faire l'objet d'une généralisation à l'ensemble des ordres juridiques car, c'est une application à géométrie variable qui tient compte de la « puissance » ou non des Etats en question. This thesis aims to reveal the different techniques that contribute to account for the applicability of transnational sports standards by the various players in Cameroonian sport. These transnational sports standards, which for the most part stem from non-governmental sports organisations, are now able to organise the world sports system in a self-sustaining way. This transnational right, the respect of which is an undeniable condition for the national sports federations to be recognized by the international sports federations and therefore, that athletes from countries can participate in international competitions or even that these countries can host this kind of competitions, applies to natural and legal persons and even in territories that normally come under the jurisdiction of sovereign States. Sport is thus marked by a form of legal pluralism structured around a complementary and potentially conflictual interaction between a sporting legal order and a state legal order. The application by essence of acts which are consistent and by necessity of acts which are compatible, does not simply make it possible to understand the way in which a State legal order understands the norms emanating from external institutions, but much more, to show how this application comes today to shake the positivist dogma that makes the State the only source of law. The research thus did not simply make it possible to highlight the diktat of ISPs in developing countries such as Cameroon but, above all, to affirm the consideration of the existence of power relations between the legal orders. Finally, the application of transnational sports law in the state legal order cannot be generalized to all legal orders because it is an application with variable geometry that takes into account the «power» or not of the States in question.
Keywords: Cameroonian positive law; Droit positif camerounais; Droit transnational sportif; Legal order; Ordre juridique; Sports -- Droit international; Transnational sports law

La sécurité juridique de la vente d'immeuble en France et au Maroc - Benchekroun, Abdelmalek (Université Paris 10, 2023)
La fiabilité des institutions étatiques, des normes juridiques qu'elles édictent ainsi que la sécurité juridique des transactions sont fondamentales pour une paix sociale au sein d'un Etat de droit. En particulier, toute personne impliquée dans une vente d’immeuble a grand intérêt à ce que l’acte soit rédigé et publié en toute sécurité. En première partie de la thèse, nous soutenons l’idée que cet objectif ne peut être atteint, tout d’abord, sans la conclusion d’un contrat valable, strictement contrôlé et efficace. Pour ce faire, le notariat latin que connait tant la France que le Maroc, constitue un moyen d'une efficacité inégalable. En effet, au regard de son caractère indépendant et impartial et du devoir de conseil qu’il doit aux parties, le notaire a vocation à tenir compte de tous les intérêts en présence. Il est tenu notamment d’effectuer un certain nombre de vérifications afin de s’assurer de l’absence de toutes manœuvres frauduleuses. De plus, le devoir de conseil du notaire commande que celui-ci assure l’efficacité juridique de l’acte, c’est-à-dire un acte dont les effets juridiques sont exactement conformes à la volonté des parties. L’intelligibilité de cette volonté est, en effet, indispensable à la sauvegarde d’une sécurité juridique que certaines lacunes de la loi fragilisent. De plus, l’acte authentique peut servir comme remède à tout manquement aux obligations contractuelles qui porterait atteinte son efficacité. Tout d’abord, sa force exécutoire en droit français représente pour les parties une garantie d’efficacité. L’adoption de ce principe en droit marocain constituerait incontestablement un gage de sécurité juridique en matière de vente d’immeuble. En outre, pour la poursuite de cet objectif d’efficacité, la qualité de l’encadrement législatif s’avère indispensable. En droit français comme en droit marocain, nous avons pu constater que les contrats les plus strictement encadrés sont les ventes d’immeuble à construire et les ventes d’immeuble existant. Cependant, pour ces contrats, tandis que le droit français est marqué par un phénomène d’inflation législative qui peut, in fine, mener à l’insécurité, un encadrement législatif renforcé est à préconiser en droit marocain notamment sur le plan de la protection du consentement de l’acquéreur. Par ailleurs, il a été souligné au cours de cette thèse qu’en France comme au Maroc, dès lors qu’un contrat se rapportant à une vente d’immeuble peut revêtir la forme sous seing privé, son encadrement et sa validité demeurent insuffisamment assurés. Il s’agit précisément des promesses de vente, des cessions de parts sociales de sociétés civiles immobilières, des actes d’avocat au Maroc et des ventes d’immeubles non immatriculés. Pour remédier à cela, en France comme au Maroc, la généralisation de l’authenticité obligatoire nous semble nécessaire au regard des garanties de sécurité juridique qu’offre l’acte authentique. Par ailleurs, dans le cadre des développements consacrés à la seconde partie de la thèse, nous soutenons l’idée que la sécurité de la publicité foncière conditionne directement et nécessairement la sécurité juridique de la vente d’immeuble. En effet, une fois l’acte de vente conclu, le rédacteur doit accomplir un certain nombre de formalités pour assurer au contrat une pleine effectivité. En France, la publicité foncière conditionne l’opposabilité de l’acte à l’égard des tiers, tandis qu’au Maroc, une formalité d’inscription sur le livre foncier est indispensable pour la reconnaissance de l’existence même du droit transféré. Ces deux États adoptent deux grands types de systèmes de publicité foncière dont la confrontation est classique, mais qui ont une même finalité : la sécurité du transfert des immeubles et des droits réels immobiliers. Il ne s’agit certainement pas d’indiquer si l’un doit prévaloir sur l’autre car, en fin de compte, les deux se valent lorsqu’ils assurent une publicité sécurisée, c’est-à-dire complète et fiable.
Keywords: Contrats; Droit français; Droit marocain; France; French law; Immeuble; Legal security; Maroc; Moroccan law; Notaire; Notariat; Sale of real estate; Sécurité juridique; Vente d'immeuble; Vente et transmission

Le contentieux individuel du travail : étude de droit comparé franco-marocain - Ouhlale, Imad (Université de Bordeaux, 2023)
Le conseil de prud’hommes est une juridiction paritaire qui a pour essence de concilier les parties. Cette juridiction est souvent décriée pour sa lenteur et la compétence insuffisante de ses juges, l’échec de la conciliation, le taux élevé d’appel, l’éclatement du contentieux. L’étude comparative a révélé que ces problématiques ne concernent pas uniquement cette institution, mais également la chambre sociale du Tribunal de première instance marocain. Cette juridiction échevinale procède elle aussi à la conciliation. Les mêmes griefs peuvent être formulés à son encontre, notamment l’échec de la conciliation, la non-spécialisation de ses juges, le taux élevé d’appel, la lenteur de la procédure, l’éclatement du contentieux.La thèse propose d’examiner des solutions adaptées à chaque juridiction sans apporter de changement radical. L’idée d’un projet de création d’un ordre juridictionnel autonome est irréalisable. Par ailleurs, la consolidation des juridictions du travail actuelles est la solution la plus raisonnable dans les deux systèmes, notamment par la formation et la spécialisation des juges, par l’allègement des tâches des greffiers et la revalorisation de leur rémunération et indemnisation. Il est également proposé de créer une école nationale de formation des greffiers au Maroc. Le recours au MARD est une solution pertinente face à l’encombrement des juridictions du travail en France et au Maroc. Le renforcement de la conciliation administrative devant l’inspecteur du travail en droit marocain est par ailleurs indispensable pour l’allègement de la juridiction du travail marocaine.L’étude comparative a également révélé qu’il n’y a pas de solutions archétypiques pour résoudre la problématique d’éclatement du contentieux, mais cela n’empêche pas de recourir à d’autres moyens pour le limiter comme la création de blocs de compétence à l’instar de récentes réformes, le recours à la question préjudicielle, à l’action de groupe, ou encore au mécanisme de demande d’avis. Les règles procédurales doivent être également améliorées et les délais de prescriptions unifiés comme c’est le cas en droit marocain. Ces mêmes délais doivent laisser suffisamment de temps aux justiciables pour pouvoir saisir le tribunal. Les règles de comparution et d’assistance doivent être allégées. En outre, il faut revoir les règles de prononciation et d’exécution des jugements en matière prud’homale comme en matière de conflits du travail marocains, en accordant plus de temps aux audiences, en réduisant les délais de procédure des délibérés et en renforçant le mécanisme de la mise en l’état. Par ailleurs, l’amélioration de l’exercice des voies de recours, notamment pour les deux degrés de juridiction en droit français et marocain, est indispensable pour garantir le droit d’accès au juge d’appel et de cassation. L’amélioration de la justice sociale ne pourrait être réalisée sans allouer aux juridictions du travail en France et au Maroc des moyens budgétaires, humains, matériels suffisants pour les rendre plus fonctionnelles.
Keywords: Action de groupe; Aldermen’s jurisdictions; Class action; Conciliation; Conseil de prud'hommes; Conseils de prud'hommes; Contentieux individuel du travail; Distribution of competences; France; Individual labour litigation; Juge du travail; Labour judge; Labour jurisdictions; Maroc; Mise en l’état; Paritarism; Paritarisme; Pre-trial procedure; Preliminary question; Question préjudicielle; Répartition de compétences; Travail (conflits); Tribunaux du travail; Échevinage; Études comparatives

Le préjudice collectif des créanciers d'une procédure collective - Touré, Abdou (Bourgogne Franche-Comté, 2023)
L’ouverture d’une procédure collective modifie les relations que le débiteur entretient avec ses créanciers. D’abord, l’entreprise du débiteur est placée sous protection de la justice. Ensuite, ses créanciers sont regroupés et forment un groupement appelé « le groupement des créanciers » en raison de la discipline collective à laquelle ils sont soumis. Le regroupement des créanciers consécutif à l’ouverture de la procédure collective est une manifestation de la discipline collective. La soumission des créanciers à une discipline collective s’explique par l’existence dans le déroulement de la procédure collective de leur intérêt collectif qui doit être défendu par les organes de la procédure compétents tout au long de celle-ci. L’intérêt collectif des créanciers d’une procédure collective est leur intérêt commun qui se traduit essentiellement par leur paiement. L’une des finalités de la procédure collective consiste à faciliter le paiement des créanciers selon l’ordre établi par la loi. Pour cette raison, l’intérêt collectif des créanciers est un élément constitutif de la discipline collective à laquelle ces derniers sont soumis et un élément constitutif de leur gage commun. Les biens du débiteur sous procédure collective sont le gage commun de ses créanciers qui doit, en théorie, être acccessible à eux tous. Dès lors, tous les agissements fautifs à l’origine de l’appauvrissement du gage commun causent un préjudice à ceux-ci. À propos de ces agissements fautifs, ils émanent du débiteur, des dirigeants de la personne morale, qu’il s’agisse des dirigeants de droit ou de fait, des organes de la procédure collective notamment le mandataire judiciaire, le liquidateur, l’administrateur judiciaire, le commissaire à l’exécution du plan, des tiers et toutes les personnes qui se rendent complices de la commission de ceux-ci. Ainsi, le Livre VI du Code de commerce consacré au traitement des difficultés des entreprises prévoit des sanctions civiles et pénales applicables à ces agissements fautifs. Le principe est que tout préjudice doit être réparé. De ce fait, le préjudice causé aux créanciers d’une procédure collective ne fait pas exception à la règle. En cas de procédure collective, le paiement des créanciers demeure le moyen permettant à ceux-ci d’obtenir une réparation, laquelle est soit intégrale, soit partielle. Cependant, la réparation du préjudice collectif des créanciers d’une procédure collective est parfois impossible.
Keywords: Action collective des créanciers; Collective action; Collective harm; Criminal liability; Débiteur et créancier; Entreprise en difficulté; Individual damage; Préjudice collectif; Préjudice individuel; Préjudice social; Préjudice économique pur; Public liability; Recours collectifs (droit); Responsabilité pénale et civile; Troubled company

Merchandising e o princípio da identificação da publicidade - Filomeno, Jose Geraldo Brito (Universidade de São Paulo, 2023)
O fenômeno da globalização, decorrente do avanço tecnológico e consequente encurtamento das distâncias em face da massificação dos meios de transporte, promoveu o deslocamento da base econômica do sistema produtivo para o sistema de consumo, bem como aumentou a oferta de produtos e serviços no mercado. Com isso, instigou-se a batalha diária entre os fornecedores para conquistar a liderança da concorrência, ou mesmo manter-se no mercado, visível, segundo o jargão que quem não é visto não existe. Para tanto, fornecedores e agências de publicidade e propaganda recorrem aos meios de comunicação de massa, sendo mais presentes na televisão em razão da força desse veículo no atendimento do desiderato de investir no discurso subjetivo a fim de penetrar no imaginário do consumidor, por meio de técnicas de persuasão/sedução que o induzem a desejar o produto ou serviço objeto de publicidade e propaganda, no caso deste trabalho, por meio do merchandising. E hodiernamente esse fenômeno está igualmente nas redes sociais, onde se destacam os autodenominados influenciadores ou youtubers que, destacando-se por algum motivo (música, gastronomia, cosmetologia etc.), são logo contratados para seus poucos minutos de mensagens trazendo conselhos mas cuja eficácia depende de produtos determinados. Considerados esses fatores, este trabalho tem por objetivo analisar a prática do merchandising no Brasil com o propósito de distinguir entre o que é bom e, portanto, aceitável diante das normas legais, no Código de Defesa do Consumidor, e de cunho moral, insertadas no Código de Autorregulamentação Publicitária, e o que é ruim e condenável e, portanto, merecedor da fiscalização, pelo Estado e outros não-governamentais, para garantir segurança ao consumidor, figura considerada vulnerável nas relações de consumo diante das técnicas de persuasão adotadas pelas agências de publicidade e propaganda, bem como pelos fornecedores de produtos ou serviços. As questões discutidas no decorrer do trabalho interessam não apenas aos profissionais do Direito, como também, como é curial, àqueles vinculados à atividade publicitária, notadamente no que toca à ética e às técnicas que a devem presidir, bem como a tantos quantos se dediquem ao estudo dos fenômenos psicológicos, porquanto as mensagens publicitárias contêm uma considerável dose de apelo às percepções conscientes e subconscientes e, quiçá, das inconscientes, sendo certo que nesse terceiro aspecto residem as maiores polêmicas atinentes ao merchandising.
Keywords: Abuses; Abusos; Acceptance; Aceitação; Identification Principle; Limites; Limits; Merchandising; Princípio da Identificação; Publicidade Subliminar; Understated Advertising

De l'influence américaine dans la lutte contre la corruption transnationale - Perez, Michel A. (Université Paris 1 Panthéon-Sorbonne, 2023)
Les sociétés et banques françaises ou européennes ont-elles été ciblées par les autorités américaines au prétexte de la lutte contre la corruption ? La thèse démontre, statistiques et textes officiels à l’appui, que cette conception est erronée. Depuis la promulgation de la loi anticorruption de 1977, les deux tiers environ des entités poursuivies aux États-Unis sont américaines, bien que les entreprises étrangères soient souvent celles qui paient les pénalités les plus lourdes. Pour expliquer ce phénomène, la thèse retrace les caractéristiques de la lutte anti-corruption qui a pris vers la fin du XXe siècle une dimension internationale. Les traditions de common law, opposées à celle du droit civil, les contextes géographique, historique et constitutionnel créent des différences de perception de la corruption et des approches pour la combattre. Aux États-Unis le moralisme, le juridisme, le fédéralisme et le pragmatisme sont des marques de naissance. Pourtant, même si elle est contraire à la vertu prônée par les Pères Fondateurs, la corruption a longtemps été tolérée. Néanmoins progressivement, à la suite de changements sociétaux et de crises, un dispositif performant se met en place. Le scandale du Watergate montre la dimension transfrontalière de la corruption. C’est pourquoi le Foreign Corrupt Practices Act, principale loi anticorruption, est doté d’une portée extraterritoriale. L’efficacité du système est renforcée par des pratiques originales et des procédures de « justice négociée ». Face à la domination américaine, d’autres juridictions, dont la France, ont tenté des mesures de blocage en invoquant le principe de souveraineté nationale. Mais l’essor de la mondialisation et d’un droit souple global mettent en cause la pertinence de cette approche. Les relations franco-américaines n’ont pas toujours été apaisées, mais une phase de coopération a débuté vers 2018, grâce notamment à l’introduction par la loi Sapin 2 de procédures compatibles avec celles américaines. La collaboration se trouve renforcée par le rôle croissant des institutions européennes, des ONG et surtout de l’OCDE pour développer un système international coordonné de lutte contre la corruption. Plusieurs chantiers, dont celui d’un système fiscal couvrant toutes les personnes, morales et physiques, dans le monde, sont en cours pour créer un jus commune. Il n’est ni réaliste, ni même souhaitable de vouloir renverser l’hégémonie américaine. Mais comme celle-ci désire établir sa légitimité, l’émergence d’une mondialité avec des objectifs communs mais dans le respect des différences, est possible. Elle serait le meilleur moyen pour, sinon éliminer, du moins réduire la corruption transnationale.
Keywords: Antimoney laundering; Barons voleurs; Blanchiment; Bribe; Compliance; Conformité; Coopération internationale; Corporate liability; Corruption; Corruption (prévention); Influence américaine; Lanceur d’alerte; Lutte contre la corruption; Pot-de-vin; Responsabilité pénale; Robber barons; Sanctions; Whistle blower; États-Unis

Accès à la justice en République démocratique du Congo : à la recherche de l'effectivité du droit - Kandolo Mundeke, Médard (Université Paris 2, 2023)
L’étude aborde l’accès à la justice comme un droit fondamental, en prenant pour référence la République démocratique du Congo (RDC). Depuis son accession à l’indépendance, la RDC est confrontée à une spirale de problèmes structurels et conjoncturels qui entrave le fonctionnement du service public de la justice et remet en cause les fondements de ce pays en tant qu’« État». Avoir accès à la justice s’analyse comme un privilège pour la majeure partie de la population qui crie à l’arbitraire. Les entraves se ramènent à l’ignorance des textes de lois, à l’absence d’une justice de proximité, au manque d’indépendance du juge, ainsi qu'à la faible protection des victimes et témoins devant les instances judiciaires. D’où la méfiance de la population envers l’institution judiciaire et en contrepartie le recours aux pratiques sociales de règlement des différends. Devant cette évidence, résorber le clivage entre la loi et le vécu quotidien de la population est un réel défi. La crise de l’État et de l’institution judiciaire persistante exige l’instauration d’une justice de proximité à la portée de la population sans mettre en disgrâce le recours aux modes alternatifs. Cette étude préconise la refondation d’un système juridique adapté et ancré aux réalités sociétales. Seul, en effet, un système empreint de pluralisme juridique, passant par un accommodement entre tradition et modernité, formel et informel, justice étatique et transitionnelle pourrait relever le défi de garantir l’accès à la justice, en assurant réparation aux victimes et en sauvegardant le dialogue auteur-victime à travers l’arbre à palabre, trait identitaire du droit traditionnel africain. The study addresses access to justice as a fundamental right, taking the Democratic Republic of Congo (DRC) as a reference. Since its independence, the DRC has been confronted with a spiral of structural and conjunctural problems that hinders the functioning of the public service of justice and calls into question the foundations of the country as a 'state'. Having access to justice is seen as a privilege for the majority of the population, which cries out for arbitrariness. The obstacles are ignorance of the law, the absence of local justice, the lack of independence of the judge, and the poor protection of victims and witnesses before the courts lead to the population's distrust of the judicial institution and, in return to the use of social practices to settle disputes.Given this evidence, resolving the gap between the law and the daily life of the population is a real challenge. The persistent crisis of the State and the judicial institution requires the establishment of a local justice system within the reach of the population without disgracing the use of alternative methods. This study recommends the re-foundation of a legal system adapted and anchored to societal realities. Indeed, only a system marked by legal pluralism, involving an accommodation between tradition and modernity, formal and informal, state and transitional justice, could take up the challenge of guaranteeing access to justice, ensuring reparation for victims and safeguarding the dialogue between the perpetrator and the victim through the palaver tree, an identifying feature of traditional African law.
Keywords: ACCES AU DROIT; ACCESS TO JUSTICE; ACCESS TO LAW; Acculturation; Accès à la justice; Arbre à palabre; Colonisation; Colonization; Democratic Republic of Congo; Droit coutumier; Droit traditionnel; Fair trial; Justice transitionnelle; Legal pluralism; Legal standards; Legal system; Normes juridiques; Palabre; Palaver tree; Pluralisme juridique; Procès équitable; République Démocratique du Congo; Système juridique; Traditional law; Transitional justice

O segredo de negócio como direito de propriedade industrial em sentido estrito - Kilmar, Sofia Gavião (Universidade de São Paulo, 2023)
A presente tese de doutorado aborda a hipótese de segredo de negócio enquanto direito de propriedade industrial em sentido estrito. A introdução do trabalho versa sobre a relevância dossegredos de negócio na prática empresarial. Por sua vez, o Capítulo 1 é dedicado à disciplina jurídica dos segredos de negócio como atualmente firmada. Aborda, nesse sentido, as propostas de justificativa apresentadas para fundamentar a proteção jurídica conferida aos segredos de negócio. Em sequência, o Capítulo 2 do trabalho trata dos problemas observados em referidas propostas de justificativa da proteção a segredos negociais, demonstrando como as citadas propostas se mostram insuficientes e inadequadas para tanto. O Capítulo 2 também aborda como a insuficiência e inadequação das citadas propostas é prejudicial, pois gera insegurança jurídica. O Capítulo 3 apresenta a hipótese da tese, de justificativa de proteção aos segredos de negócio enquanto um direito de propriedade industrial em sentido estrito, equiparável, enquanto tal, a direitos de propriedade industrial já reconhecidos, como patentes, marcas e desenhos industriais. Para tanto, o Capítulo 3 aprofunda os conceitos de Direito de Propriedade Intelectual, de Propriedade Industrial, bem como as justificativas para a existência jurídica de direitos de Propriedade Industrial. Apresenta, ao final, a hipótese objeto da tese. Por fim, a conclusão traz considerações finais acerca do tema.
Keywords: Civil liability; Concorrência desleal; Contracts; Contratos; Industrial property; Intellectual property; Private property; Propriedade industrial; Propriedade intelectual; Propriedade privada; Propriété industrielle; Responsabilidade civil; Secret commercial; Segredos de negócio; Trade secrets; Unfair competition

Pluralisme juridique et gestion des ressources naturelles : approche anthropo-juridique de la Grande Muraille Verte au Burkina Faso - Ouedraogo, Fabrice (Université de Limoges, 2023)
Cette recherche traite de la contribution de l’Initiative Panafricaine de la Grande Muraille Verte pour le Sahel et le Sahara à l’évolution normative dans son tracé géographique au Burkina Faso. L’Agence Panafricaine de la Grande Muraille Verte pour le Sahel et le Sahara en tant qu’organisation intergouvernementale se positionne comme acteur institutionnel de la lutte contre les changements climatiques et la désertification. Cependant, la multiculturalité des pays membres interroge sur le modèle juridique apte à répondre à l’urgence écologique. A cela s’ajoutent la preuve de la légitimité et de la légalité de l’institution qui pourrait justifier une approche systémique du droit de préservation de la biosphère au Burkina Faso. Il est capital que soit posée la question de l’existence d’ordre juridique non-étatique et son interaction avec le droit positif. S’appuyant sur une démarche anthropo-juridique combinant l’exégèse par l’examen des textes législatifs et règlementaires, l’ethnographie juridique de la Grande Muraille Verte (GMV) et des systèmes de régulation chez les Moose, cette thèse a permis de réaliser une ethnologie juridique du droit endogène du vivant au Burkina Faso dans le tracé de la GMV. Les analyses anthropologiques font la preuve de l’existence de système de régulations juridiques endogènes chez les Moose. Cette régulation s’étend depuis l’ère précoloniale à l’époque de la cogestion coloniale pour enfin échoir sur l’ère postcoloniale par un pluralisme normatif tacite. La prise en compte de cet ordre juridique non-étatique est un facteur de renforcement du système de résilience des populations locales face aux changements climatiques. Pour les gestionnaires de la GMV, il se présente une solution à trois facettes pour le Sahel et le Sahara : elle consistera à l’émergence d’un droit des pratiques, d’une reconnaissance des traditions juridiques locales et d’une réhabilitation des ayants droits coutumiers. This research deals with the contribution of the Pan-African Initiative of the Great Green Wall for the Sahel and the Sahara to the normative evolution in its geographical layout in Burkina Faso. The Pan-African Agency of the Great Green Wall for the Sahel and the Sahara as an intergovernmental organization is positioned as an institutional actor in the fight against climate change and desertification. However, the multiculturalism of the member countries raises questions about the legal model capable of responding to the ecological emergency. Added to this is the proof of the legitimacy and legality of the institution which could justify a systemic approach to the right to preserve the biosphere in Burkina Faso. It is essential that the question of the existence of a non-state legal order and its interaction with positive law be raised. Based on an anthropo-legal approach combining exegesis through the examination of legislative and regulatory texts, the legal ethnography of the Great Green Wall (GMV) and regulatory systems among the Moose, this thesis has made it possible to a legal ethnology of the endogenous law of life in Burkina Faso in the layout of the GGW. Anthropological analyzes demonstrate the existence of endogenous legal regulation systems among the Moose. This regulation extends from the precolonial era to the era of colonial co-management to finally fall on the postcolonial era through a tacit normative pluralism. Taking this non-state legal order into account is a factor in strengthening the resilience system of local populations in the face of climate change. For the managers of the GGW, there is a three-faceted solution for the Sahel and the Sahara: it will consist in the emergence of a law of practices, recognition of local legal traditions and rehabilitation of the beneficiaries of customary rights.
Keywords: Anthropologie juridique; Coutume; Custom; Droit; Environmental Law; Environnement; Grande Muraille Verte; Great Green Wall; Legal anthropology; Legal pluralism; Légalité; Pluralisme juridique; Pragmatism

Propriété et domanialité publiques en Guinée - Camara, Ibrahima Sory (Université Grenoble Alpes, 2023)
Cette thèse est relative aux notions de propriété et domanialité publiques en droit guinéen. L'État guinéen étant le fruit d'une longue histoire (pré-coloniale, coloniale, post-coloniale), il est indispensable de faire une présentation de la situation juridique des biens publics guinéens en tenant compte des réalités de chaque période de l'histoire du pays, afin de mettre en lumière le caractère particulier de leur traitement juridique.Le droit domanial est une discipline en pleine évolution, mais malheureusement méconnue dans le paysage guinéen, ce qui explique d'ailleurs en partie l'échec constaté dans le processus de gestion et d'utilisation des biens publics par les décideurs politiques et administratifs. Ce travail mené dans une approche interdisciplinaire et empirique sur le droit administratif local - qui met en avant les difficultés contemporaines et propose des perspectives pour une gestion domaniale plus saine - ambitionne d'offrir des pistes d'amélioration de la gouvernance en la matière. This thesis aims to examine the notions of public property and domaniality in Guinean law. As the emergence of the Guinean State results from a long history (pre-colonial, colonial, post-colonial), it is crucial to study the legal situation of Guinean public property, considering the realities of each period in this country's history, to highlight the nature of the legal framework developed in this field.Public property law is a rapidly evolving discipline, but unfortunately, it is not well know in Guinea, which explains in part the failure of political and administrative decision-makers in the management and use of public property. This research, adopting an interdisciplinary and empirical approach of the administrative law of Guinean property - which highlights contemporary difficulties and proposes perspectives for a good management of public property - aims to suggest improving ways of governance of public property.
Keywords: Biens d'utilité collective; Biens publics guinéens; Collective utility property; Colonies agricoles; Concessions de terres; Domanialité publique; Droit administratif; Droit administratif des biens guinéen; Guinea; Guinean administrative property law; Guinean public property; Guinée; Propriété publique; Pubic domaniality; Public property

Les œuvres automatisées à l'épreuve du droit d'auteur : réflexions sur les créations réalisées par des systèmes d'intelligence artificielle - Fandiño López, Efraín (Université Paris Cité, 2023)
Les progrès de l’intelligence artificielle issus de la croissance de la puissance de calcul, des mégadonnées et des nouveaux algorithmes de plus en plus puissants ont permis l'automatisation de certaines activités intellectuelles humaines. Les créateurs sont donc directement concernés, car il est désormais possible d'automatiser le processus d’exécution de création humain. Ainsi, Il convient donc d'effectuer une étude approfondie sur les oeuvres automatisées afin de déterminer si elles sont conformes au droit d'auteur et, si ce n'est pas le cas, si le droit d'auteur doit être adapté pour s’adapter à ce nouveau phénomène. Cette étude soulève plusieurs questions fondamentales, notamment celle de savoir si une œuvre automatisée est licite et comment évaluer son originalité. Elle suscite également une interrogation quant au statut de l'auteur de l'œuvre automatisée. Ces problématiques sont davantage importantes, en raison de l'utilisation croissante des systèmes d'IA en tant qu'outils de création.
Keywords: Artificial Intelligence; Arts; Automated creations; Automated works; Copyright; Creaciones automatizadas; Créations automatisées; Derechos de autor; Droit d'auteur; IA générative; Inteligencia artificial; Inteligência artificial; Intellectual property; Intelligence artificielle; Intelligence artificielle générative; New technologies; Nouvelles technologies; Nuevas tecnologías; Oeuvres automatisées; Propriété intellectuelle; Technologie et arts

L'influence du dialogue social sur les politiques de prévention dans les entreprises de plus de cinquante salariés - Feutry, Sarah (Université de Lille, 2023)
Le basculement vers une nouvelle approche de la santé au travail se traduit par un ascendant de l’entreprise et des partenaires sociaux pour améliorer la prise en charge de la santé des travailleurs. La prépondérance de la logique conventionnelle cumulée au besoin d’une dimension multidisciplinaire pour gérer ces problématiques semble indiquer une certaine influence du dialogue social en matière de santé. Le législateur s’est donc progressivement tourné vers le dialogue social et professionnel ainsi que l’acteur syndical pour laisser la possibilité aux parties prenantes d’une entreprise de s’immiscer dans sa gestion. Les entreprises s’intéressent désormais de plus près à la qualité de vie au travail et au bien-être en régissant les problématiques relationnelles, matérielles et organisationnelles de l’activité. Privilégier une approche dialogique et collaborative génère une vision commune des problématiques et permet de tirer profit du partage de l’expérience de chacun. Avec cette promotion d’une gestion participative il est difficile d’échapper à la question de la responsabilité. A ce jour, les textes sont clairs, l’obligation de prévention reste exclusivement de l’apanage de l’employeur. Néanmoins la jurisprudence a démontré à plusieurs reprises qu’un employeur proactif pouvait s’exonérer de sa responsabilité transformant le résultat attendu de l’obligation de sécurité. A la lumière de l’autopsie de cette obligation, s’ensuivent les prémices d’une responsabilisation accrue du salarié et de son représentant.
Keywords: Comité social et économique; Dialogue social; Employeurs (responsabilité); Intelligence collective; Négociation collective; Partenaires sociaux; Santé au travail (prévention); Services de santé du travail; Sidérurgie -- Personnel; Sécurité du travail; Usines métallurgiques

L’action en réparation des préjudices subis en cas d’atteinte du droit à un environnement sain par l’exploitation minière : cas des communautés locales vivant dans la zone CEMAC - Andosmoui, Nature de Destin (Université de Montréal, 2023)
La zone CEMAC (Communauté Économique et Monétaire de l’Afrique Centrale) dispose d’innombrables ressources minières solides et liquides. Dans cette zone, l’exploitation minière est considérée comme un véritable levier stratégique de développement socio-économique. C’est pour cette raison que la vision 2025 ainsi que le Programme Économique Régional de cette zone communautaire l’ont érigé comme pilier de l’émergence économique et initié, entre autres, la création d’une académie minière, les projets transfrontaliers d’exploitation minière ainsi que l’adoption d’un code minier communautaire. Au-delà des commodités économiques qu’apportent l’exploitation minière aux pays membres de la CEMAC, il sied de souligner que cette activité demeure concurremment une des principales sources de dégradations environnementales dans cette sous-région. En effet, l’exploitation minière se déroule en plusieurs phases. Pendant la phase dite de concassage ou de broyage, des contaminants tels que le cadmium, le plomb, le sélénium et l’arsenic, utilisés pour extraire les minerais, sont rejetés dans l’air. Au contact de celui-ci, ces contaminants subissent des transformations physico-chimiques et finissent par polluer l’air. Lors de la phase dite de lessivage, certains de ces constituants toxiques composés généralement d’azote, de cyanure, d’ammoniac, de nitrate ou de nitrite sont, quant à eux, déversés dans des eaux domestiques utilisées par les communautés locales. Ces substances chimiques ne se dissolvent pas dans ces eaux. Au contraire, elles y restent pendant plusieurs années et finissent par devenir des foyers de pollution des eaux domestiques. Aujourd’hui, ces répercussions environnementales, qui constituent indéniablement une violation du droit à un environnement sain (DES), menacent non seulement la santé mais également la survie de plusieurs communautés locales vivant dans les pays de la zone CEMAC. Compte tenu des préjudices qu’elles subissent, ces dernières sont légitimement en droit de demander réparation. Selon certaines recherches dont celles effectuées par le Centre de ressources sur les entreprises et les droits de l’homme, malgré la multiplication des atteintes du DES du fait de l’exploitation minière et les dénonciations de la société civile dans cette sous-région d’Afrique, les principales victimes, en l’occurrence les communautés locales, n’entreprennent que rarement voire quasiment jamais une action en réparation devant les juridictions compétentes. C’est fort de ce constat qu’à travers une analyse positiviste de certains éléments règlementaires et socio-contextuels, cette thèse s’est proposée dans un premier temps d’identifier les principaux obstacles à l’origine de cette quasi-absence d’actions en réparation des communautés locales. Dans un second temps, elle s’est astreinte à proposer deux grandes pistes de réforme en la matière. Un double objectif sous-tend cette proposition. Elle vise d’abord à ménager le mécanisme d’action en réparation en la matière afin de faciliter voire encourager les communautés locales victimes des violations de leur droit à un environnement sain par l’exploitation minière à saisir les juridictions compétentes. Ensuite, elle vise également à garantir une obtention effective de l’indemnisation des préjudices qu’elles subissent du fait de l’activité minière. The CEMAC zone (Economic and Monetary Community of Central Africa) has countless solid and liquid mining resources. In this zone, mining is considered a real strategic lever for socio-economic development. This is why the 2025 vision and the Regional Economic Program of this community zone have established it as a pillar of economic emergence and initiated, among other things, the creation of a mining academy, cross-border mining projects and the adoption of a community mining code. In addition to the economic benefits that mining brings to CEMAC member countries, it should be noted that this activity remains one of the main sources of environmental degradation in this sub-region. Indeed, mining takes place in several phases. During the crushing or grinding phase, contaminants such as cadmium, lead, selenium and arsenic, used to extract the ores, are released into the air. In contact with the air, these contaminants undergo physical and chemical transformations and end up polluting the air. During the leaching phase, some of these toxic constituents, generally composed of nitrogen, cyanide, ammonia, nitrate or nitrite, are discharged into domestic water used by local communities. These chemicals do not dissolve in these waters. On the contrary, they remain there for several years and end up becoming sources of domestic water pollution. Today, these environmental repercussions, which undeniably constitute a violation of the right to a healthy environment (DES), threaten not only the health but also the survival of several local communities living in the countries of the CEMAC zone. Given the damage they suffer, these communities are legitimately entitled to claim compensation. According to some research, including that carried out by the Resource Center on Business and Human Rights, despite the multiplication of DES violations due to mining and the denunciations of civil society in this sub-region of Africa, the main victims, in this case the local communities, rarely, if ever, take action for compensation before the competent jurisdictions. It is with this in mind that, through a positivist, comparative and interpretative analysis of certain well-known regulatory and socio-contextual elements, this thesis first proposes to identify the main obstacles at the origin of this near absence of reparation actions by local communities. Secondly, it has attempted to propose two major avenues of reform in this area. The aspiration of this singular proposal is twofold. Firstly, it aims to spare the mechanism of reparation action in this matter in order to facilitate and even encourage local communities who are victims of violations of their right to a healthy environment by mining operations to bring their case before the competent jurisdictions. Secondly, it also aims to guarantee that the damages suffered by these communities as a result of the mining activity are effectively compensated.
Keywords: Civil liability; Class action; Compensation fund; Droits de la personne; Environment; Environmental damage; Exploitation minière; Fonds d’indemnisation; Human rights; Mining; Préjudices environnementaux; Recours collectif; Responsabilité civile

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

L'instrumentalisation des procédures collectives par les groupes de sociétés : réflexion sur une crise de légitimité en droit des entreprises en difficulté - Vas, Marie (Université Paris 10, 2023)
L’instrumentalisation des procédures collectives par les groupes de sociétés se manifeste au travers de deux affaires emblématiques : Cœur Défense et Sodimédical. Dès lors, l’instrumentalisation semble recouvrir les situations dans lesquelles l’effort collectif mis en place au sein de la procédure pour traiter les difficultés du débiteur n’apparaît pas légitime. La question de savoir à quel titre ces situations sont perçues comme illégitimes conduit à reconstituer le système formé par le droit des entreprises en difficulté afin de déterminer ce qui fait sa légitimité. Sa cohérence, son ordre tiennent à sa finalité essentielle : le traitement d’une entreprise en difficulté. Or, les conditions d’ouverture de procédures collectives n’étant pas appréciées à l’aune de cette finalité, une procédure collective peut être ouverte à l'égard d'un débiteur qui n’est pas une entreprise. Dans ces circonstances, la légitimité de l’application du droit des entreprises en difficulté est mise en cause. Ce droit est instrumentalisé dès lors qu’il bénéficie à un débiteur qui n’est pas une entreprise, ce qui trouve à se réaliser particulièrement au sein des groupes de sociétés où le principe de l’autonomie de la personne morale ne permet pas de se saisir de l’entreprise. La problématique révélée par l’instrumentalisation des procédures collectives par les groupes de sociétés démontre une crise de légitimité de l’application du droit des entreprises en difficulté.
Keywords: Droit économique; Economic right; Entreprise; Entreprises en difficulté; Firm; France; Groupes de sociétés; Groups of companies; Insolvency proceedings; Instrumentalisation; Instrumentalization; Legitimacy; Légitimité; Procédures collectives

L'action civile et le droit à un procès pénal équitable - Assamoi, Haumond N'doumi Nelly Brenda (Université de Limoges, 2023)
Le procès pénal n’est pas qu’un assemblage de règles techniques. Il est irrigué par les garanties du droit à un procès équitable qui implique un équilibre des droits des parties au procès. Dans la mesure où ces garanties ont été développées avant tout au bénéfice de la personne poursuivie qu’il fallait protéger face à un ministère public représentant la société et disposant de prérogatives considérables, l’équilibre procédural était surtout recherché entre ces deux parties principales au procès pénal. Cependant, avec l’action civile exercée devant les juridictions répressives, de plus en plus de parties défendant des intérêts variés, individuels et collectifs participent à la procédure pénale. La présence de ces parties civiles au cours du procès pénal, pour ancrée qu’elle soit dans le système juridique français, est une source de transformations de la physionomie du procès. En effet, compte tenu de leur diversité et de l’accroissement de leurs prérogatives ces dernières décennies, la configuration du procès pénal change : de bipartite il tend à devenir véritablement tripartite ce qui influe sur l’équilibre recherché entre les parties. Il devient donc nécessaire de déterminer et d’apporter des réponses à l’impact de l’action civile française sur l’économie générale du procès pénal au regard des garanties du droit à un procès équitable. Partant, un constat s’impose : la fragilisation du droit à un procès pénal équitable en présence d’une ou plusieurs parties civiles. Il apparaît ainsi que l’économie générale du procès pénal ne peut pas être envisagée à travers le prisme de rapports symétriques entre la ou les parties civiles, le ministère public et la défense. Les caractéristiques propres à chaque catégorie de parties civiles doivent être prises en compte pour adapter les règles du droit à un procès pénal équitable. The criminal trial is not just a collection of technical rules. It is guaranteed by the right to a fair trial which implies a balance in the right of each parties during the trial. So far, those guarantees have been developed for the benefit of the defendant who had to be protected against a public prosecutor representing society and having considerable prerogatives, the procedural balance was above all sought between these two main parties in the trial. However, with the civil action brought before the criminal courts, more and more parties defending various interests, individual and collective, participate in the criminal procedure. Although the presence of these civil parties during the criminal trial is rooted in the French legal system, it is a source of change for the structure of the trial. Indeed, given their diversity and the increase in their prerogatives in recent decades, the configuration of the criminal trial is changing: from bipartite it tends to become truly tripartite, which influences the balance sought between the parties. It therefore becomes necessary to determine and provide responses to the impact of French civil action on the general economy of the criminal trial with regard to the guarantees of the right to a fair trial. Therefore, one thing is clear: the weakening of the right to a fair criminal trial in the presence of one or more civil parties. It thus appears that the general economy of the criminal trial cannot be considered through the prism of symmetrical relationships between the civil party or parties, the public prosecutor and the defence. The specific characteristics of each category of civil parties must be taken into account to adapt the rules of law to a fair criminal trial.
Keywords: Action civile; Civil action; Criminal proceedings; Droit pénal; Droit à un procès équitable; Fair trial; Procédure pénale

Le juge du droit de la concurrence - Castryck Fernandez, Emmanuel (Université de Perpignan, 2023)
Un juge en droit de la concurrence est un juge qui est chargé de veiller à ce que les lois sur la concurrence soient respectées. La difficulté est que cette définition peut s’appliquer autant à un juge qu’à une autorité. En effet, le choix de ne pas adapter l’appareil juridictionnel pour une juridiction spécialisée s’est traduit par la création d’une Autorité de la concurrence aux pouvoirs proche d’une juridiction. S’expliquant par une forte prégnance du fait économique dans l’analyse des pratiques anticoncurrentielles, à l’avantage notamment de l’Autorité de la concurrence, le rôle du juge a pourtant évolué au fil des ans. Finalement, est apparu un clivage entre une action publique qui vise à prévenir, à dissuader et à sanctionner les comportements anticoncurrentiels et une action privée qui favorise la réparation d’un préjudice causé aux victimes de pratiques anticoncurrentielles. Il en résulte un rôle différencié dans l’application du droit de la concurrence qui renouvelle la réflexion sur la définition d’un juge du droit de la concurrence
Keywords: Autorité de la concurrence; Commerce (réglementation); Competencia; Competition law; Concurrence; Droit; France; Infractions économiques et financières; Judge; Juge; Juges

Avaliação para fins de apuração de haveres nas sociedades limitadas: apreciação de ativos intangíveis - Vilela, Renato (Universidade de São Paulo, 2023)
A avaliação para fins de apuração de haveres do sócio, decorrente de dissolução parcial de sociedades limitadas, deve apreciar ativos intangíveis da sociedade para aferir o seu valor patrimonial e da quota parte do sócio retirante, por força do art. 1.031 do Código Civil e do art. 606 do Código de Processo Civil. Essencialmente, o valor dos ativos intangíveis reside na sua expectativa de rentabilidade futura, que pode ser adequadamente avaliada por método econômico, sob a técnica do fluxo de caixa descontado. A doutrina e a jurisprudência são divididas em relação a admissão da avaliação de ativos intangíveis, via de regra analisada no âmbito da avaliação da sociedade, sob critério de continuidade e perenidade. A tese defende que os ativos intangíveis avaliados com base em expectativas de rentabilidade futura devem ser admitidos no escopo da avaliação para fins de apuração de haveres, desde que sob os estritos termos da avaliação conforme determinada pelo direito. O critério de avaliação aplicável é o da dissolução total ficta; o escopo da avaliação abarca todos os ativos sob controle da sociedade, escriturados pela contabilidade ou não, bem como os passivos; tais ativos e passivos são individualmente considerados e avaliados a preço de saída, de modo que o avaliador deve fazê- lo pelo método que retrate da forma mais adequada o preço de mercado do recurso sob avaliação. Deste modo, a tese propõe: a interpretação dos artigos 1.031 do Código Civil e 606 do Código de Processo Civil baseada na técnica dos termos e expressões empregados, bem como na análise do desenvolvimento do tema na legislação brasileira; critérios de reconhecimento dos ativos intangíveis para fins de avaliação; e interpretação pela adequação da avaliação econômica do preço de saída em relação a finalidade almejada pelo regime jurídico atual. The valuation for the purpose of calculating the partner\'s assets, resulting from the partial dissolution of limited liability companies, must assess the company\'s intangible assets to assess their equity value and the share of the withdrawing partner, pursuant to art. 1.031 of the Civil Code and art. 606 of the Code of Civil Procedure. Essentially, the value of intangible assets resides in their expected future profitability, which can be adequately evaluated by the economic method, under the discounted cash flow technique. The doctrine and jurisprudence are divided in relation to the admission of the evaluation of intangible assets, as a rule analyzed in the context of the evaluation of the company, under the criterion of continuity and perpetuity. This thesis argues that intangible assets evaluated based on expectations of future profitability should be admitted in the scope of the evaluation for the purpose of calculating assets, provided that under the strict terms of the evaluation as determined by law. The applicable evaluation criterion is the fictitious total dissolution; the scope of the assessment covers all assets under the company\'s control, whether or not recorded in accounting, as well as liabilities; such assets and liabilities are individually considered and valued at the exit price, so the valuer must do so using the method that most adequately portrays the market price of the asset under valuation. Thus, the thesis proposes: the interpretation of articles 1031 of the Civil Code and 606 of the Code of Civil Procedure based on the technique of terms and expressions used, as well as on the analysis of the development of the theme in Brazilian legislation; criteria for recognizing intangible assets for valuation purposes; and interpretation for the adequacy of the economic assessment of the exit price in relation to the purpose sought by the current legal regime.
Keywords: Apuração de haveres; Art. 1.031 do Código Civil; Art. 1.031 of the Civil Code; Art. 606 do Código de Processo Civil; Art. 606 of the Code of Civil Procedure; Assessment of assets; Ativos intangíveis; Dissolução parcial; Intangible assets; Partial dissolution

Preservação da empresa e interesse público : uma teoria sobre a recuperação judicial dos concessionários - Ramalho, Matheus Sousa (Universidade de São Paulo, 2023)
Tese de doutorado de Direito Comercial desenvolvida em forma de pesquisa bibliográfica e documental, com a utilização preponderante do método analítico e, em alguns momentos, do dialético, que objetiva investigar a recuperação judicial dos concessionários. A pesquisa almeja elaborar uma teoria que mapeie e segregue os vários interesses públicos e privados que orbitam em torno do contrato de concessão, visando encontrar um ponto de equilíbrio na relação existente entre o Concessionário e o Poder Concedente, assim como dos princípios da preservação da empresa e do interesse público no curso de uma recuperação judicial. Para tanto, o trabalho será dividido em três etapas: (i) a primeira parte dedicada à apresentação da estrutura funcional da recuperação, bem como às particularidades deste procedimento de reestruturação; (ii) a segunda parte dedicada ao estudo das concessões, apresentando as particularidades aplicáveis a esta figura jurídica, seus diferentes tipos e seus aspectos comuns; e, finalmente, (iii) a terceira parte cuja exposição é centrada no desenvolvimento da teoria investigando as particularidades da recuperação judicial dos concessionários. As principais questões a serem dirimidas neste trabalho são: (a) qual seria o tratamento dispensado à concessão na recuperação judicial; (b) teria o devedor em recuperação judicial o direito de ser e de se manter concessionário; (c) seriam sujeitos à recuperação os créditos derivados das multas administrativas ou as obrigações do contrato de concessão; (d) quais os efeitos do despacho de processamento sobre as prerrogativas do Poder Concedente e teria o juízo da recuperação judicial poderes de limitar tais prerrogativas; (e) como o Poder Concedente seria convocado para a recuperação judicial e qual seria a consequência desta convocação; (f) seria possível prever a venda da concessão como meio de recuperação, inclusive em forma de unidade produtiva isolada, e qual seria a consequência desta alienação; (g) teria ou não o Poder Concedente o dever de se manifestar de maneira fundamentada na recuperação judicial, considerando as regras do procedimento aplicáveis para outros credores e o seu regime próprio; e (h) considerando a fase de controle de legalidade, seria legal a previsão de tratamento mais favorecido para o Poder Concedente pelo devedor considerando a importância estratégica da concessão; e qual seria a extensão dos poderes do juízo da recuperação judicial para controlar manifestações e decisões do Poder Concedente no curso da recuperação judicial. Corporate law doctoral thesis developed in the form of bibliographic and documental research, with a preponderant usage of the analytical method and, in specific chapters, the dialectical method, focused on the investigation of the bankruptcy of public utilities\' grantees. The research aims to elaborate a theory that captures and segregates the multiple public and private interests that orbit over the public utility contract, looking for a middle ground in the relation between the public utility\'s grantor and the public utility\'s grantee, as well as the concerns over public interest and going concern preservation amidst a bankruptcy reorganization proceeding. In order to achieve such goals, the research was structured in three different parts: (i) the first one dedicated to the presentation of the functional structure of bankruptcy reorganization and the exposition of its specificities; (ii) the second part focused on the study of public utilities, taking into account all their particularities, different kinds available, and looking to identify their common aspects; (iii) the third part centered on the construction of a theory investigating the special aspects applicable to the bankruptcy reorganization of public utilities\' grantees. The major topics addressed in this work were: (a) how should the public utility contract be treated in a bankruptcy reorganization; (b) should a Debtor-in-Possession have the right to become a public utility\'s grantee or maintain such status after filing for bankruptcy reorganization; (c) should credits owed by the Public Utility\'s Grantor comprised in administrative fines or derived from the public utility\'s agreement be subject to bankruptcy reorganization effects; (d) which effects does the bankruptcy\'s automatic stay produce over Public Utility\'s Grantor entitlements and could the bankruptcy court impose some limitation to its usage; (e) how is Public Utility\'s Grantor summoned to bankruptcy court and what consequences could this summoning produce; (f) could a bankruptcy restructuring plan set a provision selling the public utility as a recovery strategy, even as a fire sale, and what consequences such sale could produce; (g) should or not Public Utility\'s Grantor manifest its positions reasonably and thoroughly while on a bankruptcy reorganization, taking into account restructuring procedural requirements imposed to all creditors and special legal regime applicable to Public Utility\'s Grantor; and (h) during procedural phase dedicated to checking legality and adequacy of all workouts prior to granting of reorganization, should bankruptcy court accept provision set on restructuring plan providing more favorable treatment to Public Utility\'s Grantor in relation to all other creditors, taking into account its approvalstrategic importance for debtor\'s duly restructuring; and what is extend of power of bankruptcy court as to challenge or control reasoning and decisions brought on by Public Utility\'s Grantor during reorganization.
Keywords: Bankruptcy reorganization; Concessões; Going concern preservation; Interesse público; Preservação da empresa; Public interest; Public utilities; Recuperação judicial

L'usus des droits sociaux - Gheidene, Tristan (Université Bourgogne Franche-Comté, 2023)
Le démembrement est traditionnellement défini comme un acte juridique entrainant le partage des attributs du droit de propriété sur un bien. L'usufruitier aura le droit d'user du bien (usus) et d'en percevoir les fruits (fructus). Sa seule limite est de ne pas porter atteinte à la substance du bien puisqu'il devra le restituer au nu-propriétaire à la fin du démembrement, celui-ci en deviendra alors pleinement propriétaire. Pendant la durée de l'usufruit, le nu-propriétaire ne détiendra que l'abusus qui est le droit de disposer de la chose. Mais il ne pourra pas exercer ce droit sans l'accord de l'usufruitier, en effet, le nu-propriétaire ne doit pas porter atteinte au droit de jouissance de l'usufruitier.Il existe des biens dépourvus d'usus ou dont l'usus et l'abusus se confondent. Il s'agit des choses consomptibles pour lesquels l'usufruit prendra la forme d'un quasi-usufruit. L'usufruitier n'aura plus pour obligation de restituer le bien démembré mais un bien de même quantité et qualité ou sa valeur estimée à la date de la restitution.Les droits sociaux n'étant pas des choses consomptibles, il existerait un usus des droits sociaux. La présente étude aura pour objectif de démontrer que les droits sociaux sont nécessairement dotés d'un usus puisqu'ils constituent des biens meubles fongibles mais non consomptibles et que le lien unissant l'associé à ses droits sociaux est un rapport de droit réel. La présente étude aura ensuite pour ambition de repenser le partage des prérogatives politiques dans le cadre d'un démembrement de droits sociaux, en distinguant celles qui relèvent de l'usus et celles qui relèvent de l'abusus. Ce nouveau partage sera l'occasion de s'interroger sur la qualité d'associé en cas de démembrement de droits sociaux et de proposer une solution à mi-chemin entre la théorie moniste et dualiste de la qualité d'associé : le nu-propriétaire et l'usufruitier partagent la qualité d'associé. Une telle approche nécessitera d'avoir un regard critique sur la position récemment adoptée par la jurisprudence qui refuse la qualité d'associé à l'usufruitier.
Keywords: Choses fongibles; Droits sociaux; Droits économiques et sociaux; Fongibilité; Fungibility; Shares; Usufruct; Usufruit; Usufruit de droits sociaux; Usus; Valeurs mobilières

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
Keywords: Antitrust law; Australia; Competencia; Competition Act, 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

La place contestée de l'arbitrage international en droit de l'investissement - El Issa, Rayyan (Université Paris-Saclay, 2023)
La place de l'arbitrage en droit de l'investissement est discutée. Les réfutations à son encontre grandissent. De nombreuses problématiques édulcorent la définition même de la notion d'investissement. Les controverses doctrinales restent toujours nombreuses et débattues à ce sujet. De même, des doctrines s'affrontent sur la question de savoir s'il faut ou non élaborer un corps de règles cohérentes pour des sentences arbitrales homogènes. L'opposition à l'arbitrage dans le droit de l'investissement se retrouve aussi dans les problématiques liées à l'exequatur des sentences arbitrales liées à l'arbitrage d'investissement dans l'Union européenne. Un manque de soutien apparent au développement de l'arbitrage dans l'Union européenne s'est installé, comme le démontre le récent traité CETA conclu entre l'Union européenne et le Canada. L'arbitrage d'investissement ferait courir le risque d'un recul de la souveraineté. En effet, du fait l'arbitrage d'investissement, les Etats seraient moins incités à légiférer sur des matières pouvant avoir un impact sur l'activité d'une entreprise étrangère, par crainte d'une procédure arbitrale. Un lien délicat apparait alors, entre souveraineté et arbitrage d'investissement. Plusieurs doctrines se sont longtemps affrontées, notamment celle élaborée par Calvo et Drago en Amérique Latine entre 1870 et 1900, proposant de réduire les droits des investisseurs étrangers, face à une doctrine opposée, celle militant pour un standard minimum international de protection des investisseurs étrangers. Or, une renaissance de ces débats apparaît aujourd'hui, avec une problématique liée à la souveraineté de plus en plus ancrée dans les débats liés à l'arbitrage d'investissement. Pourtant, l'arbitrage d'investissement doit être perçu comme une méthode permettant à des investisseurs de bénéficier d'un arbitre indépendant et permettant de « dépolitiser » les contentieux. Mais des Etats admettent de moins en moins que leurs lois établies démocratiquement pour l'intérêt général puissent être contestées par des investisseurs étrangers devant un tribunal arbitral. Des auteurs parlent de « chilling effect », par lequel des Etats n'osent plus légiférer, par crainte de contentieux ultérieurs. De plus en plus d'Etats refusent que leur droit soit remis en cause par des juges privés. Plusieurs questions se posent. Est-il toujours concevable de protéger davantage un investisseur étranger qu'un investisseur national ? Est-il légitime de privilégier des juges privés, plutôt que des juges nationaux pour trancher les litiges en matière d'investissement ? L'utilité de l'arbitrage peut être comprise, dans des pays où la justice étatique est dite « corrompue » ou « biaisée ». En pareille situation, un investisseur étranger est légitime à vouloir saisir un arbitre neutre et indépendant. Mais la légitimité d'avoir recours à l'arbitrage dans des pays développés bénéficiant d'une justice étatique indépendante pose plus de difficultés. Dès lors, faudrait-il limiter l'arbitrage d'investissement aux pays souffrant d'un déficit d'indépendance de justice étatique ? Et donc d'exclure ce mode de règlement des litiges en la matière dans l'Union européenne ? La « politisation » du débat est en pleine renaissance. L'arbitrage d'investissement est un domaine relativement jeune et il convient de se demander s'il s'agit là d'un mode de règlement des litiges adéquat et d'un mode adapté au commerce international en général ? Assistera-t-on prochainement ou assiste-t-on déjà à ce que des auteurs qualifient de « fin de cycle » ? Il s'agit de questions ancrées dans l'actualité, que ce soit en France ou ailleurs dans le monde. The place of arbitration in investment law is discussed. The rebuttals are growing. Many issues water down the very definition of the notion of investment. The doctrinal controversies are still numerous and debated on this subject. Similarly, doctrines clash on the question of whether or not it is necessary to develop a body of coherent rules for homogeneous arbitral awards. The opposition to arbitration in investment law is also found in issues related to the exequatur of arbitral awards related to investment arbitration in the European Union. An apparent lack of support for the development of arbitration in the European Union has set in, as demonstrated by the recent CETA treaty concluded between the European Union and Canada. Investment arbitration would run the risk of a decline in sovereignty. Indeed, because of investment arbitration, States would be less encouraged to legislate on matters that could have an impact on the activity of a foreign company, because of the fear of arbitration proceedings. A delicate link then appears between sovereignty and investment arbitration. Several doctrines have long clashed, in particular the one developed by Calvo and Drago in Latin America between 1870 and 1900, proposing to reduce the rights of foreign investors, in front of an opposing doctrine, that campaigning for a minimum international standard of protection for foreign investors. A revival of these debates is appearing today, with an issue linked to sovereignty increasingly rooted in the debates linked to investment arbitration. However, investment arbitration must be seen as a method allowing investors to benefit from an independent arbitrator and allowing disputes to be “depoliticised”. But states admit less and less that their laws democratically established for the general interest can be challenged by foreign investors before an arbitration tribunal. Authors talk about the “chilling effect”, by which States no longer dare to legislate, because of the fear of subsequent litigation. More and more States refuse to have their rights challenged by private judges. Several questions arise. Is it always conceivable to protect a foreign investor more than a national investor ? Is it legitimate to favor private judges, rather than national judges, to settle investment disputes ? The usefulness of arbitration can be understood in countries where state justice is said to be “corrupt” or “biased”. In such a situation, a foreign investor is legitimate in wanting to seize a neutral and independent arbitrator. But the legitimacy of having recourse to arbitration in developed countries benefiting from independent state justice arouses more difficulties. Therefore, should investment arbitration be limited to countries suffering from a lack of independence of state justice ? And therefore to exclude this method of settling disputes in this area in the European Union ? The “politicization” of the debate is in full revival. Investment arbitration is a relatively young field and it is worth asking whether it is an adequate mode of dispute resolution and a mode suitable for international trade in general ? Will we soon witness or are we already witnessing what some authors describe as the “end of the cycle” ? These are issues rooted in the news, whether in France or elsewhere in the world.
Keywords: Arbitrage; Arbitragem; Arbitration; Contentieux; Contentieux de la concurrence; Droit de l'investissement; Droit et État; Investment Law; Investments; Litigation; Souveraineté; Sovereignty

La Diplomatie juridique : Défense et illustration du droit français et du droit continental dans le droit global à travers les exemples de la médiation et de l'arbitrage international - Gontier, Jean-Yves (Université Paris-Saclay, 2023)
Dans la conception traditionnelle de la diplomatie, l'action extérieure des États est cantonnée aux domaines politique, économique et culturel. Le droit est plus rarement pris en compte comme outil d'influence dans l'action extérieure des États.Or, le droit joue un rôle fondamental dans la diplomatie économique. En effet, un pays qui n'est pas capable de défendre son système juridique est un pays qui économiquement est en péril, car c'est un pays qui ne peut pas s'exporter.Si la France par exemple, ou d'autres pays, se mettent à la remorque de l'Alternative Dispute Resolution jusque dans leur propre droit interne, ces pays ne pourront plus exporter leur système juridique au risque de ne plus pouvoir exporter tout court. Ils risquent alors de perdre une partie essentielle et substantielle de leur capacité de projection sur la scène internationale.De même, lorsque la francophonie économique perd du terrain, c'est tout un pan de la diplomatie économique qui perd de sa force de frappe.Avec les clauses compromissoires et clauses de médiation inspirées des modèles anglo-saxons qui se répandent dans les contrats internationaux, comment les juridictions des pays francophones qui ont été calquées sur le système judicaire français pourront-elles continuent à exister ? Les arbitres anglo-saxons finiront-ils par imposer lentement mais sûrement la Common law ? Il y a là un enjeu de diplomatie économique énorme.Nous verrons comment défendre au mieux la francophonie économique et juridique en évitant que l'Alternative Dispute Resolution ne devienne le cheval de Troie du droit anglo-saxon, avec à terme, le risque que des systèmes nationaux disparaissent.Ce sont là des questions légitimes et très graves, et l'on peut comprendre qu'elles soient posées avec une certaine persistance.Avec l'élargissement continu du champ des relations internationales, le droit doit devenir l'objet d'une politique extérieure stratégique à part entière. C'est pourquoi nous plaidons pour la mise en place d'une diplomatie juridique française et formulons des recommandations ainsi qu'une stratégie d'influence juridique extérieure.En prenant la défense et en illustrant le droit continental et le droit français dans le droit global à travers les exemples de la médiation et de l'arbitrage international, nous espérons contribuer à l'ébauche d'une théorie de la diplomatie juridique et à ouvrir des pistes nouvelles de réflexion en matière d'influence internationale, en particulier d'influence juridique internationale.Nous espérons contribuer ainsi modestement mais utilement à la défense du droit français et du droit continental pour que la confrontation et la compétition des système juridiques n'aboutissent pas à la domination d'un système juridique sur un autre mais que cette compétition aille au contraire dans le sens d'un meilleur équilibre entre les systèmes juridiques, dans le sens du progrès et de l'amélioration du droit français et du droit continental, mais aussi - s'il se peut -dans le sens des progrès dans la défense des causes et des valeurs universelles. In the traditional conception of diplomacy, the external action of States is confined to the political, economic and cultural domains. Law is more rarely taken into account as a tool of influence in the external action of States.However, Law plays a fundamental role in economic diplomacy. Indeed, a country that is not able to defend its legal system is a country that is economically in danger, because it is a country that cannot be exported. If France, for example, or other countries, follow the Alternative Dispute Resolution right up to their own domestic law, these countries will no longer be able to export their legal system at the risk of no longer being able to export at all. They then risk losing an essential and substantial part of their ability to project themselves on the international scene.Similarly, when the economic Francophonie loses ground, a whole section of economic diplomacy loses its strike force.With arbitration clauses and mediation clauses inspired by Anglo-Saxon models that are spreading in international contracts, how will the courts of French-speaking countries that have been modeled on the French judicial system be able to continue to exist? Will Anglo-Saxon arbitrators end up slowly but surely imposing the Common law? There is a huge stake in economic diplomacy here.We will see how best to defend the economic and legal Francophonie by preventing the Alternative Dispute Resolution from becoming the Trojan horse of Anglo-Saxon law, with the eventual risk that national systems will disappear.These are legitimate and very serious questions, and one can understand that they are asked with a certain persistence.With the continuous widening of the field of international relations, Law must become the object of a strategic foreign policy. This is why we plead for the establishment of a French legal diplomacy and formulate recommendations as well as a strategy of external legal influence.By defending and illustrating continental law and French law in global law through the examples of mediation and international arbitration, we hope to contribute to the sketch of a theory of legal diplomacy and to open new paths of reflection in terms of international influence, in particular international legal influence.We hope in this way to contribute modestly but usefully to the defense of French law and continental law so that the confrontation and competition of legal systems does not lead to the domination of one legal system over another but that this competition goes on the contrary in the sense of a better balance between legal systems, in the direction of progress and improvement of French law and continental law, but also - if possible - in the direction of progress in the defense of universal causes and values.
Keywords: Arbitrage; Arbitragem; Arbitration; Diplomatie; Diplomatie juridique; Diplomatie économique; Droit global; Economic Diplomacy; Global Law; Influence; Influence juridique internationale; International Legal Influence; Legal Diplomacy; MARD; Mediación; Mediation; Mediação; Médiation; Relations extérieures; Relations économiques internationales

La motivation de l’exercice des prérogatives contractuelles : l'exemple de la résiliation du contrat d’assurance par l’assureur - Leblond, Nicolas (Université Polytechnique Hauts-de-France, 2023)
Depuis 2014, l’article L. 113-12-1 du code des assurances impose à l’assureur de motuver la résiliation du contrat d’assurance qu’il prononce. Cette obligation de motivation faite suite à des obligations similaires qui avaient été déjà consacrées. L’objet du travail présdenté est de comprendre les ressorts de l’obligation de motivation imposée à l’assureur qui souhaite résilier le contrat, d’identifier ce que cette obligation dit de la perception contemporaine du contrat d’assurance et ce, afin d’en proposer un régime cohérent et adapté. Au-delà de la question technique, il s’agit aussi de mener une réflexion sur la place du risque dans notre société. La thèse ici défendu est que le contrat d’assurance est devenu un « contrat de nécessité », ce qui conduit à considérer que la motivation exigée de l’assureur doit reposer sur des motifs de nature à démontrer que l’assurance du risque de l’assuré est impossible. Le caractère nécessaire du contrat d’assurance justifie que l’assurance ne puisse être rompue que si elle est ou est devenue impossible.

La protection des données dans les contrats de cloud computing - Sadik, Sarah (Université de Perpignan Via Domitia, 2023)
L’accélération de la technologie numérique et le développement des services de cloud computing ont contribué à porter atteinte aux données. Par ce constat, le droit est intervenu et tente toujours d’apporter des solutions juridiques à ce besoin de protection des données numériques. L’intérêt de cette étude réside dans le constat que la technologie du cloud computing suscite des interrogations juridiques en ce qui concerne l’effectivité du droit et de la responsabilité des acteurs du cloud computing. Ces interrogations s’amplifient par l’effet de la mondialisation et du principe de libre circulation des données promu à l’échelle européenne. Dans ce contexte, la question est de savoir comment renforcer la protection des données dans les contrats de cloud computing ? La réflexion sur le renforcement de la protection des données est menée à partir d’un triptyque de protection attendue, la protection technologique, la protection légale et la protection contractuelle. Les travaux de recherches sont basés sur l’étude des mesures techniques de protection des données, du cadre légal (national, européen et étasunien) applicable à la protection des données et sur l’analyse des contrats de cloud computing. Cette étude a été réalisée en vue d’apporter des solutions aux lacunes légales et aux insuffisances technologiques pour protéger les données des personnes physiques et des personnes morales dans le cadre de l’exécution d’un contrat de cloud computing. Les solutions proposées reposent essentiellement sur l’adaptation du droit à la protection des données à caractère personnel des personnes physiques et du patrimoine informationnel des personnes morales, et l’ingénierie contractuelle
Keywords: Cloud computing; Contrats; Données; Informatique dans les nuages; Protection; Protection de l'information (informatique)

La production de l’intelligence artificielle comme objet du droit d’auteur - Billion, Arnaud (Université Jean Moulin Lyon 3, 2023)
Les systèmes dits d’intelligence artificielle peuvent obtenir des produits dont on se demande s’ils sont éligibles au droit d’auteur. Face à cette question, le juriste intellectualiste ne peut se contenter d’un modèle grossier de son droit, ni se satisfaire d’une approximative revendication. Il est alors invité à considérer la production artificielle de manière réaliste, dans ses caractères sériels et divergents. Ceci éloigne la possibilité d’une appréciation erronée des faits : il n’y a pas, le plus souvent, un produit créé par un utilisateur de l’IA. La production artificielle, ce sont avant tout des surnuméraires, outputs obtenus incidemment en très grand nombre, traces numériques d’une ingénierie indirecte et hautement itérative. Pratiquer l’exercice de qualification au droit d’auteur sur le cas artificiel fait comprendre les raisons de l’impossible protection : les choix libres ne peuvent être qualifiants que des formes originales créées (les logiciels) … ils ne sauraient qualifier toute forme lointainement obtenue. Face à ce cas limite, les caractères de l’œuvre de l’esprit se révèlent dans la cohérence du droit positif : la conception réalisée, la disqualification du fait d’une trop grande contrainte technique, la précision et l’objectivité de l’identification et les autres conditions d’entrée au droit d’auteur, viennent souligner la détermination autoriale, la convergence créative et l’intelligibilité sociale comme le sous-texte pré-conditionnel de l’institution.
Keywords: Algorithm; Algorithme; Artificial Intelligence; Artificial production; Author’s right; Computer-Generated work; Conception and realization; Conception assistée par ordinateur; Conception réalisée; Copyright; Creativity; Création; Création assistée par ordinateur; Cybernetics; Cybernétique; Droit d'auteur; Free choices; Inteligência artificial; Intellectual property; Intelligence Artificielle; Intelligence artificielle; Liberté créative; Logiciel; Originality; Originalité; Production artificielle; Software; Work of authorship; Œuvre de l’esprit

La protection des associés minoritaires : étude comparée de droit français et droit OHADA - Moundounga Mapangou, Ulrich (Université de Pau et des Pays de l'Adour, 2023)
La protection juridique des associés minoritaires se justifie en droit des sociétés et en droit OHADA par l’absence directe de la gestion des sociétés commerciales par ces derniers. De ce fait, les deux ordres juridiques mettent en œuvre plusieurs mécanismes afin de protéger les intérêts des minoritaires. Ces mécanismes sont de plusieurs natures à savoir des règles juridiques favorisant un traitement égalitaire de tous les associés ou des droits exclusifs aux associés minoritaires favorisant un équilibre de pouvoirs dans la gestion de la société mais également la coexistence d’acteurs capables de réguler le bon fonctionnement de la société, notamment le juge, les associations de défenses d’intérêts des associés minoritaires.Dans les sociétés où les enjeux économiques sont très importants comme les sociétés faisant appel public à l’épargne, les législateurs français et OHADA, soucieux de protéger les associés minoritaires, ajoutent au droit commun, l’intervention du droit des marchés financiers qui vient renforcer la protection des minoritaires, notamment dans l’exercice de leur droit de cession. Ainsi, l’on remarque que le droit des sociétés français et le droit OHADA utilisent quasiment les mêmes fondements juridiques pour protéger les associés minoritaires. Il existe plus de similitudes que des différences dans les deux ordres juridiques puis que le législateurs OHADA a entrepris une réforme en 2014 afin de renforcer considérablement les compétences des associés minoritaires dans la gestion de la société. Cette réforme du droit OHADA s’est quasiment rapprochée du droit de société.Toutefois, malgré les efforts du droit des sociétés français et du droit OHADA de protéger les intérêts des associés minoritaires, subsiste une précarité du statut des minoritaires. La loi de la majorité fait obstacle à ce que l’on puisse objectiver que la protection apportée aux associés minoritaires est absolument efficace. Pour en arriver à une protection efficace certains droits devraient être généralisés pour contrôler sereinement la gestion sociale et leurs intérêts. The legal protection of minority shareholders is justified in company law and in OHADA law by the direct absence of management of commercial companies by the latter. As a result, both legal systems implement several mechanisms to protect the interests of minority shareholders. These mechanisms are of several kinds, i.e. legal rules favouring equal treatment of all partners or exclusive rights for minority partners favouring a balance of power in the management of the company, but also the coexistence of actors capable of regulating the proper functioning of the company, in particular the judge, and associations defending the interests of minority partners.In companies where the economic stakes are very high, such as companies making public offerings, the French and OHADA legislators, anxious to protect minority shareholders, add to common law the intervention of financial market law, which reinforces the protection of minority shareholders, particularly in the exercise of their right to sell. Thus, it can be seen that French company law and OHADA law use almost the same legal basis to protect minority shareholders. There are more similarities than differences in the two legal orders since the OHADA legislators undertook a reform in 2014 in order to considerably strengthen the powers of minority shareholders in the management of the company. This reform of OHADA law has almost come close to company law.However, despite the efforts of French company law and OHADA law to protect the interests of minority shareholders, the status of minority shareholders remains precarious. The law of the majority prevents the protection of minority shareholders from being absolutely effective. To achieve effective protection, certain rights should be generalised in order to control the management of the company and their interests.
Keywords: Associé; Corporate law; Droit des sociétés; Droit des sociétés commerciales; Droits des associés; French law; Minoritaire; Minority; OHADA law; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires; Protection; Shareholders

Disrupção enviesada e viés na abordagem do consumidor na análise antitruste - Taufick, Roberto Domingos (Universidade de São Paulo, 2023)
Aprende-se que o progresso científico é inerentemente bom, que melhorou as condições de vida de todos os seres humanos e que a revolução digital está progressivamente ajudando a nivelar as condições de competir para todos. Mas as evidências empíricas contam outra história, quando o assunto são os efeitos das rupturas tecnológicas sobre as condições de vida das minorias. As mudanças tecnológicas sempre tiveram como inspiração um determinado perfil de consumidor, identificado como o cidadão padrão. Tecnologia, política, saúde e quase tudo o mais que se possa consumir foi criado, ou adaptado por e para se adequar ao interesse particular de um determinado perfil de indivíduo que controla a vida econômica, independentemente do quão estatisticamente relevantes sejam as minorias sociais. Como consequência, quanto mais distante alguém se encontrar do perfil do cidadão padrão, menos se sente contemplado por decisões empresariais, ou por políticas públicas que não a/o tiveram como público-alvo. Trazendo evidências doutrinárias inclusive fazendo amplo uso dos recursos tecnológicos mais avançados de comunicação, como podcasts, blogues e ensino a distância em canais na rede de computadores e estudos de casos que relatam como o passado, o presente e o futuro foram, ou estão sendo projetados para perpetuar o hiato que separa as minorias do cidadão padrão, esta tese coloca em evidência como a política antitruste também foi vítima de uma interpretação enviesada do consumidor e de como esse erro tem afetado as decisões em casos antitrustes. Finalmente, a partir desses achados, propõe as adaptações necessárias para corrigir a abordagem enviesada do consumidor e para criar tomadas de decisão inclusivas na seara concorrencial. We learn that scientific progress is inherently good, that it has improved the living conditions of all humans and that the digital revolution is progressively helping level the playing field for all. But empirical evidence related to the effects of technological disruptions on the living conditions of minorities tells another story. Technological changes have always addressed a certain profile of consumer, identified as the standard model citizen. Technology, politics, healthcare and almost everything else one can consume has been created or adapted by and to fit the particular interest of a certain profile that controls the economic life, regardless of how statistically representative minorities are in society. Because of bias, the more distant one falls from the tree of the standard model citizen, the less one feels contemplated by corporate decisions and public policies. Bringing compelling bibliographical evidence including wide use of the most advanced technological communication resources, like podcasts, blogs and distance learning channels on the Internet and case studies showing that the past, the present and the future have been or are being designed to perpetuate the minority gap, I show how antitrust policy has been affected by a biased understanding of the consumer and how that mistake has affected decisions in antitrust cases. Finally, I suggest adaptations that might be needed to correct the biased consumer approach and create inclusive decision-making in antitrust.
Keywords: Antitrust; Antitruste; Bias; Consumer approach; Consumidor; Disruption; Disrupção; Inclusiveness; Inclusão; Minorias; Minorities; Technology; Tecnologia; Viés

La protection pénale de la famille : étude comparée des droits français et algérien - Bouziane, Nacer Eddine (Université de Bordeaux, 2023)
Protéger la famille semble aujourd’hui constituer une finalité ignorée par le droit pénal contemporain. Ce dernier ne protège que des membres de la famille et non la famille elle-même. Si cela est confirmé dans le droit français par sa vision universelle des droits de l’homme, plaçant l’individu au centre du droit. Le droit algérien ne semble pas, a priori, partager cette même vision philosophique et juridique au regard de sa culture propre et de l’influence secondaire que joue le droit musulman sur ce dernier. Cette étude vise donc à vérifier cet apriori et à s’interroger sur l’existence d’une protection pénale commune de la famille dans les droits français et algérien ; qui pourrait par la même occasion aider à mesurer l’existence d’un phénomène de mondialisation du droit pénal. Cette étude comparée se focalise ainsi sur une double dimension, individuelle et institutionnelle en étudiant l'aspect critique de l'intérêt porté à la famille par le droit pénal. L'équilibre recherché entre les droits individuels et la protection de l'institution familiale en tant que groupe sera interrogé selon la méthode de recherche dynamique, qui porte sur l'universalisme de la protection pénale de la famille.
Keywords: Algeria; Algérie; Comparative law; Criminal family law; Dispositions pénales; Droit comparé; Droit musulman; Droit pénal de la famille; Droit transnational; Famille; Family; France; Muslim law; Protection; Transnational law; Études comparatives

Le droit de la résolution des défaillances bancaires : contribution à l'étude du traitement administratif des établissements de crédit peu solides ou défaillants - Moreau, Victoria (Université Côte d'Azur, 2023)
Si on eut un temps pu s'interroger sur la nécessité de régir les défaillances bancaires, l'intérêt de telles dispositions a été réaffirmé depuis les années 2000. Dans ce contexte, le législateur européen, désireux d'assurer la stabilité financière, a mis en place une véritable Union bancaire, dont le second pilier est composé d'un Mécanisme de résolution unique destiné à prévenir et à traiter les défaillances bancaires. Ont ainsi été conçus différentes procédures et instruments dits de résolution, pouvant être mis en œuvre par des autorités administratives spécialisées. Or, la notion de résolution bancaire est une notion qui semblait jusqu'alors inconnue. Pourtant, les dispositions qui la gouvernent ne semblent pas véritablement la définir, et lui octroient la nature de Mécanisme, qui parait inadaptée. En effet, en observant l'ensemble des éléments qui compose ce Mécanisme, il ne fait nul doute que le législateur ne s'est pas contenté de créer un dispositif de gestion des défaillances bancaires, mais est allé plus loin en élaborant un véritable droit sui generis. L'existence de ce droit doit être affirmée pour permettre à celui-ci d'être pleinement efficient. Il produit par ailleurs des effets considérables tant sur les sujets de droit qu'il gouverne, que sur les acteurs avec qui ceux-ci interagissent. Ces effets originaux participent à l'efficacité de la prévention et du traitement des défaillances bancaires. S'ils peuvent en ce sens être salués, certains risques doivent néanmoins être relevés, notamment à l'aune des droits fondamentaux. La jurisprudence naissante en la matière - mais déjà très instructive -, laisse présager un droit en évolution et aux enjeux multiples, qui fera sans nul doute l'objet d'un intérêt grandissant.
Keywords: Bank resolution; Banques (réglementation); Credit institution; Droits fondamentaux; Défaut de paiement; Entités systémiques; Etablissement de crédit; Faillites bancaires; Financial stability; Fondamental rights; Résolution bancaire; Stabilisation économique; Stabilité financière; Systemic entity

Le droit de visite et de saisie de l'article L. 16 B du Livre des procédures fiscales- contribution à l'étude de la protection du domicile par le juge judiciaire - Papagiannoulas, Anastasios (Université Paris-Saclay, 2023)
Le droit de visite et de saisie de documents de l'article L. 16 B du LPF constitue entre les mains de l'Administration fiscale une mesure d'enquête coercitive portant atteinte à l'inviolabilité du domicile. Validé par le Conseil constitutionnel, et par la Cour européenne des droits de l'homme, qui ont toujours considéré que les nécessités de la répression des infractions fiscales et de la fraude fiscale justifiaient l'attribution de telles prérogatives à l'Administration fiscale, le régime des visites fiscales se caractérise par les fortes garanties procédurales dont dépend la protection du domicile. Au premier rang de ces garanties se trouve le contrôle du juge judiciaire. L'ensemble des garanties en question a été particulièrement renforcé après l'arrêt Ravon de la Cour européenne des droits de l'homme, qui a subordonné le contentieux des visites fiscales au droit à un procès équitable. Leur aptitude à répondre aux exigences d'un équilibre subtil est la clé de la prépondérance des garanties procédurales en la matière. Celles-ci permettent, d'une part, de tempérer un déséquilibre structurel au stade d'autorisation et d'exécution des visites fiscales, qui se caractérisent par leur nature unilatérale et qui mettent sous pression le respect du domicile, tandis que, d'autre part, elles stimulent l'équilibre déjà présent après la visite fiscale, moment auquel la personne bénéficie du droit à un recours juridictionnel. A côté de ces garanties, les lacunes, tout aussi procédurales, du régime n'ont pas permis de davantage promouvoir cette difficile conciliation et de mieux protéger le domicile. A travers leurs effets négatifs, le renforcement des garanties procédurales réapparaît comme la condition indispensable d'amélioration de cette protection. Cette prépondérance des garanties procédurales se retrouve au sein du contrôle des visites fiscales par le juge judiciaire. Ce contrôle est réel et sérieux et peut ainsi être qualifié d'effectif. Pour autant, sa structure ne se calque pas pleinement sur les garanties de procès équitable. Ainsi, l'efficacité du contrôle du juge judiciaire est réduite. La prise en compte des garanties procédurales résurgit comme la condition indispensable de protection du domicile. Parallèlement avec le juge judiciaire civil, ad hoc compétent en matière de visites fiscales, le juge pénal renonce à contrôler cette mesure, bien que son contrôle soit une garantie indispensable et de nature à consolider les garanties procédurales et à mieux préserver le domicile. Son contrôle se caractérise également par une méconnaissance des garanties nécessaires pour assurer le caractère équitable du procès pénal.Le dénominateur commun de l'ensemble du régime des visites fiscales est la force des garanties procédurales, afin de protéger le domicile. Par ailleurs, ce régime a fonctionné comme un point de départ de leur extension, notamment en matière de perquisitions pénales. Un fond commun de garanties procédurales, assurant la protection du domicile, a priori et a posteriori, se forge progressivement et donne les garanties entourant les visites fiscales demeurent le noyau.
Keywords: Contrôle juridictionnel; Domicile (protection); Droits de la défense; Défense (procédure civile); Fraude fiscale; Fundamental defense rights; Garanties procédurales; Home protection; Inviolabilité; Judicial authority; Judicial control; Juge civil; Juge judiciaire; Juge pénal; Perquisition; Perquisitions et saisies; Procedural guarantees; Procès équitable; Respect du domicile; Saisie; Seizure; Visite fiscale

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

Ticari İşlemlerde Taşınır Rehni Kanunu uyarınca ticari işletme rehninin kuruluşu - Balkan, Nurdan (İstanbul Üniversitesi, 2023)
6750 sayılı Ticari İşlemlerde Taşınır Rehni Kanunu (TİTRK) 01.01.2017 tarihi itibariyle yürürlüğe girmiştir. TİTRK'de de ticari işletme, üzerinde rehin kurulabilecek taşınır varlıklardan biri olarak düzenlenmiştir. Hukuki niteliği itibariyle taşınır olarak kabul edilmeyen ticari işletmenin, taşınır varlıkların rehninin düzenlendiği bir Kanun'da kapsamlıca düzenlenemediği ilk bakışta görülmektedir. Bu nedenle ticari işletme rehninin kuruluşu tez konusu olarak seçilmiştir. Çalışmamızda TİTRK ile yapılan değişiklikler ve yenilikler ticari işletme rehninin kuruluşu özelinde incelenmiştir. Bu kapsamda ticari işletme rehninin kuruluşu konusu, TİTRK ve ikincil mevzuat, yeri geldikçe mülga TİRK ve TİTRK'nin mehazı olduğunu düşündüğümüz Uncitral Secured Transactions Model Law ile karşılaştırmalı olarak değerlendirilmiştir. Ticari işletme rehninin kuruluşu, ticaret hukuku, medeni hukuk ve borçlar hukukunun ilgili düzenlemelerinin bir bütün olarak incelenmesini gerekli kıldığından yeri geldikçe, TTK, TMK ve TBK'nın ilgili düzenlemeleri, tez konumuz özelinde incelenmiştir. The Law Numbered 6750 "The Law On Pledge Over Movable Assets In Commercial Transactions (TITRK)", which is a regulation that allows not only commercial enterprises but also many movable assets to be pledged without delivery entered into force as of 01.01.2017. In TITRK, a commercial enterprise is regulated as one of the movable assets that can be pledged too. However, it can be seen at first glance that the commercial enterprise, which is not considered as movable due to its legal nature, cannot be comprehensively regulated in the Law that regulates the pledge of movable assets. For this reason, the establishment of the commercial enterprise pledge has been chosen as the thesis topic. In our study, the changes and innovations made with TITRK were examined in terms of the establishment of the commercial enterprise pledge. In this context, the establishment of the commercial enterprise pledge have been examined in comparison with TITRK, its secondary legislation, mulga TIRK and Uncitral Secured Transactions Model Law, which we think is the basis of TITRK. Since the establishment of the commercial enterprise pledge requires the examination of the relevant regulations of the commercial law, civil law and law of obligations as a whole, the relevant regulations of the Turkish Commercial Code, Turkish Civil Code and Turkish Code of Obligations have been examined specifically for our thesis topic. In this section the secured transactions arrangements in comparative law will be discussed too.
Keywords: Commercial Transactions; Commercial institutes; Hypotheca; Movable Assets; Pledge of assets agreement; Rehin hakkı; Taşınır mal; Ticari işlemler; Ticari işletme rehni sözleşmesi; Ticari işletmeler; Ticari İşlemlerde Taşınır Rehni Kanunu; Trading operations

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

A legal analysis on how France, Germany, the European Union and South Africa responded to the United Nations guiding principles on business and human rights - Buis, Jeanette (University of Pretoria, 2023)
Globally, companies pursue profitability; they want lower prices for the goods they buy and for the services they use. To gain profit and keep their prices low, they contribute to human rights violations and/or the devastation of the environment. The UNGP is the UN unanimously endorsed instrument that encourages states to pass legislation to compel companies to exercise human rights due diligence and to report on their efforts. The United Nations Guiding Principles (UNGP) impose a duty on companies to conduct human rights due diligence that apprises them of possible human rights or environmental risk exposure in their international operations. States have a responsibility to assist those harmed by a company’s activities to seek judicial relief. The UNGP is a soft law instrument but has had a major effect in the field of business and human rights. Though a voluntary obligation, the UNGP has become the reference document and is used by Civil Society Organisations (CSO) to pressure states into passing regulations on business and human rights. In 2016 Germany passed a National Action Plan (NAP) and the Lieferkettensorgfaltspflichtgesetz (Supply Chain Due Diligence Act) in 2021. France passed a Vigilance Law (Loi de Vigilance) in 2017. Additionally, a UN resolution has initiated a treaty-making process, which might lead to an internationally legally binding instrument that will articulate companies’ responsibilities to avoid, mitigate and remedy human rights violations that their activities cause. The South African government’s response to the UNGP has focused on negotiating a legally binding instrument at an intergovernmental level. This research examines three countries’ varying responses to the UNGP, a soft law instrument. In February 2022 the EU Commission published a proposed directive on corporate sustainability due diligence. The proposed EU legislation aims to advance respect for human rights and environmental protection. The goal is to create a level playing field within the European Union which leads to the exploration of the role China plays in a globalised world. China aims to be more than the world's factory and to become a leader in innovation and high-end manufacturing.
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights due diligence; Mandatory corporate due diligence; RSE; United Nations Guiding Principles; responsabilité sociale des entreprises

Kurumsal yönetim bakış açısıyla mali durumu bozulan anonim şirketlerde alacaklıların menfaatinin korunması - Demi̇rel Özdemi̇r, Duygu (Kocaeli Üniversitesi, 2023)
Anonim şirketler hukukunda alacaklılar, şirketlerin dış finansman kaynaklarının merkezini oluşturmakta ve bu nedenle de son derece önemli bir menfaat grubunu teşkil etmektedirler. Bu durum şirket alacaklılarının çıkarlarının etkin bir biçimde gözetilmesi ve korunmasını gerekli kılmaktadır. Zira alacaklıların alacaklarına kavuşabilmeleri için müracaat edebilecekleri tek kaynak şirketin malvarlığıdır. Dolayısıyla anonim şirketin mali durumunun bozulması sonucu malvarlığının kayba uğraması veya uğrama tehlikesi altında olması, alacaklıların menfaatlerini zedeleyici niteliktedir. Bu durum mali durumu bozulan anonim şirketlerde, alacaklıların menfaatlerinin gözetilmesini ve özellikle de öncül (ex-ante) koruma imkânlarıyla bu risk gerçekleşmeden önce bu konuda tedbirler alınmasını gerektirmektedir. Kurumsal yönetim anlayışı, anonim şirketlerde menfaat grupları arasındaki çıkar çatışmalarının en iyi, en adil şekilde dengelenmesini hedeflemektedir. Bu itibarla bu tez çalışmasında söz konusu menfaat çatışmaları özelinde kurumsal yönetimin şeffaflık, adillik, hesap verilebilirlik ve sorumluluk ilkeleri çerçevesinde bir menfaat grubu olarak şirket alacaklılarının menfaatlerinin, mali durumu bozulan veya bozulma tehlikesi altında olan anonim şirketlerde nasıl gözetilmesi ve korunması gerektiği hususunda bir bakış açısı sunulması hedeflenmektedir. Bu bakış açısından hareketle sermaye kaybı yaşayan, borca batık hale gelen anonim şirketlerin mali durumlarının iyileştirilmesi maksadıyla sermayenin korunması esası benimsenerek öngörülen TTK m.376 hükmü ile bu hükmün uygulanmasına ilişkin Tebliğ kapsamında öngörülen düzenlemelerin, alacaklıların menfaatlerinin korunması bakımından etkileri tartışılmaktadır. Ayrıca ilgili hükümlerin, şirketlerin mali yapılarının güçlendirilmesi bakımından yeterlilikleri ve yerindelikleri, karşılaştırmalı hukuk düzenlemeleri de göz önünde bulundurularak eleştirel bir bakış açıyla ayrıntılı şekilde incelenmektedir. Creditors are the key to external financing sources for companies under the statute of joint stock companies, and hence represent an important figure interest group. This situation needs the effective supervision and protection of the company's creditors' interests. This is because the company's assets are the only source to which creditors can turn to acquire receivables. Hence, the loss or threatened loss of the joint stock company's assets because of its worsening financial situation is detrimental to the creditors' interests. This circumstance necessitates that the interests of the creditors of companies with a worsening financial situation be considered and that steps be taken in this respect prior to the realization of this danger, particularly with ex-ante protection opportunities. The corporate governance method strives to achieve the most equitable resolution of conflicts of interest between interest groups in joint stock companies. This thesis aims to provide a perspective on how the interests of company creditors, as an interest group, should be observed and protected in joint stock companies whose financial situation deteriorates or is at risk of deterioration, within the framework of the principles of transparency, fairness, accountability, and responsibility of corporate governance. From this perspective, to improve the financial situation of companies that have capital loss and become over-indebted, the effects of the provisions of TCC art.376 and the Communiqué, which are envisioned based on the principle of capital maintenance, are discussed in terms of protecting the interests of creditors. In addition, the adequacy and suitability of the relevant rules in terms of strengthening the financial structures of corporations are analysed in depth from a critical standpoint, considering the norms of comparative law.
Keywords: Corporate governance; Creditors; Financial distress; Joint stock company

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Anonim şirketlerde imtiyazlı paylar - Erten, Cengiz (Kocaeli Üniversitesi, 2023)
6102 sayılı Türk Ticaret Kanunu (TTK) ile Türk Ticaret Hukuku'nda özellikle anonim şirketler hukukunda yapılan değişiklikler arasında imtiyazlı paylarla ilgili düzenlemeler de bulunmaktadır. Mülga 6762 sayılı Türk Ticaret Kanunundaki (eTK) hükümlere benzerlik gösteren yönleri olsa da imtiyazlı paylarla ilgili daha ayrıntılı, yenilikler getiren ve önceki Kanun döneminde karşılaşılan sorunları gidermeye çalışan düzenlemelerin yapıldığı görülmektedir. TTK'daki imtiyazlı paylarla ilgili düzenlemelerin eTK döneminde ortaya çıkan sorunları giderip gidermediğinin ya da yeni sorunlara, belirsizliklere ve tartışmalara yol açıp açmadığının tespit edilerek değerlendirilmesi amacı bu tezin yazılmasına sebep oluşturmaktadır. Birinci bölümde önce genel olarak pay kavramı, imtiyazlı payın tanınması koşulları, imtiyaz kavramının terminolojik yönü ve mevzuatımızda konuyla ilgili düzenlemelerle hukuk sistemimize esin kaynağı olan yabancı hukuk sistemlerindeki düzenlemeler incelenmiştir. Ardından, imtiyaz tanınan hakların, eşitlik ilkesi, müktesep hak ve vazgeçilmez hak ile olan ilişkilerine değinilmiş ve imtiyazlı pay kavramının nasıl tanımlanması gerektiği üzerinde durulmuştur. Tezin asıl omurgasını oluşturan ikinci bölümde, imtiyaza konu haklar, malvarlığı hakları ve yönetim hakları olarak iki asıl eksen üzerinde incelenmiştir. İkinci bölüm için en fazla tartışılmış bulunan konu, yönetim haklarında imtiyaza ilişkindir. Yönetim haklarında imtiyazı oluşturan iki alt başlık, oy hakkında imtiyaz ve yönetim kurulunda temsilde imtiyaz ayrıntılı bir şekilde incelenmeye çalışılmış, imtiyazın kanundan kaynaklanan nedenlerle engellenmesinden bahsedilmiş ve diğer haklarda imtiyaza değinilmiştir. Tezin üçüncü bölümü imtiyazların korunması konusuna ayrılmıştır. Bu bölümde imtiyazlı pay sahipleri özel kurulunun (İPSÖK) yapısı, niteliği ve toplanması ile özel kurulun onayına bağlı kararlar halka açık olan ve olmayan şirketler dikkate alınarak açıklanmıştır. Üçüncü bölümde ayrıca İPSÖK kararlarına karşı açılacak iptal davalarıyla ilgili değerlendirmeler yapılmıştır. It is observed that although there are some similarities with the previous one, the new Turkish Commercial Code, Law No: 6102, introduces more detailed and innovative arrangements which is intended to provide an answer to the problems experienced during the abrogated code was in force in relation to preference shares. It is easily can be said that, by and large, the topic "preference shares" is the one of the most radically altered topic in the new code. The main purpose of this thesis is to shed light whether these innovative arrangements in the new code actually solving the problems that is intended to solve or, rather opposite, causing new problems and ambiguities. For this purpose, the first section of this thesis is allocated to analyse the concept of "share" in general and under which conditions the preference shares are granted first and then the meaning of the concept of "preference" is investigated. It is followed by subsections devised to identify the current domestic law, and comprative law that inspried the law makers in this area. In the following subsections it is attempted to explain where preference shares stand with respect to principle of equality, vested interests and inalienable rights, and how the concept of preference shares should be defined. In the second section, which constitutes the backbone of this thesis, the rights that are being subject of the preference shares are examined on the axis of the assest rights and the administrative rights. The topic of the administrative rights attached to preference shares is the most debated topic in this section. In this context under the head of the administrative rights, the issues related to priveleges in votes and the representation on the executive board are examined seperately in two separate subsections. Also in this subsection the issues of statutory basis of the prevention of preferences and the preferences in relation to other rights are grappled. The third section of the thesis is completely devised to the issues related to the protection of the preference shares. In this section the structure, qualifications, gathering of the board of preference shares owners and the decisions subject to approval of this board are explained in the context of private and public companies. In this section the suits that could be brought for the annulment of this board decision is evaluated briefly.
Keywords: Joint stock company; Preference Shares

İcra ve iflâs hukukunda ticarî işletmenin bir bütün hâlinde paraya çevrilmesi - Erzeybek, Hakan (Ankara Hacı Bayram Veli Üniversitesi, 2023)
Ticarî işletme, kendisine özgülenen malvarlığı unsurlarının tamamı ile kapsamlı bir organizasyon niteliğini haiz olup, ticarî ve ekonomik bir bütünlük arz etmektedir. Ticarî işletme, ticarî bir amaca özgülenen ve bütünlük arz eden yapısı gereği, tacire ait malvarlığı unsurlarından belki de en değerlisidir. Bu yapısı gereği ticarî işletme, cebri icra hukukunda alacaklıların ilk müracaat edeceği malvarlığı unsurudur. Alacaklıların borçluya ait mal veya hakların paraya çevrilmesi sonucu tatmin edilmesi, cebri icra hukukuna hâkim olan genel bir ilkedir. Ticarî işletmenin cebri icra hukukunda paraya çevrilmesi, kapsamında bulunan mal veya hakların niteliği ve çeşitliliği gözetildiğinde ayrı bir önem taşımaktadır. Ticarî işletmeye özgülenen mal veya hakların ayrı ayrı paraya çevrilmesi, bu mal veya hakların parçalanmasına sebep olacağından, işletme faaliyetinin sona ermesine yol açar. Ticarî işletme faaliyetinin devamlılığının zedelenmesi, alacaklı ve borçlu menfaatlerini doğrudan etkilediği gibi ekonomik, sosyal ve toplumsal bir kısım olumsuz etkileri de beraberinde getirir. Bu nedenle, cebri icra prosedürleri içerisinde ticarî işletme bütünlüğünün bozulmaması büyük önem arz eder. Ticarî işletmenin cebri icra yoluyla bir bütün hâlinde paraya çevrilmesi, işletmeye özgülenen mal veya hakların bütünlüğünün bozulmasının önüne geçerek, faaliyetin devamlılığını sağlayan bir paraya çevirme şekli olarak karşımıza çıkmaktadır. Bunun yanında, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi ile ayrı ayrı paraya çevirmeye nazaran daha yüksek gelir elde edilir. Çalışmamızda, öncelikle, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi açısından karşılaştırmalı hukuk sistemlerinde yer alan bazı düzenlemeler incelenmiştir. Daha sonra, ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin İcra ve İflâs Kanunu'nda yer alan her bir paraya çevirme türü açısından durumu ve ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin yerine getirilme usulü ile paraya çevirmenin etki ve sonuçları ortaya konulmaya çalışılmıştır. A commercial enterprise has the character of a comprehensive organization with all the elements of assets specific to it, and it offers a commercial and economic integrity. A commercial enterprise, due to its structure that is specific to a commercial purpose and offers integrity, is perhaps the most valuable of the elements of the merchant's assets. Due to this structure, a commercial enterprise is the first asset element that creditors will apply for in forced execution law. The satisfaction of creditors as a result of the conversion of the debtor's goods or rights into money is a general principle that dominates the enforcement law. The conversion of a commercial enterprise into money in compulsory enforcement law is of particular importance when the nature and diversity of the goods or rights covered by it are taken into account. The conversion of goods or rights specific to the commercial enterprise into money separately leads to the termination of the business activity, as this will lead to the fragmentation of these goods or rights. Damage to the continuity of commercial business activity directly affects the interests of creditors and debtors, as well as brings with it some negative economic, social and social effects. For this reason, it is of great importance that the integrity of the commercial enterprise is not disrupted within the forced execution procedures. The conversion of a commercial enterprise into money as a whole through forced execution appears as a form of conversion into money that ensures the continuity of activity by preventing the deterioration of the integrity of the goods or rights specific to the enterprise. In addition, a higher income is obtained by converting the commercial enterprise into money as a whole than by converting it into money separately. In our study, first of all, some regulations in comparative legal systems have been examined in terms of the conversion of commercial enterprise into money as a whole. Subsequently, the situation of the conversion of the commercial enterprise into money as a whole in terms of each type of conversion contained in the Execution and Bankruptcy Code, as well as the procedure for performing the conversion of the commercial enterprise into money as a whole, as well as the effects and consequences of the conversion into money have been tried to be revealed.
Keywords: Cebri icra hukuku; Commercial institutes; Compulsory enforcement law; Ticari işletmeler; Turkish commercial law; Türk ticaret hukuku

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Le paradigme du bail à usage professionnel de l'OHADA - Ilboudo, W. Justin (Université Laval, 2023)
Le bail à usage professionnel est un contrat nommé de l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA). Ce contrat est une figure apparentée au bail commercial dont il portait d'ailleurs le nom avant la réforme de 2010. Le bail commercial lui-même s'est historiquement détaché du contrat de louage des choses prévu dans le Code civil de 1804 pour répondre aux exigences des mutations sociales et économiques du premier quart du XXᵉ siècle en Europe. Le bail à usage professionnel se pose donc comme une forme d'arrangement contractuel entre une tradition assumée et une modernité voulue. C'est de cet arrangement qu'a surgi le besoin de s'interroger sur la logique qui le sous-tend pour découvrir s'il existe un objectif poursuivi par le législateur et s'il existe, dans quelle mesure l'ensemble de la règlementation et l'interprétation qu'en fait le juge sont cohérents avec l'objectif visé. Le postulat qui préside à cette étude c'est que les règles de droit ont une raison d'être et une histoire qui obéissent idéalement à la finalité impulsée par ceux qui les appellent à l'existence. Pour les fins d'une telle investigation, l'analyse économique du droit (AED) et le pragmatisme juridique ont permis de dégager un double objectif au bail à usage professionnel. Il correspond à la fois à un ratio legis, c'est-à-dire à la politique juridique du législateur et à un ratio juris, c'est-à-dire à une justice désirable inhérente à l'esprit du contrat. L'étude pose que l'un des objectifs poursuivis par le bail est la protection, non pas tant d'une partie faible ni même d'un fonds de commerce, mais de toute activité économique qu'abrite le local loué. Ce projet permet de rendre compte des règles qui régissent le bail comme des mécanismes de sécurisation de l'espace et du temps de jouissance donnés au locataire. À la lumière de cette finalité, il apparaît que la valorisation économique voulue est restée inachevée avec le traitement partial réservé à l'activité de l'entreprenant. Si le premier objectif du bail consiste en la protection de l'activité économique, le second concerne la protection des acteurs économiques eux-mêmes. Après avoir établi que le bail correspond à ce que la littérature économique appelle actif spécifique, il apparait que la formation et l'exécution de ce contrat constituent une occasion propice aux comportements opportunistes des parties prenantes. La thèse propose une synthèse de la notion d'opportunisme et suggère une lecture de la seconde partie des règles sur le bail comme autant de mécanismes de prévention et de sanctions de comportements opportunistes.
Keywords: Bail commercial; Bail à usage professionnel; Droit OHADA

Anonim ortaklıkta yönetim ve temsil yetkisinin devrinde yönetim kurulu üyelerinin hukuki sorumluluğu - Kalender, Süleyman (Çukurova Üniversitesi, 2023)
Anonim şirketlerde yönetim veya temsil yetkisi kural olarak yönetim kurulu tarafından kullanılmakla birlikte, özellikle halka açık veya büyük ölçekli ortaklıklarda söz konusu yetkilerin tamamının yönetim kurulu tarafından bizzat yerine getirilmesi uygulamada sık rastlanan bir durum değildir. Bu nedenle kanunda, yönetim kuruluna, yönetim veya temsil yetkisinin 6102 sayılı Türk Ticaret Kanunu' nun 367/I ve 370/II hükümlerinde yer alan şartlara uygun olarak, mevcut yönetim kurulu üyelerinden bir veya birkaçına yahut üçüncü kişilere devretmek suretiyle, şirketin yönetim teşkilatını belirleme yetkisi tanınmıştır. Şirket yönetimi konusunda uzmanlaşmış ve yeterli mesleki tecrübeye sahip olan kişilere yetkilerin devredilmesi, bir yandan şirkette profesyonelleşmeyi sağlamakta, diğer yandan kural olarak, devredilen yetkilerle birlikte bu kapsamda ortaya çıkabilecek hukuki sorumluluk da devredilmiş sayılacağından, yönetim kurulu üyelerinin hukuki sorumluluğunu sınırlandırmaktadır. Yönetim veya temsil yetkilerinin geçerli bir şekilde devredilmesi halinde, devredilen yetkilerle ilgili olarak yönetim kurulu üyelerinin hukuki sorumluluğu; murahhasların seçiminde, onlara verilecek talimatlarda ve murahhasların üst gözetiminde göstermeleri gereken makul derecede özen yükümlülüğü ile sınırlı olarak devam eder. Çalışmamızda, geçerli ve geçersiz yetki devri hallerinde, yönetim kurulu üyelerinin hukuki sorumluluğunun ne şekilde ortaya çıkacağı meselesi, mehaz İsviçre hukukundaki görüş ve yargı kararlarına yer verilmek suretiyle, detaylı bir şekilde incelenmiştir. Although the management or representation authority in joint stock companies is used by the board of directors as a rule, it is not common in practice that all of the said authorities are personally exercised by the board of directors, especially in publicly held or large-scale partnerships. For this reason, in the law, the board of directors is authorized to determine the management organization of the company by delegating the management or representation authority to one or more of the existing board members or to third parties in accordance with the provisions of the Turkish Commercial Code numbered 6102, 367/I and 370/II has been recognized. Delegation of powers to people who are specialized in company management and have sufficient professional experience, on the one hand, ensures professionalization in the company, and on the other hand, as a rule, legal responsibility that may arise in this context together with the delegated powers will be deemed to have been transferred, thus limiting the legal liability of the members of the board of directors. In case of a valid transfer of management or representation powers, the legal responsibility of the members of the board of directors regarding the delegated powers; limited to the reasonable care obligation that they must show in the selection of the executive directors, in the instructions to be given to them and under the supervision of the executive directors. In our study, the issue of how the legal responsibility of the members of the board of directors will arise in cases of valid and invalid delegation of authority has been examined in detail by including the opinions and judicial decisions in the Swiss law.
Keywords: Board of directors; Joint stock company

Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis

La protection des renseignements personnels du consommateur dans un système bancaire ouvert : étude comparative entre le droit canadien et le droit québécois ainsi que le droit de l'Union européenne et le droit français - Rakotomandimby, Lauriane (Université Laval, 2023)
Dans un marché bancaire oligopolistique, marqué par un nombre limité d'institutions bancaires et financières offrant des services bancaires de plus en plus innovants et attractifs à une quantité innombrable de consommateurs, le système bancaire ouvert a engendré la multiplicité de ces services, grâce aux entreprises de technologie financière qui se présentent comme des concurrentes de taille face aux banques traditionnelles. Désormais, le consommateur peut procéder à des transactions électroniques, dont celles relatives au paiement ou au transfert électronique de fonds, sans devoir passer au comptoir de sa banque traditionnelle. Depuis la mise en place du Règlement général sur la protection des données et de la Directive révisée sur les services de paiement au niveau de l'Union européenne, les entreprises commerciales peuvent avoir accès aux renseignements personnels, dont les données financières des clients de banques, notamment pour initier un paiement, par le truchement des interfaces de programmation d'applications. Toutefois, le traitement des renseignements personnels des consommateurs par les entreprises commerciales augmente le risque de vol d'identité, étant donné la présence d'une quantité impressionnante de données sur le Web, sans un contrôle adéquat pour en assurer la confidentialité. Les conséquences d'une fuite de ces données sont pourtant non négligeables, aussi bien à l'égard de la banque, de la personne concernée que de l'État qui doit en assurer une protection optimale. Devant ce phénomène où le consommateur est vulnérable, l'État intervient pour le protéger et contrebalancer le déséquilibre dans sa relation contractuelle avec les prestataires de services financiers.
Keywords: Approche comparée; Confidentialité des données; Consommateur; Droit comparé

Harmonisation in the rules governing the recognition of foreign judicial ship sales - Shao, Yingfeng (World Maritime University, 2023)
Ships, the high-value asset used in both seagoing and inland navigation, and in which various legal and natural persons have interests, must be secured against legal risks arising from any cross-border legal divergence. Legal certainty of ownership of the ship is therefore desirable but it is under challenge with regard to the judicial sale of a ship: the effects of a judicial sale may be denied in a jurisdiction other than the place where it was sold under the principles of state jurisdiction. Multiple efforts have been made to address legal uncertainty. Particularly important is a new treaty governing the international effects of judicial sales: the United Nations Convention on the International Effects of Judicial Sales of Ships (Beijing Convention). This dissertation is intended to contribute to that process by setting out two tasks; first, it seeks to identify the obstacles to the recognition of foreign judicial sales, providing additional knowledge which may aid national legal orders when deciding recognition approaches; second, it looks for a universal solution that better guarantees recognition which would benefit shipping. A comparative legal research exercise exploring similarities and dissimilarities in the municipal and international laws governing the recognition and sale procedures is undertaken. Research results are presented in this kappa and research papers, exhibiting the profuse difficulties a party seeking recognition may encounter in the current legal framework, and explains the new recognition approach under the Beijing Convention. Based on the research findings, a universal solution is proposed that avoids révision au fond, defines the finality of a judicial sale, and sets forth a fixed number of grounds for denial of recognition which may bring greater certainty. This purported optimal solution should guarantee equal treatment for all foreign sales seeking recognition before the registry while minimising the registrar’s burden of finding and examining foreign laws. In the interest of universality, this solution better accommodates disagreeing principles underlying certain aspects of the sale, viz., the ship’s location at the time of sale, the notification of sale, and the variance in the standard sale, namely, court-approved private sales, in a manner that more states may accept. This solution is largely in line with the recognition approach under the Beijing Convention. Considering the greater legal certainty the new instrument may bring, ratification is supported.

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk